An analytical model of geosynthetic-reinforcement pile-supported embankments simultaneously considering pile–soil differential settlement and geosynthetic-soil interface friction - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Lei Zhang; Hanyan Gu; Yanjun Qiu (European Journal of Environmental and Civil Engineering, 2026)

Mechanisms and long-term evolution of river valley contractions after impoundment in the upstream reservoir area of Baihetan - Mayong Jiang; Zhongjie Yu; Bowen Li; Zuhao Lyu; Guan Rong (European Journal of Environmental and Civil Engineering, 2026)

Mechanism-guided analysis of tunnel construction-induced surface subsidence based on InSAR monitoring - Zhonghua Jiang; Haiqing Yang; Anhua Ju; Rong Zhang; Muguang Diao (Tunnelling and Underground Space Technology, 2026)

Supercritical water gasification of high-salinity oily wastewater: study on inorganic salt deposition behavior and mechanisms - Siqi Rong; Hanbing Jia; Kun Jiang; Libo Lu; Zhiyong Peng; Jialing Xu; Hui Jin; Liejin Guo (Fuel, 2026)

Characterization and Expression Analysis of KCS Genes in Cotton: Insights Into Temperature-Regulated Fuzz Development - Yuchen Song; Langjing Hua; Yanan Xu; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Plant Molecular Biology Reporter, 2026)

RNA-binding protein BICC1 promotes gastric cancer progression via the PRRX1-MAPK signaling axis - Yuanxin Xing; Rong Fan; Xiuzhen Jiang; Wenshuai Zhu; Fubo Jing; Xiaoli Ma; Yunshan Wang; Yanfei Jia (Functional & Integrative Genomics, 2026)

The mercury-nitrogen nexus: Trade-off between nitrous oxide emissions and mercury methylation in rice paddy systems - Rong Huang; Yuzhu Huang; Qinghua Zhou; Jiayue Zhou; Xingyu Li; Ouping Deng; Bing Li; Bo Meng; Jiang Liu; Xinbin Feng (Water Research, 2026)

Ecosystem-specific patterns in soil dissolved organic matter (DOM) biodegradability: Validated by a multi-property persistence index for linking DOM and soil organic matter intrinsic characteristics - Shanyi Tian; Sihua Zhu; Songbo Yao; Hui Jiang; Jitao Lv; Rong Huang; Tongwen Zhang; Xiaolei Su; Yongguang Yin; Tao Jiang; Dingyong Wang (Journal of Environmental Sciences, 2026)

High-speed air circulation preserves curcumin bioactivity and enables pH-dependent intestinal release in oyster-based functional foods for IBD dietary intervention - Shuang Gao; Xue Jiang; Yi Rong; Huanhuan Chi; Ci Song; Shujia Wang; Ying Li; Jingjing Chen; Lida Yang; Huawei Ma (Food Research International, 2026)

Free polyphenols and multi-omics traits underlying antioxidant variation across Paeonia lactiflora leaf cultivars - Rong Liu; Yike Jiang; Zhiying Hou; Hengrui Qi; Qinyu Wang; Fengzhong Wang; Baohe Miao; Qiong Wang (Food Research International, 2026)

Identification of concentrated seepage pathways integrating hydrogeological mechanisms and data-driven modeling: a case study of the Baihetan hydropower station - Guan Rong; Huqi Zhang; Maiyong Jiang; Qinyan Qiu; Shilong Chen (Engineering Geology, 2026)

Thermally activated iron-rich Palygorskite for tetracycline hydrochloride removal via coupling adsorption and in situ Fenton-like oxidation - Chao Jiang; Rong Jiang; Ling Meng; Huiyu Li; Xiao Feng; Saeed Ahmed; Yongjun Feng (Applied Clay Science, 2026)

A low-cost method for planar localization of leakage points in closed landfills - Rong Liu; Yaohui Liu; Shiyu Jiang; Gaofeng Yang; Kouao Laurent Kouadio (Waste Management, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

NaOH-induced dual-vacancy engineering in ZnCdS solid solutions for enhanced photocatalytic hydrogen evolution - Rong Yan; Chunyan Du; Danlian Huang; Lin Shi; Hanbo Yu; Wenbo Xu; Yu Yang; Tian Ao; Tong Sun; Shasha Yi; Jingyi Jiang; Yiyi Deng (Journal of Environmental Chemical Engineering, 2026)

Stability analytical solution for the geosynthetic-reinforced pile-supported embankments based on an improved three-wedge model - Rong Sun; Xin Jiang; Canyang Cui; Jianbiao Du; Hanyan Gu; Yanjun Qiu (Geotextiles and Geomembranes, 2026)

Reducing the residual oil body content in soy protein isolate (SPI) through pH regulation and studying the changes in physicochemical, flavor profiles, and processing properties - Merga Nagassa; Shudong He; Shuyun Liu; Yulong Deng; Huimei Li; Rong Zhang; Jiazhen Song; Suwei Jiang; Hanju Sun (Food Chemistry, 2026)

TF2A ameliorates lipid metabolism in high fat diet mice as an oxidative derivative of EGCG with altered gut microbiota and hepatic transcriptomic profiles - Yiyun Zhang; Zongzhen Guo; Kefan Wei; Rong Li; Jiaqian Cao; Liang Zhao; Sujing Wu; Caili Feng; Qiliu Jiang; Yong Xue (Food Bioscience, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

A porous-media-based crystallization fouling model incorporating bidirectional coupling between flow and heat transfer - Jiang Li; You-Rong Li (Chemical Engineering Journal, 2026)

Iodine vapor adsorption induced liquid conductive metal-organic frameworks for self-powered humidity sensing - Weifang Zhang; Yuan Cheng; Lingling Zhuang; Ruijin Jiang; Cui-Cui Ji; Rong-Rong Xie; Yupeng Chen (Chemical Engineering Journal, 2026)

α-Ketoglutarate attenuates ammonium chloride-induced ferroptosis by maintaining mitochondrial homeostasis in grass carp (Ctenopharyngodon idellus) hepatocytes - Yuling Zhang; Chengchen Jiang; Dapeng Li; Rong Tang (Aquatic Toxicology, 2026)

Straw return regimes improve mollisol quality by reshaping microbial composition and metabolic profiles - Xinyuan Li; Yanhui Dou; Tingting Cui; Jing Xu; Yuxian Wang; Junqiang Wang; Rong Jiang; Shumin Sun; Guanghui Hu; Wanrong Gu (Applied Soil Ecology, 2026)

Seasonal hydrochemical variations of a regulated river in the North China Plain: mechanisms and implications for chemical weathering - Xi Yang; Tao-Tao Ji; Zhi-Yuan Zhang; Rong-Tao Ma; Xiao-Wei Jiang (Journal of Hydrology, 2026)

Ambient PM2.5 exposure and sleep quality: Evidence from circadian DNA methylation signatures in a population-based study - Yuting Wang; Shuzhen Liu; Jiahui Rong; Yaxin Luo; Siyuan Niu; Peifeng Guo; Xu Tang; Yujian Liang; Xiaoting Mo; Linhai Zhao; Shiwen Jiang; Tiantian Gu; et al. (Journal of Hazardous Materials, 2026)

Effects of nitrogen and phosphorus limitation on physiological regulation and Sulfur cycling dynamics in Symbiodiniaceae - Yu-Rong Zheng; Yu-Chien Kao; Chun-Ting Chen; Chih-Chung Yen; Nilubol Nuanjunkong; Guang-Yuh Jauh; Pei-Luen Jiang (Journal of Experimental Marine Biology and Ecology, 2026)

Screening of ACE inhibitory peptides in digestive products of TGase-induced GCSG and evaluation of their absorption and transport properties - Chenghong Jiang; Mingrong Chen; Qilin Huang; Youming Liu; Jianhua Rong; Mingtao Yang; Xibo Wang; Yang Hu (Food Chemistry, 2026)

LiDFOB/LiFSI/FEC-induced interphase regeneration and evaporative cooling of HFE in TMP-based electrolytes enable thermal runaway suppression of lithium metal batteries - Xiangming Hu; Hengyu Xu; Lihua Jiang; Yuan Cheng; Duxi Li; Duo Wang; Rong Fu; Shutong Jiang; Miaomiao Liu; Yurui Deng; Longfei Han; Mengdan Zhang (Chemical Engineering Journal, 2026)

Electrostatic-field-driven synergistic regulation of molecular conformation and mesostructure enables stable Na+ transport in 12 μm PVDF-HFP-based electrolytes - Jiaze Li; Rong Yang; Xiaobin Li; Aoyi Jiang; Xin Dong; Hongyu Shang; Yinglin Yan; Hyun Woo Kim; Jou-Hyeon Ahn (Chemical Engineering Journal, 2026)

A nonlinear constitutive model for fine sandstone considering freeze–thaw induced compaction and damage evolution - Qi Wu; Ruichen Luo; Bowen Li; Qinyan Qiu; Maiyong Jiang; Guan Rong (Bulletin of Engineering Geology and the Environment, 2026)

Spatiotemporal variations and influencing factors of the incidence of cervical and breast cancer among rural women in Anhui Province, China - Xiaoqing Song; Yi Lu; Rong Wang; Jian Mao; Yi Long; Wei Jiang; Jingwen Hu (Applied Geography, 2026)

Optimizing inlet design for improved water renewal and solids removal in circular tanks in recirculating aquaculture systems - Huacheng Li; Qiushi Yang; Wenhan Li; Chengchen Jiang; Tingting Xu; Yutian Yuan; Rong Tang; Li Li; Yale Deng; Dapeng Li (Aquacultural Engineering, 2026)

Role of pyroptosis in melanoma: Molecular mechanisms and therapeutic potentials - Xiao-Han Zhang; Ke Zhang; Xue-Chun Qu; Jing Zhang; Umm E. Laila; Bo Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2026)

The Study on the Biological Characteristics of Photobacterium damselae subsp. damselae Affected by the Deletion of the Iron Uptake System Genes tonB1 and tonB2 - Hua Jiang; Yufei Ji; Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Xiaojun Rong; Aijun Ma; Shuyi Li; Zheng Zhang (Fishes, 2026)
Photobacterium damselae subsp. damselae (PDD), a marine fish pathogen, has an unclear contribution of tonB genes to iron acquisition and pathogenicity. ΔtonB1-PDD and ΔtonB2-PDD mutants as well as their complemented strains were generated via homologous recombination from the virulent strain PDD1605. Growth was evaluated by monitoring OD600 with viable-count calibration, intracellular iron was measured using a colorimetric assay, biofilm was detected by crystal violet staining, transcription was analyzed through qRT-PCR, and pathogenicity was assessed via an 8-day intramuscular challenge in black rockfish (Sebastes schlegelii). Under iron limitation induced by 100 μM 2,2′-dipyridyl, the maximum density decreased from 4.51 × 108 CFU/mL in wild-type (WT-PDD) to 4.00 × 108 and 3.64 × 108 CFU/mL in ΔtonB1-PDD and ΔtonB2-PDD respectively, and was largely restored after complementation. The intracellular iron content declined from 3.75 × 10−4 ± 4.00 × 10−6 nmol/106 cells in WT-PDD to 3.13 × 10−4 ± 1.05 × 10−5 nmol/106 cells in ΔtonB1-PDD and 2.55 × 10−4 ± 2.00 × 10−5 nmol/106 cells in ΔtonB2-PDD. Compared with WT-PDD, biofilm formation was reduced by 22.1% in ΔtonB1-PDD and by 24.8% in ΔtonB2-PDD. Deletion of tonB2 induced mild yet statistically significant transcriptional alterations in multiple iron acquisition and virulence-related genes, while colony morphology, swarming motility, hemolysis, phospholipase activity, biochemical traits, and antimicrobial susceptibility remained unchanged. In the high-dose challenge assay, WT-PDD caused 100% mortality within 2 days, whereas ΔtonB1-PDD and ΔtonB2-PDD caused 17/20 and 18/20 deaths respectively; all infected groups reached 100% mortality by day 3. In the low-dose challenge assay, WT-PDD, ΔtonB1-PDD, and ΔtonB2-PDD caused 12/20, 12/20, and 13/20 deaths by day 2, with cumulative mortalities reaching 80%, 70%, and 80% by day 8, respectively. Kaplan–Meier analysis detected no significant differences among the survival curves at either challenge dose. These findings suggest that tonB1 and tonB2 play roles in iron acquisition, low-iron adaptation, and biofilm formation, with tonB2 deletion exerting greater effects on growth and intracellular iron accumulation under iron-limited conditions.

Chemical and isotopic constraints on sources of precipitation chemistry in the Yangtze River Delta: A multi-year comparison of mountain and urban sites - Yongbin Jiang; Fei Rong; Guo Hu; Fuchao Zhou; Yanjun Huang; Xiaoyun Wang; Tao Huang; Tao Zhong (Acta Geochimica, 2026)

Retraction notice to “Grassland greening impacts on global land surface temperature” [Sci. Total Environ. 838 (2022) 155851] - Xiangjin Shen; Yiwen Liu; Liyuan Wu; Rong Ma; Yanji Wang; Jiaqi Zhang; Lei Wang; Binhui Liu; Xianguo Lu; Ming Jiang (Science of The Total Environment, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Mitigating bioaerosol exposure risks in high-traffic clinics: Experimental and numerical optimization of air purifier interventions - Yongxin Wang; Zhijian Liu; Lei Jiang; Zirun Shi; Zijian Li; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2026)

Separation of V/Cr from the leachate of vanadium slag by solvent extraction to prepare vanadium electrolyte - Rong Jiang; Limei Chen; Qiuxiang Liu; Mingyu Wang; Guiqing Zhang; Qinggang Li; Wenjuan Guan; Shengxi Wu; XinSheng Wu (Hydrometallurgy, 2026)

The peroxisome RING-type E3 ubiquitin ligase-mediated peroxisome function is essential for Alternaria alternata pathogenicity: coordinated regulation of lipid metabolism homeostasis and redox balance - Qianqian Jiang; Yongcai Li; Yuanpin Nan; Rong Li; Yangyang Yang; Wenjuan Liu; Yang Bi (Fungal Biology, 2026)

From byproduct to bioresource: Antioxidant potential, flavor profile, and microbiological quality of recovered water from freeze-dried and rotary evaporation dried Muscat grapes - Mengru Li; Yilei Huo; Pengkai Tang; Xiaoying Zhang; Haiyu Du; Wuernisha Kadeer; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2026)

Uncovering the effect of drying process on aquaporin proteins and fruit quality of goji berry (Lycium barbarum), a worldwide popular functional food - Zhigang Li; Rong Jiang; Zhiqiang Wang; Juanjuan Mi; Juanhong Zhao; Zhanfei Liu; Yuan Liu; Guoqi Zheng; Shaohua Zeng (Food Chemistry, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Impacts of urban open space environments on residents' health: A perspective on potentially toxic metals in dust - Yue Zeng; Qiang Ban; Junjie Yu; Changchun Qiu; Yajie Jiang; Xinyu Liu; Dian Lin; Shiqi Yan; Yunqin Li; Binxin Wu; Wei Yu; Rong Yu (Environmental Pollution, 2026)

Corrigendum to “A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization” [Chemical Engineering Journal 532 (2026) 174382] - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Reaction-generated secondary phase advances electronic-phonon decoupling and boosted mechanical performance in Bi0.42Sb1.58Te3 alloys - Yi-lin Liu; Hao Liang; Chong-Yu Wang; Jiang-Hu Yu; Kang Yue; Qian Deng; Ju Rong; Jing Feng; Zhen-Hua Ge (Chemical Engineering Journal, 2026)

MOF-derived carbon composites: Magnetically induced high electromagnetic shielding effectiveness and intelligent regulation of absorption-dominated mechanism - Lin Chen; Yujun Rong; Xin Zhou; Xiyu Qiu; Xiaofan Ma; Shaohua Jiang; Jianzhong Guo (Chemical Engineering Journal, 2026)

Simultaneous point-of-care detection and virulence typing of Helicobacter pylori using multiplex recombinase polymerase amplification combined with lateral flow strip - Lele Song; Lufei Yuan; Zhoujie Ma; Rong Jiang; Jilu Shen (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Impacts of trunk height, tree planting density, and wall heating on flow and pollutant dispersion inside an urban street canyon - Yuan-Dong Huang; Yan-Jiao Jiang; Rong Ji; Ke-Xin Wang; Meng-Xin Chai; Yang Luo; Peng-Yi Cui (Environmental Fluid Mechanics, 2026)

Histamine regulation in shaping spindle refractoriness: a computational modeling study - Bo Wang; Qiang Li; Wen-Hua Wang; Wan-Rong Zan; Yi-Ming Li; Jiang-Ling Song; Rui Zhang (Journal of Computational Neuroscience, 2026)

Evaluation of acute neurotoxic effects induced by Gelsemium elegans in rats - Meng-Ting Zuo; Jiang-Yu Long; Chong-Yin Huang; Yi-Rong Wang; Xiao-Qing Xu; Zhao-Ying Liu (Toxicological Research, 2026)

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

Serum exosomes protect heat-stressed mouse 2-cell embryos: Enhanced antioxidant defense and base excision repair of oxidative DNA damage - Hong-Chuan Zhang; Si-Jing Qu; Xin-Lei Yan; Rui-Cong Wang; Shi-Yong Zhu; Rong-Feng Cao; Kai-Qiang Fu; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Exposure to high ambient temperature during pre-implantation impairs embryo transport and development in the oviduct: Potential association with ANO1 downregulation - Hong-Chuan Zhang; Rui-Cong Wang; Shi-Yong Zhu; En-Yan Wang; Yu-Feng Huang; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2026)

Deciphering the multivariable interactions of MOFs in heavy metal adsorption via explainable machine learning for sustainable and resource-efficient adsorbent development - Mingxing Jiang; Weiwei Fu; Xiaoliang Zhao; Rong Gao; Duanping Xu; Sitan Wang (Journal of Cleaner Production, 2026)

Evaluation of the aerosol transmission patterns and the airflow organization effectiveness in the respiratory outpatient clinic - Yongxin Wang; Lei Jiang; Zhijian Liu; Duo Cai; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Building and Environment, 2026)

Enhancing maize productivity via biochar and organic fertilizer applications: evidence from decade-long field experiments on soil nitrogen pool dynamics - Jinmeng Hu; Jiuhui Chen; Jun Yi; Pan Jiang; Biao Sui; Xiangmin Rong; Yuping Zhang; Jianwei Peng; Gongwen Luo (Plant and Soil, 2026)

Contrasting effects of iron oxides versus bentonite on the biodegradation and conversion of dissolved organic matter derived from single and mixed plant litters - Wen Xiao; Xue Li; Shuangshuang Jiang; Minghui Rong; Xinhou Zhang (Plant and Soil, 2026)

Seed dispersal drives competition between pair-growing trees: implications for forest community dynamics - Xifu Yang; Haifeng Gu; Guangshun Jiang; Ke Rong; Hongjun Li; Qinghua Zhao; Yanhui Guan; Feifei Yang; Wentao Zhang; Tongzuo Zhang; Zhibin Zhang (Plant Ecology, 2026)

An approach for detecting hemodynamic parameters in the carotid arterial system based on the priori relationship between blood pressure and arterial radius - Jin Wang; Yong-Jiang Li; Yu-Yuan Zhang; Jing-Rui Gu; Xian-Wei Wang; Dong Chen; Kai-Rong Qin (Medical & Biological Engineering & Computing, 2026)

Preparation of a carbon fiber brush for solid-phase microextraction of petroleum hydrocarbons from environmental water samples - Aiying Song; Wenjun Song; Guanying Qin; Quanjing Guan; Xiaoyu Guo; Wanfeng Jiang; Shaoping Zhang; Rong Liu (Analytica Chimica Acta, 2026)

HDAC inhibition reprograms stem cell fate to suppress infantile hemangioma vasculogenesis - Qiming Chen; Hao Rong; Chao Liu; Jiang Li; Jiawei Zheng; Qian Bian (Angiogenesis, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Highly-efficient peroxydisulfate activation by nonstoichiometric bismuth-copper bimetallic oxide for 2,4-dichlorophenol degradation - Yifan Jiang; Wei Zhang; Chengbo Bai; Chunping Su; Ying Liang; Rong Chen (Journal of Environmental Chemical Engineering, 2026)

Fabrication and adsorption behavior of a lithium manganese oxide-based β-Cyclodextrin/PVDF composite membrane for lithium extraction from salt lake brine - Gao Deng; Rong Jiang; Zhaofei Hou; Yongjun Feng (Journal of Environmental Chemical Engineering, 2026)

Collaborative optimization of thermal safety and interphase stability of sodium-ion batteries based on ethoxy (pentafluoro) cyclotriphosphazene additive - Xiangming Hu; Shutong Jiang; Lihua Jiang; Yuan Cheng; Duo Wang; Hengyu Xu; Duxi Li; Yurui Deng; Longfei Han; Mengdan Zhang; Rong Fu; Miaomiao Liu (Journal of Cleaner Production, 2026)

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Optimizing biochar selection for soil amendment: Unraveling the feedstock-texture interplay for enhanced crop performance - Rong Zhang; Zizhen Ma; Linhua Jiang; Wenjie Gao; Hongping He; Heng Yu; Tao Yu; Bo Yang; Chengtun Qu (Bioresource Technology, 2026)

Operational control mechanism and pilot-scale demonstration of integrated fixed-film activated sludge partial nitritation/anammox system - Zibin Luo; Chao Rong; Tianjie Wang; Yu Qin; Jiang Wu; Yan Guo; Yisong Hu; Zhe Kong; Taira Hanaoka; Shinichi Sakemi; Yu-You Li (Bioresource Technology, 2026)

Evolution Mechanism of Internal Swelling Induced by Gas Sorption of Coal Matrix: Theoretical Inversion and Numerical Simulation - Shouqing Lu; Yongfu Liu; Jiang Shi; Yujin Qin; Congmeng Hao; Zhanyou Sa; Jie Liu; Yongliang Zhang; Rong Zhang; Hao Zhang (Rock Mechanics and Rock Engineering, 2026)

Evaluation and analysis of signal quality monitoring for BDS‑3 B1C signal in the presence of various digital distortions - Xinyi Huang; Md Sahat Mahmud; Yiping Jiang; Rong Yang (Advances in Space Research, 2026)

Integrated Analysis of Bulk and Single-Cell Transcriptomics Identifies Prognostic Biomarkers in Breast Cancer Metastasis - Qi-Qiao Wu; Kun Liu; Jian-Fang Xu; Yi Zhang; Jun-Rong Jiang; Hui-Lin Wang; Lin-Feng Wang; Jia-Na Zhou; Juan Liu; Xin Lin; Huan Chen; Ying-Ying Guan; et al. (Biochemical Genetics, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Hormonally and chemically induced male-to-female sex reversal is independent of Y-chromosome number in common carp - Kuangxin Chen; Yuanqi Guo; Yi Rong; Zhaoxian Li; Mouyan Jiang; Rui Li; Xiya Zhang; Yongming Li; Yulai Wei; Yanlong Song; Ji Chen; Binbin Tao; et al. (Aquaculture, 2026)

A nitrogen-rich covalent organic framework with high conductivity for high specific capacity Li-ion battery cathode - Xiaoning Zhan; Yucheng Jin; Rong Jiang; Dongdong Qi; Xiya Yang; Qi Zhang; Qingmei Xu; Zhixin Liu; Liancong Yue; Hailong Wang (Science Bulletin, 2026)

Assessing green synergy efficiency to advance sustainable development goals: A multi-objective collaborative efficiency analysis framework - Xiaomei Shen; Rong Yan; Xiangqin Xu; Huiwen Fang; Mingdong Jiang (Journal of Cleaner Production, 2026)

An intelligent multi-stage fishway integrating computer vision and adaptive hydraulic control - Guiwen Rong; Tengyu Ma; Hongling Jiang; Shangzhi Chen; Yangyan Zhang; Guoqing Zhao; Hai Lin; Huaiqin Ran (Ecological Engineering, 2026)

Study on the deposition characteristics of crystallization fouling in rib channel based on CFD 3D dynamic mesh technology - Jiang Li; You-Rong Li (Desalination, 2026)

Non-volumetric phase transition of PNIPAM enables high-sensitivity temperature monitoring and photoelectric therapy for wound care - Jie Ding; Danni Hou; Yuan Tian; Rong Li; Yuyan Wang; Junzhong Jiang; Yucai Hu; Chengheng Wu; Dan Wei; Jing Sun; Zi Qiao; Hongsong Fan (Chemical Engineering Journal, 2026)

An arabinogalactan from Bupleurum chinense DC. attenuates LPS-induced inflammation in RAW264.7 macrophages - Bowen Zheng; Chenxu Jiang; Zheng Wang; Qiuhong Zhang; Hang Du; Nana Huang; Jin Wang; Jinhua Du; Daizhou Zhang; Rong Sun; Daijie Wang (Carbohydrate Polymers, 2026)

Aerosol optical depth in the Yellow River Basin during 2000-2023: Spatiotemporal variations and potential impacting factors - Rong Zhu; Youyan Jiang; Sipika Sundriyal; Bo Wang; Yulan Zhang (Atmospheric Environment, 2026)

Evaluation of protein and metabolic engineering strategies on (−)-α-bisabolol production by Escherichia coli - Jiayi Ma; Rong Fang; Xiaoyuan Yue; Hui Jiang; Qixuan Kong; Tiankuo Jiang; Jiale Yu; Chang Zhou; Yuanyuan Xia; Wei Shen; Haili Liu; Yaqin Shen; et al. (Systems Microbiology and Biomanufacturing, 2026)

Characteristics of excavation unloading deformation and reinforcement force estimation method considering stress compensation for differential weathering slopes in valley areas - Ling-fa Jiang; Shang-rong Gao; Xiao-tao Yin; Hui Qin (Bulletin of Engineering Geology and the Environment, 2026)

Influence of winter-fallow management strategies on the stability of soil organic matter in a typical rice paddy region of southwestern China - Meihui Tian; Sihua Zhu; Bin Liu; Jitao Lv; Shanyi Tian; Rong Huang; Xiaohong Zuo; Meichun Duan; Yongguang Yin; Tao Jiang; Dingyong Wang; Xinping Chen (Agriculture, Ecosystems & Environment, 2026)

Bridging cortical intentions: brain–computer interfaces for spinal cord injury recovery - Xuantao Hu; Jiale He; Na Li; Jian Mo; Senyu Yao; Yubao Lu; Mudan Huang; Pan Jiang; Mao Pang; Lei He; Jin Gong; Zifeng Liu; et al. (Science Bulletin, 2026)

Immunogenicity and safety of an Escherichia coli-produced 9-valent HPV vaccine in adolescents aged 9 to 17 compared with young women - Yulin Jing; Xiaowen Hu; Li Zhang; Jiangyahui Wang; Fei Yang; Rong Wang; Ying Jiang; Lingling Nie; Zhongqiang Jin; Xuecheng Liu; Sihai Li; Chao Du; et al. (Science Bulletin, 2026)

Two new menthane monoterpene derivatives isolated from Hypericum monogynum - Yan-Rong Zeng; Hong-Jin Ban; Jing-Yi Yin; Zhan Feng; Ya-Nan Li; Yan Liu; Xiao-Jiang Hao; Chun-Mao Yuan (Phytochemistry Letters, 2026)

Rapid retreat of the East Asian summer monsoon at the end of the Holocene humid period accelerated the transition from broadleaf to pine forest landscapes in northern China - Linjing Liu; Xin Mao; Lei Song; Xingqi Liu; Dejun Wan; Gaolei Jiang; Jingsong Yang; Hongmei Zhao; Chengmin Wang; Hua Zhao; Rong Ma (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The transcription factor SlPLATZ22 negatively regulates salinity tolerance in tomato plants - Xin Li; Fei Ding; Niannian Zhou; Zheng Chen; Jiahui Huang; Fangling Jiang; Carl-Otto Ottosen; Ron Mittler; Rong Zhou; Zhen Wu (Journal of Plant Physiology, 2026)

Buffering failure of the ratio of secondary to primary phases: Risk overestimation of soil heavy metals under alkaline conditions - Yingdong Wu; Zixin Zeng; Rong Teng; Junwei Yang; Jiang Yu; Hui Sun; Siwei Deng; Pengxinyue Huang; Jie Luo; Yi Wu; Xuetao Zhao (Journal of Hazardous Materials, 2026)

Effects of iron, manganese, and aluminum oxides on soil cadmium distribution coefficient: A multi-scale analysis based on explainable machine learning - Yingdong Wu; Jiayi Li; Rong Teng; Zixin Zeng; Jiang Yu; Xuetao Zhao; Yiwen Li; Pengxinyue Huang; Siwei Deng (Journal of Hazardous Materials, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

Comparative study of pristine and desulfurized gypsum ball-milled biochar for saline-alkali soil amelioration in combination with sulfur - Lijuan Sun; Yafei Sun; Lina Zou; Limiao Ye; Shiyan Yang; Qin Qin; Jun Wang; Xiaofeng Jiang; Naling Bai; Zhenglong Wang; Ping Lu; Rong Zhang; et al. (Journal of Environmental Chemical Engineering, 2026)

High hydrostatic pressure mitigates light-induced degradation of volatiles and phenolic compounds in seabuckthorn pear blends - Jianfeng Wang; Yonghao Chen; Rong Zhang; Shengbin Ma; Faisal Eudes Sam; Jixin Li; Yang Bi; Yumei Jiang (Food Chemistry, 2026)

Using integrated multi-omics and molecular docking to decode stone epiphytic culture as a strategy for enhancing flavonoids and bioactivity in Dendrobium officinale leaves for functional tea development - Jing Li; Rong Zhou; Yingyue Hou; Yichang Chen; Shaohao Xie; Jinyu Wu; Jiang Chen; Hongbin Hou; Guangying Du (Food Bioscience, 2026)

Research progress on the structure of edible fungi polysaccharides and their anti-obesity mechanisms via the regulation of intestinal microbiota and metabolites - Xin Wei; Weiya Rong; Liyang Jin; Limin Zhang; Daoqin Ren; Yue Jiang; Jinling Cao; Shaojun Yun; Feier Cheng; Wenfei Zhao; Yong Li; Mingchang Chang; et al. (Food Bioscience, 2026)

Ultrasound-assisted dry-heating glycosylation with xylooligosaccharides: Enhancing the structural and functional properties of pig skin collagen - Shengqi Jiang; Lin Li; Hongqing Nie; Jincheng Han; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Huiyu Han; Jing Xi; Wu Ding (Food Hydrocolloids, 2026)

Multi-objective optimization of rice production and environmental sustainability under climate change in the Yangtze River Delta: A DNDC-random forest framework approach - Shuoshuo Liang; Ping He; Qingnan Chu; Wentian He; Ruochen Li; Xinpeng Xu; Rong Jiang; Shuang Liu; Linkui Cao; Zhimin Sha (Field Crops Research, 2026)

Towards sustainable potato production in China: Optimizing nitrogen and water management with 5R strategies - Zhaolong Pan; Rong Jiang; Daijia Fan; Daping Song; Hanyou Xie; Xiya Wang; Wei Zhou; Ping He; Wentian He (European Journal of Agronomy, 2026)

Hierarchical Cu Ni micro-nanocone arrays as stable lithium metal hosts - Qiulong Tang; Guang Jiang; Jilu Zhao; Qingyu Dong; Jingshu Wang; Haiyang Zhang; Jianxin Ou; Xuechun Wang; Rong Huang; Hui Shao; Jun Ge; Xuefeng Gao; et al. (Chemical Engineering Journal, 2026)

Metal-free C H functionalization unlocks multifunctional luminescent PEGs for biomedical imaging and therapy - Weiping Liu; Qinyue Guo; Lifang Ma; Ruohan Li; Jiajia Ren; Haixia Jiang; Gang Wang; Rong Zeng (Chemical Engineering Journal, 2026)

Design of green multifunctional mesoporous nanosheets for trace biomarker detection, AI-enhanced pollutant discrimination, and synergistic catalytic degradation - Zamar Daka; Yuqi Zhang; Jieli Li; Liying Yao; Chenxi Luo; Meng Tian; Xi Xia; Guowen Qin; Rong Jiang; Min Song; Shunli Ji (Chemical Engineering Journal, 2026)

Calcium-mediated modulation of ultra-low-ester pectin-gluten interactions: subunit-level mechanisms revealed using HMW-GS deletion lines and molecular dynamics simulations - Rong-ran Zhang; Ping-ping Zhang; Tian Lv; Bo Wang; Zhe Liu; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Carbohydrate Polymers, 2026)

Stage-specific ion release from dual-crosslinked alginate/boron-doped bioactive glass hydrogel accelerates infected wound healing - Fuqiang Song; Linyuan Jiang; Anqi Ye; Rong Huang; Anwen Lai; Longyang Xu; Wei Shen; Junjun Li; Jiayan Hui; Andi Suo; Yanzhi Xiong; Xiaoyu Dong; et al. (Carbohydrate Polymers, 2026)

Urbanisation magnifies the effect of innovative behaviour on avian persistence and extinction risk - Lingxue Li; Jiaxuan Jiang; Xinyu Guo; Xinyu Zhang; Yanfang Li; Ke Rong (Biological Conservation, 2026)

Biomechanical Evaluation of Different Minimally Invasive Internal Fixation Methods for the Anterior and Posterior Rings in Tile C Pelvic Fractures - Xin Rao; Daixiang Jiang; Hui Lu; Yangxing Luo; Dingxi Liu; Yuanfeng Liu; Lei yin; Rong Liu (Journal of Medical and Biological Engineering, 2026)

Development and validation of a copolymerized thiol-silica based DGT technique for the assessment of bioavailable As(Ⅲ) speciation - Yue Zeng; Zhennan Liu; Yajie Jiang; Yunqin Li; Wei Yu; Rong Yu; Xiang Xu; Meiling Xiao (Environmental Geochemistry and Health, 2026)

Biochar and manure amendments mitigate chemical-fertilizer-induce negative effects on soil microbiomes, with implications for crop productivity gain - Pan Jiang; Hao Huang; Jinmeng Hu; Linlin Wang; Yuping Zhang; Xiangmin Rong; Jianwei Peng; Gongwen Luo (Applied Soil Ecology, 2026)

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

Molten NaOH-KOH assisted thermo-chemical detoxification of waste salt containing hazardous organics - Hongping He; Yong Cheng; Linhua Jiang; Youcai Zhao; Dongjie Niu; Xunchang Fei; Rong Zhang; Shijin Dai (Process Safety and Environmental Protection, 2026)

Morphological characteristics, molecular identification, and phylogenetic analysis of the four Leonurus species used for the treatment of gynecological diseases - Qing Du; Ziyi Rong; Yanjuan Guan; Chang Zhang; Liqiang Wang; Xiangyang Zhou; Chuanbei Jiang; Haidong Gao; Bin Wang; Haimei Chen; Chang Liu (Plant Gene, 2026)

Interfacial adsorption mechanism of xanthan gum pre-assembled with calcium ions as an efficient depressant for Cu-S flotation separation under low-alkaline - Hulin Gao; Jian Liu; Jiamei Hao; Meiguang Jiang; Xu Bai; Da Li; Rong Huang (Minerals Engineering, 2026)

Mechanism study on ultrasonication combined with soybean 11S globulin to improve the quality and flavor compounds of low-salt lamb meat gel - Rong Bai; Hongqing Nie; Jing Xi; Aitmagambetova Madina; Lin Li; Huiyu Han; Shengqi Jiang; Gege Wang; Wu Ding (Meat Science, 2026)

Synergistic transformation of alkylbisphenols (BPA, BPE, and BPF) mediated by ammonia-oxidizing bacteria and heterotrophic bacteria in nitrifying activated sludge - Hang Xu; Wenhui Zhang; Sicheng Zhu; Bingyu Shen; Xinyu Li; Bingqi Jiang; Lianhong Wang; Philippe F.X. Corvini; Max M. Häggblom; Rong Ji (Journal of Hazardous Materials, 2026)

Mechanism of synergistic astringency enhancement by organic acids in model wine: Insights from organic acid-phenols-protein triadic interaction - Yan Liu; Xiang Jie Jiang; Shi qing Zhang; Qing hao Zhao; Yue fan Zhao; Wan Rong Zhao; Shi Yi Peng; Guo Rong Du; Xiao Yuan; Peng Tao Zhao; Xiao Yu Wang (Food Chemistry, 2026)

Modification of sheep hoof collagen by electron beam irradiation: Mechanistic insights into its effects on physicochemical and functional properties based on molecular structural analyses - Huiyu Han; Jing Xi; Jiangtao Yu; Lin Li; Shengqi Jiang; Rong Bai; Xiang Ye; Siying Wang; Hongqing Nie; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Irradiation co-succinylation modification of caprine casein: Impact on physicochemical properties, molecular structure, and functional properties - Jing Xi; Huiyu Han; Rong Bai; Madina Aitmagambetova; Siying Wang; Shengqi Jiang; Hongqing Nie; Lin Li; Xiang Ye; Gege Wang; Wu Ding (Food Hydrocolloids, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

One stone, two birds: Preparation of nutritionally fortified and easy-to-swallow 3D printed pea protein gel based on high internal phase emulsions - Wei Liang; Junhong Xie; Qiannan Zhao; Chenghong Jiang; Xiaofeng Zhan; Mingrong Chen; Lu Zhang; Chuan Li; Jianhua Rong; Yang Hu (Food Hydrocolloids, 2026)

Construction of mineral-carbon nanosheet using waste activated sludge and bentonite for boosting dye adsorption - Rong Guo; Lina Wang; Di Zhang; Chuanhui Jiang; Guoxiu Qian; Yonggang Wu (Environmental Research, 2026)

Monodisperse lutetium-177-labeled poly(lactic acid) microspheres for radioembolization therapy of hepatocellular carcinoma - Qing-Rong Jiang; Ping He; Ling-Yun Guo; Qi-Yi Mo; Xing-Long Zhou; Wei Wang; Zhuang Liu; Rui Xie; Da-Wei Pan; Wen-Jie Zhang; Xiao-Jie Ju; Liang-Yin Chu (Chemical Engineering Journal, 2026)

A self-limiting swelling hydrogel with covalent anchoring for durable vascular embolization - Rong Wang; Rui Zhang; Siying Li; Yuxuan Huang; Jingying Yan; Yuqing Gu; Qi Jiang; Xuri Chen; Jinchun Ye; Qianqian Zhu; Xianzhu Zhang; Xiaozhao Wang; et al. (Chemical Engineering Journal, 2026)

Cold adaptation strategies of anammox bacteria and the bottleneck of nitrogen removal performance in autotrophic nitrogen removal process treating digested swine wastewater - Ya-hui Wang; Fang-yu Huang; Long-xing Jiang; Rong You; Yun-hong Zhang; Liang-wei Deng; Wen-guo Wang; Lan Wang (Chemical Engineering Journal, 2026)

Study of the machine learning emission inversion method of the CUACE model on the basis of fused Fengyun observations - Tao Niu; Congwu Huang; Yiliang Jiang; Qi Jiang; Bihui Zhang; Hongli Liu; Rong Li; Yuzhan Xie; Tijian Wang (Atmospheric Pollution Research, 2026)

Longifolene and β-ionone promote astaxanthin accumulation in Microcystis aeruginosa by serving signaling function - Lexin Huang; Fei Jiang; Shanshan Song; Xinyuan Zhao; Zhehan Yang; Junjie Ma; Haozhe Xu; Rong Hu; Tianyu Huang; Zhijie Chen; Huiying Fu; Zhaojiang Zuo (Algal Research, 2026)

Mechanisms of failure and permeability evolution in gas-bearing strata under tunnel-induced stress paths - Jiafeng Tan; Deyi Jiang; Rong Liu; Yi He; Jinyang Fan; Jianyu Liang; Cheng Qian; Hanlin He; Hong Zheng (Transportation Geotechnics, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Short-term black carbon exposure impairs mental health and DNA methylation signatures of mitochondrial carrier genes - Shuzhen Liu; Yaxin Luo; Jiansheng Cai; Yuting Wang; Jiahui Rong; Xiaoting Mo; Yujian Liang; Zeyan Ye; Xu Tang; Siyuan Niu; Tiantian Zhang; Lei Luo; et al. (Journal of Hazardous Materials, 2026)

Optical diagnostic study on the combustion and soot formation process of nanobubble diesel - Han Wang; Liang Guo; Wanchen Sun; Yuying Yan; Hao Zhang; Miao Yang; Mengqi Jiang; Degang Li; Rong Xuan; Junfeng Zhang; Kaiqi Yang (Fuel, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Ion−dipole−induced high stability of acidic DESs for efficient extractive and oxidative desulfurization - Dongao Zhu; Jie Yin; Siyi Han; Rong Zhang; Chunyan Dai; Jing He; Hongping Li; Wenshuai Zhu; Huaming Li; Wei Jiang (Chemical Engineering Journal, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Deep Learning-Based Object Detection of Electromagnetic Interference Echoes from Weather Radar Data - Man Yao; Muyun Du; Rong Yu; Xianling Jiang; Hedi Ma; Guoying Tang; Peiting Liu (Journal of Meteorological Research, 2026)

Can digital economy facilitate carbon reductions in China - Wanting Jiang; Guoyong Liu; Yijie Wang; Rong Kong (Environment, Development and Sustainability, 2026)

Juvenile-Onset Cerebrotendinous Xanthomatosis with Novel Compound Heterozygous CYP27A1 Mutations: Case Series and Literature Review - Kefang Du; Chunrong Wang; Linlin Wan; Zhao Chen; Hongyu Yuan; Qian Jiang; Xiao Dong; Daji Chen; Riwei Ouyang; Xiafei Long; Xiaokang Wu; Xinying Xiao; et al. (The Cerebellum, 2026)

Beyond electrostatic interaction: Ball milling-induced dominance of pore filling and π-π stacking for methylene blue adsorption on tobacco stem derived activated carbon - Dong-Can Lv; Meng-Ru Chen; Mei-Rong Song; Guang-Ce Jiang; Zhi-Min Wang (Journal of Water Process Engineering, 2026)

pH-dependent overestimation of heavy metals mobility risk in soils: Implications for soil quality assessment - Yingdong Wu; Zixin Zeng; Rong Teng; Jiang Yu; Guanlin Guo; Pengxinyue Huang; Zhi Huang; Siwei Deng (Journal of Hazardous Materials, 2026)

Risk assessment and environmental influencing factors of urinary polycyclic aromatic hydrocarbons metabolites in pregnant women in Zunyi, China - Jing Yang; Jing Jiang; Linfei Wu; Pei Xu; Nian Wu; Rui Yu; Yanling Xiao; Xingting Zheng; Rong Zeng; Yuanzhong Zhou; Yan Xie; Xubo Shen (Journal of Environmental Sciences, 2026)

Cd(II) adsorption at a biofilm–mineral interface: Capacity penalty, site masking, and behavior shifts induced by bacterial coating - Liangwei Han; Huijie Zheng; Zihao Ding; Yinjie Kang; Jiang Yu; Yineng Lu; Rong Tan; Zhuanjun Zhao (Chemical Engineering Journal, 2026)

Recrystallization and orientation competition via hot extrusion in n-type Bi2Te3 alloys for advanced power generator - Tao Xiong; Hailong He; Ge Tian; Yi Wu; Youqun Li; Chunping Niu; Feng Jiang; Chenhao Ren; Mingzhe Rong (Chemical Engineering Journal, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Phytochemistry, pharmacology and bibliometrics insight of the genus Callicarpa L.: an extensive review encompassing the years from approximately 2010 to 2024 - Wang Jiang; Si-Rong Huang; Wen-Jie Ma; Yi-Qiu Yi; Ping Li; Zhong-Hui Ma; Zhi-Wei Su (Phytochemistry Reviews, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Curcumin Ameliorates Depressive-like Behaviors by Modulating mGluR2/PGC-1α-Mediated Glutamatergic Homeostasis and Mitochondrial Function - Liping Xu; Deyun Jiang; Lujing Yang; Conghua Ji; Rong Bai; Yirun Xu; Tian-Rui Xu (Molecular Neurobiology, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Kinetic model reveals microbial-mediated hydrogen consumption and abiotic mineral reactions jointly control hydrogen depletion during geological storage - Dongfang Ke; Weiqiang Feng; Peng Liao; Rong Li; Ruina Xu; Yu-Min Chou; Peixue Jiang (Applied Geochemistry, 2026)

SREBP2 confers ferroptosis resistance by targeting GPX4 in colorectal cancer - Huage Zhong; Ruiqi Chen; Tianyu Chen; Min Lin; Siqi Wen; Man Zhang; Dejun Liu; Junfeng Yu; Jinchi Chen; Bei Yi; Rong Liang; Wei Jiang; et al. (Apoptosis, 2026)

Reliability analysis of dam based on vine Copula function - Qi Wu; Feng Yu; Bowen Li; Henglin Xiao; Peizhen Su; Maiyong Jiang; Guan Rong (European Journal of Environmental and Civil Engineering, 2025)

A review of data-driven key technologies for intelligent citrus systems - Wengang Li; Aoting Wan; Jing Li; Kelin Chen; Zifei Ma; Qinghua Li; Rong Jiang; Juan Yang; Tong Li (Computers and Electronics in Agriculture, 2025)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Bioactive constituents from Salacia obovatilimba as potential in vitro hSGLT2 inhibitors - Zhi-Yong Jiang; Lin Chen; Hong-Xi Xie; Jun-Jie Hao; Rong Chen; Chun-Qiu Huang; Hong-Lei Zhang; Ai-Xue Zuo (Phytochemistry, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Effects of soil labile carbon fractions and microbes on GHG emissions from flooding to drying in paddy fields - Yi Xiao; Rong Huang; Zongjin Zhang; Vanessa N.L. Wong; Xingyu Li; Xiaoyan Tang; Youlin Luo; Yingjie Wu; Jiang Liu; Shiwei Li; Changquan Wang; Bing Li (Journal of Environmental Sciences, 2025)

Unravelling the migration of bioactive and volatile compounds coupled with water sublimation from grapes to recovered water during dynamic freeze-drying - Mengru Li; Wei Zhang; Yuan Huang; Xiaoying Zhang; Wuernisha Kadeer; Leihong Mao; Yuqian Jiang; Rong Tsao; Yao Tang (Food Chemistry, 2025)

Enhanced Type-II singlet oxygen production via 3D topological porphyrin-based covalent organic framework - Xiaoning Zhan; Yucheng Jin; Houhe Pan; Baoqiu Yu; Rong Jiang; Boce Cui; Dongdong Qi; Siyu Liu; Yanjun Zhao; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Exploring the protein complexity of lipid droplets in DHA-producing Schizochytrium sp. and potential applications of lipid droplet-associated proteins in lipid production - Chu-Bin Lin; Jun-Jie Wu; Xue-Qiang Chen; Jia-Xue Zhao; Shan Jiang; Xue-Rong Zhou; Peng-Yang Liu; Feng-Hong Huang; Xia Wan (Chemical Engineering Journal, 2025)

An injectable and programmable hydrogen delivery system for modulation tendon tissue in tendon-bone interface microenvironment - Tao Yuan; Fei Jin; Lili Qian; Xiaojiang Yang; Xin Yu; Zhongyang Lv; Ziying Sun; Shiwen Shen; Hong Qian; Jia Meng; Hui Jiang; Wenshuang Sun; et al. (Chemical Engineering Journal, 2025)

Preparation of activated carbon from waste mushroom sticks via a two-step supercritical carbon dioxide pyrolysis and KOH activation method - Ke Tian; Xiaoran Rong; Jiangang Jiang; Qingang Xiong; Hui Jin (Waste Disposal & Sustainable Energy, 2025)

Microbially carbon transformation in response to the partially replacement of chemical fertilizer by straw returning aggravates soil acidification in red paddy soil - Yingxi Chen; Changkuan Zhou; Xiangmin Rong; Xinyu Liu; Lian Zhang; Guoliang Jiang; Rusheng Xiao; Yongliang Han (Journal of Soils and Sediments, 2025)

Acute systemic inflammation induces region-specific morphological remodeling of astrocytes and microglia concurrent with depression-like behavior - An-Qi Zhang; Meng-Meng Zhang; Ling-Jie Li; Mei-Xue Yuan; Rong-Yu Liu; Peng Chen; Chen-Wei Wang; Yu Wang; Jiang-Ning Zhou; Qing-Hong Shan; Xin-Ya Qin (Histochemistry and Cell Biology, 2025)

Spatiotemporal transition of resting-state brain networks associates with human cognitive abilities - Lv Zhou; Zhengchang Jiang; Zhao Chang; Rong Wang; Ying Wu (Cognitive Neurodynamics, 2025)

The pore-network-continuum modeling of two-phase flow properties for multiscale digital rocks - Bowen Shi; Jianqi Rong; Han Jiang; Bo Guo; S. Majid Hassanizadeh; Chao-Zhong Qin (Advances in Water Resources, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Non-extractable residues as the dominant fate of bisphenol A (BPA) in oxic paddy soil: formation and characterization - Yanan Zhao; Yongfeng Wang; Xiaoran Guo; Siqi Cao; Bingqi Jiang; Yao Yao; Xiaolong Liang; Rong Ji (Science of The Total Environment, 2025)

Sesquiterpenoids from Achillea setacea Waldst. & Kit. with anti-inflammatory activity by inhibiting the glycolytic pathway - Gui-Min Xue; Jin-Feng Xue; Jiang-Jing Duan; Hui-Ying Yang; Yan-Jun Sun; Hui Chen; Yan-Le Zhi; Zhi-Qiang Zhang; Rao Li; Dong-Rong Zhu; Guo-Sheng Li (Phytochemistry, 2025)

Screening of proteins interacting with PirA and PirB from Vibrio parahaemolyticus causing acute hepatopancreatic necrosis disease in Pacific white shrimp Litopenaeus vannamei - Li Jiang; Na An; Rong Fan; Dianli Zhao; Mengqiang Wang (Fish & Shellfish Immunology, 2025)

How root exudates of vegetation contribute to prevention and control of soil disintegration on Chinese Loess Plateau: A case study of Robinia pseudoacacia L. - Tao Xiao; Ping Li; Rong Jiang; Sai K. Vanapalli; Xiangcheng Han; Hui Zhai; Yiyi Yang; Qi Gu; Jiading Wang (Engineering Geology, 2025)

Preparation of porous hydrophilic ion sieves for lithium recovery from highly alkaline lithium precipitation mother liquor and low-lithium raw brine: Batch and continuous operation - Gao Deng; Rong Jiang; Faman Tang; Zhaofei Hou; Yongjun Feng (Desalination, 2025)

Direct oxidation of trace methane to formaldehyde under ambient conditions by piezo-photocatalytic synergy - Qiyu Zhang; Li Rong; Yue Jiang; Zhiping Zhu; Xiaochang Lin; Yongzhen Ding; Hongmin Dong; Dezhao Liu (Chemical Engineering Journal, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Oxygen vacancy-conductivity synergy enables efficient oxygen catalytic activity for reversible solid oxide cells - Changyang Liu; Rong Xuan Jiang; Liuzhen Bian; Chaoyi Wang; Lei Xing; Dongsheng Ren; Hewu Wang; Shengli An; Minggao Ouyang (Chemical Engineering Journal, 2025)

A fungal polysaccharide from Trametes orientalis: Structural elucidation and multifaceted antitumor mechanisms via metastasis, angiogenesis, and immunomodulation - Wenrui He; Haojing Jiang; Mingming Rong; Xinxing Li; Jing Xu; Yuanqiang Guo (Carbohydrate Polymers, 2025)

The potential role of hydrogen sulfide-autophagy axis in diseases - Ti Chu; Yan-Wen Wang; Lei Cao; Xue-Li Wang; Yong-Qi Fan; Yu-Hang Chen; Yi Zhang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Journal of Physiology and Biochemistry, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Chemically gated ion transport in two-dimensional heterogeneous membranes with ultrahigh metal ion selectivity - Gang Yuan; Junjie Fang; Yukun Sun; Jiaojiao Ma; Hao Wang; Wanqi Zhou; Yu Jiang; Chongyang Yang; Zhihua Zhou; Rong Hu; Mingyang Xia; Konstantin S. Novoselov; et al. (Science Bulletin, 2025)

The late Eocene pine seed cones from Mangkang Basin, southeastern Xizang (Tibet) and their biogeographic significance - Xuan-Rong Yao; Yi Gao; Ren-Dan Yang; Jiang-Bo Meng; Shu-Feng Li; Tao Su (Palaeoworld, 2025)

Tracing toxic pollutants in coastal urban atmosphere: A case study on the particle-size distribution, sources, and health risks of PCDD/Fs, PCBs, PAHs, and substituted PAHs - Zhangpeng Guo; Shuai Sun; Rong Cao; Nan Jiang; Naibing Liang; Zichen Wang; Jiasen Guo; Minzhen Li; Xing Liu; Ningbo Geng; Jiping Chen (Journal of Hazardous Materials, 2025)

Airborne bioaerosol transmission in hospital waiting corridor: Characteristic, exposure risk and evaluation of prevention strategies - Zhijian Liu; Duo Cai; Chenxing Hu; Lei Jiang; Yongxin Wang; Lina Hu; Rui Rong; Shiyue Li; Jingwei Liu; Jiajun Feng (Journal of Hazardous Materials, 2025)

Identification, occurrence, and toxicity prediction of alkylphenolic disinfection by-products in disinfected combined sewer overflows - Yayun Zhang; Pin Wang; Rong Xiao; Wenyuan Yang; Fang Yuan Jiang; Wen Hai Chu (Journal of Hazardous Materials, 2025)

The application of manure and straw is beneficial for improving the content and stability of DOM in paddy soil - Qinghua Zhou; Jiayue Zhou; Weiliang Xiong; Shiwei Li; Ouping Deng; Yi Xiao; Xingyu Li; Bing Li; Changquan Wang; Xuesong Gao; Genchuan Bai; Jiang Liu; et al. (Journal of Environmental Management, 2025)

Dual regulation of surface electronegativity and interlayer structural feature in fluorinated COFs for efficient gold recovery - Xiaoning Zhan; Yucheng Jin; Bin Han; Dongdong Qi; Chunli Li; Rong Jiang; Xiaonan Pang; Guoqing Xu; Mingyue Wang; Qi Zhang; Jianzhuang Jiang (Chemical Engineering Journal, 2025)

GO-enhanced polyurethane phase change materials with triple dynamic bonds: Oxime-urethane, coordination and hydrogen bonds - Rong Huang; Fu Zhao; Yongsheng Li; Zhuoni Jiang; Fangfang He; Kai Zhang; Zhengguo Chen; Guansong He; Wenbin Yang (Chemical Engineering Journal, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Targeting cuproptosis in liver cancer: Molecular mechanisms and therapeutic implications - Yun-Fei Zhou; Yi-Wen Zhu; Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Yan-Ge Li; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Regulatory mechanism of microplastics on arsenic bioavailability in a subtropical estuary, China - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Rong Yu; Wei Yu; Binxin Wu; Meiling Xiao (Science of The Total Environment, 2025)

Ten eudesmane sesquiterpenoids from Dobinea delavayi and their antimalarial and lipid-lowering activities - Wei Chen; Li-Tian Dong; Pei-Mi He; Wei-Juan Zu; Yi-Ling Yang; Rong Liu; Bei Jiang; Chao-Jiang Xiao (Phytochemistry, 2025)

The effect of DHN melanin synthesis mediated by trihydroxynaphthalene reductase Aabrm2 on the cell membrane, cell wall integrity, and toxin synthesis of Alternaria alternata - Rong Li; Li Li; Xiwang Wang; Qianqian Jiang; Yuanping Nan; Yang Bi; Yongcai Li (Physiological and Molecular Plant Pathology, 2025)

Personnel exposure studies to multi-source diffusion of bioaerosols under biosafety laboratory - Level 2 plus operating conditions - Yongxin Wang; Zhijian Liu; Chuan Jiang; Lei Jiang; Jingwei Liu; Rui Rong; Shiyue Li; Wentao Wu; Guoqing Cao (Journal of Hazardous Materials, 2025)

Multifunctional microbial inoculation regulates compost product microbiomes, with implications for improving crop health and yield - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Xingxiang Deng; Guixian Xie; Gongwen Luo (Journal of Cleaner Production, 2025)

Deciphering the preservative effects of protamine from Xinjiang Coregonus peled on grass carp (Ctenopharyngodon idellus) fillets during refrigerated storage: a perspective from the microbiome - Rong Zhang; Yanan Gao; Xiaoji Fan; Song Zhu; Tingzhang Wang; Lili Gao; Xueqin Zhao; Zhuang Ma; Yiling Fan; Dan Jiang; Shuyan Liu (International Journal of Food Microbiology, 2025)

Different impacts of temperature and precipitation on vegetation net primary production of global marsh wetlands - Jiaqi Zhang; Meiling Zhao; Rong Ma; Mingming Feng; Chen Ding; Liyuan Wu; Xianguo Lu; Xiangjin Shen; Ming Jiang (Global and Planetary Change, 2025)

Structural-taste relationship and molecular interaction mechanisms of umami peptides from Meretrix lyrata hydrolysates: Insights into key binding sites and thermodynamic drivers - Chunyong Song; Rong Jiang; Mingtang Tan; Zhongqin Chen; Huina Zheng; Jialong Gao; Haisheng Lin; Wenhong Cao (Food Bioscience, 2025)

Network-based insights into the temperature-driven mechanisms of bacterial self-assembly in the solid-state fermented vinegar seed Pei - Mingchao Jiang; Yiyang Zou; Yuhang Wang; Yunsong Yang; Dong Han; Wenting Li; Yuanyuan Zhu; Yuqin Wang; Zhen Yu; Ke Wang; Chunchi Rong; Peng Liu; et al. (Food Bioscience, 2025)

Nanoplastics under the charge effects: Unveiling the potential threats to amphibian (Rana nigromaculata) growth, intestinal damage and microbial ecology - Peng Fang; Shuzi Ye; Zidie Luo; Rong Guo; Yan Jiang; Lemei Liu; Siwen Li; Fang Xiao (Environmental Pollution, 2025)

The application of hyper dose drug derived cell vehicles theory in gouty arthritis: Phoenix nirvana — A non-living mesenchymal stem cell drug delivery system - Chengran Wang; Xinao Rong; Tianqi Dong; Jinqi Zhu; Fangruyue Wang; Pu Shao; Jinlan Jiang (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Bio-organic fertilizer application improves cucumber growth, disease resistance, and soil fertility by regulating rhizosphere microbiomes - Junyan Yang; Xin Liu; Xiangmin Rong; Pan Jiang; Yixiang Xia; Guixian Xie; Gongwen Luo; Xiaoyuan Yan (Plant and Soil, 2025)

Distinct mechanisms of marine heatwave formation in offshore waters of China - Zhibo Chen; Ying Wang; Jiaqi Wang; Rong-Hua Zhang; Yifan Jiang; Yu Qi; Xinchi Yu (Journal of Oceanology and Limnology, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Extending the Mutational Spectrum of SYNE1 Ataxia in Chinese Patients - Xin Huang; Zhao Chen; Qian Jiang; Panyan Liu; Yiqing Gong; Lijing Lei; Jia Chen; Chunrong Wang; Linlin Wan; Lang He; Linliu Peng; Rong Qiu; et al. (The Cerebellum, 2025)

Spatio-temporal variations in the supply and demand of ecosystem services with multi-scenario prediction in Guangzhou City, China - Jun Wu; Zhi-Yun Jiang; Yan-Yu Xu; Lin Lin; Rong Guo; Yi-Jia Wang (Environmental Science and Pollution Research, 2025)

Anaerobic membrane distillation bioreactors for saline organic wastewater treatment: Impacts of salt accumulation on methanogenesis and microbial community - Zhimeng Yang; Linjiang Jiang; Haiyang Yang; Haiqing Chang; Yuxuan Wan; Huarong Yu; Hongwei Rong; Fangshu Qu (Water Research, 2025)

Corrigendum to “Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression” [Toxicology 514 (2025) 154129] - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Effects of Penthorum chinense pursh and gallic acid on embryonic and cardiac development in zebrafish (Danio rerio) - Kehui Liu; Hui Jiang; Rong Ji; Yuanyuan Ma; Rui Zhang; Binbin Song; Ying Han (Toxicology in Vitro, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Anchoring nanoscale zero-valent iron within bacterial cellulose particles for boosting efficient adsorption of Co(II) and Sr(II) from seawater: Dual system and varying adsorption mechanisms - Rong Cheng; Yating Chen; Mi Kang; Peiwen Jiang; Lei Shi; Jianzhong Zheng; Xiang Zheng; Jianlong Wang (Journal of Environmental Sciences, 2025)

Transcriptome analysis reveals the molecular mechanisms of the 8-day infection cycle of Ecytonucleospora hepatopenaei in Litopenaeus vannamei and the host's molecular responses - Yan Rong; Yi Qiao; Tingyue Liu; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Xianping Fan; Hui Shen (Fungal Biology, 2025)

Facile fabrication of ethyl cellulose/gelatin fibers incorporated with copper-based metal-organic frameworks as humidity-triggered release of carvacrol for blueberry preservation - Jing Xie; Xingyu Rong; Xiaoqian Jiang; Yuping Zhao; Tianhua Ding; Jing Yan; Suqing Li; Wen Qin; Mingrui Chen; Yaowen Liu (Food Chemistry, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Quantitative modeling of substrate velocity effects on deposition efficiency and precursor consumption in spatial ALD - Geng Ma; Zhaojie Wang; Yuan Gao; Zoushuang Li; Xuewei Jiang; Yanwei Wen; Bin Shan; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

The antibacterial activity, action mechanisms and prospects of Baicalein as an antibacterial adjuvant - Liuqing Mu; Kaiyan Xie; Rong Chen; Jiang Cao; Yang Shu; Xuebin Huang (World Journal of Microbiology and Biotechnology, 2025)

Electroacupuncture may alleviate diabetic neuropathic pain by inhibiting the microglia P2X4R and neuroinflammation - Si-ying Qu; Han-zhi Wang; Qun-qi Hu; Yi-qi Ma; Yu-rong Kang; Li-qian Ma; Xiang Li; Lu-hang Chen; Bo-yu Liu; Xiao-mei Shao; Bo-yi Liu; Jun-ying Du; et al. (Purinergic Signalling, 2025)

Improvement of soil quality, microbial community structure and function with the application of microbial agent in continuous cropping of Pinellia ternata - Rong Deng; Yuan Zhao; Lin Chen; Siqi Li; Linwei Jiang; Xiaomei Wang; Tao Yang; Xueping Tian; Jun Huang (Plant and Soil, 2025)

Histopathological Insights into Demyelination and Remyelination After Spinal Cord Injury in Non-human Primates - Junhao Liu; Zucheng Huang; Kinon Chen; Rong Li; Zhiping Huang; Junyu Lin; Hui Jiang; Jie Liu; Qingan Zhu (Neuroscience Bulletin, 2025)

AHNAK2 Regulates NF-κB/MMP-9 Signaling to Promote Pancreatic Cancer Progression - Na-na Tang; Rong-bo Xu; Bo Jiang; Hai-ling Zhang; Xiao-song Wang; Dan-dan Chen; Ji-jun Zhu (Biochemical Genetics, 2025)

Direct recovery of high-purity uranium from fluoride-containing nuclear wastewater via extraction materials with ensemble Lewis sites and a tandem electrochemical device - Guo Li; Yan Liu; Chi Jiao; Zhengyu Jiang; Juan Zhang; Tao Chen; Tao Lin; Rong He; Wenkun Zhu; Xiangke Wang (Water Research, 2025)

An environmentally friendly strategy for the preparation of high-purity quartz using combined collector reverse flotation coupled with acid-leaching technology - Ke Rong; Dawei Luo; Jiabao Deng; Shengnan Sun; Shasha Song; Bowen Jiang; Zhongxiang Yu; Ke Zhao (Minerals Engineering, 2025)

Does greater molecular diversity in soil organic matter imply greater persistence: Insights from molecular and multi-property analyses in Western China - Shanyi Tian; Sihua Zhu; Joeri Kaal; Jitao Lv; Rong Huang; Tongwen Zhang; Xiaolei Su; Yongguang Yin; Tao Jiang; Dingyong Wang (Geochimica et Cosmochimica Acta, 2025)

Insights from structural characterization for understanding isolation and impact of roasting on allergenic potential of sesame Oleosins - Dakai Di; Rong Zhang; Huimei Li; Min Qiu; Suwei Jiang; Shuizhong Luo; Hanju Sun; Shudong He (Food Chemistry, 2025)

Oligosaccharide glycosylation of pigskin collagen: Impact on molecular structure, physicochemical properties, and gel functionality - Shengqi Jiang; Huiyu Han; Madina Aitmagambetova; Aidana Rakhimova; Lin Li; Rong Bai; Chunjie Yang; Xiang Ye; Siying Wang; Jing Xi; Wu Ding (Food Hydrocolloids, 2025)

Machine learning-driven molecular generation for accelerated screening of high-performance flame retardants in epoxy resin composites - Zhongwei Chen; Chunlei He; Kai Wang; Feng Rong; Long Xiang; Ziwei Zuo; Changliang Wang; Xinyuan Yang; Yong Guo; Juncheng Jiang; Yuan Yu (Chemical Engineering Journal, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Fine mapping and functional validation reveal two incomplete dominant genes controlling photoperiod-sensitive flowering in Gossypium hirsutum - Langjing Hua; Chao Xu; Xiao Liu; Zhicheng Wang; Tengyu Li; Yuefen Cao; Xin Hu; Yurong Jiang; Junkang Rong (Theoretical and Applied Genetics, 2025)

(±)-Involucrasin D, a pair of enantiomeric bisflavonoid from the roots of Shuteria involucrata and its anti-inflammatory activity - Xiaoying Zhou; Qiong Jin; Bingruo Zhang; Lisha Wei; Lue Bao; Xiaoyun Jiang; Rong Duan; Lu Liu; Zhuya Yang (Natural Product Research, 2025)

Integrated transcriptomic and metabolomic analysis reveals molecular mechanisms of infectious myonecrosis virus (IMNV) pathogenesis in Litopenaeus vannamei muscle tissue - Yan Rong; Yi Qiao; Xiaohui Cao; Ge Jiang; Jie Cheng; Huiwen Jiang; Hui Shen (Aquaculture, 2025)

Active spermatogenesis in YY supermale common carp makes it suitable for potential control of this invasive species - Kuangxin Chen; Yi Rong; Yuanqi Guo; Mouyan Jiang; Yulai Wei; Xishuang Shan; Yongming Li; Yanlong Song; Ji Chen; Binbin Tao; Wei Hu (Aquaculture, 2025)

Bioinformatics identification of shared signaling pathways and core targets linking Benzo[a]pyrene exposure to HCC progression - Yong-Le Li; Rong He; Meng Tang; Jing-Yi Lan; Guo-Yang Liu; Li-He Jiang (Toxicology, 2025)

Megastigmane glycosides from Heterosmilax yunnanensis and their neuroprotective activity - Rong-Rong Du; Wen-Jie Qin; Xiu-Mei Duan; Xu Zhang; Ya-Nan Yang; Jian-Shuang Jiang; Xiang Yuan; Pei-Cheng Zhang (Phytochemistry, 2025)

Assessment of fate of respiratory droplets and effectiveness of different air cleaners during outpatient consultation - Haiyang Liu; Zhijian Liu; Guangpeng Yao; Zhijian Dong; Chuan Jiang; Jingwei Liu; Rui Rong; Junzhou He; Chenxing Hu; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2025)

Climate warming will alter the impact of microplastics on the bioavailability of arsenic in a subtropical estuary - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Wei Yu; Rong Yu (Journal of Hazardous Materials, 2025)

High-efficiency immobilization of soil available cadmium by chicken manure and its derivatives: Roles of chemical and microbial property - Zhi-Wen Hu; Feng Jiang; Fei Huang; Heng Wang; Qian-Jun Liu; Xiao Zhou; Ming-Zhi Huang; Peng Wang; Rong-Bo Xiao (Journal of Environmental Chemical Engineering, 2025)

Mechanistic study of ultrasound synergy with soybean 11S globulin to improve myofibrillar protein gel properties in low-salt lamb: molecular conformation and water migration - Rong Bai; Jing Xi; Huiyu Han; Rakhimova Aidana; Aitmagambetova Madina; Shengqi Jiang; Xiang Ye; Chunjie Yang; Siying Wang; Wu Ding (Food Research International, 2025)

Nectar characteristics and pollination ecology of Camellia perpetua in South China - Hai-du Jiang; Dan-juan Zeng; Hui-zhen Qin; Li-hui Peng; Yi-shan Yang; Zong-you Chen; Rong Zou; Jian-min Tang; Yun-sheng Jiang; Zhong-chen Xiong; Xiao Wei; Sheng-feng Chai (Flora, 2025)

Improved rainfall infiltration model for probabilistic slope stability assessment considering transition layers and spatial variability - Shui-Hua Jiang; Zhi-Rong Yuan; Ze Zhou Wang; Xian Liu (Engineering Geology, 2025)

Ultra-stable all-solid-state lithium metal batteries facilitated by in-situ LiF-rich single-ion conductor composite polymer electrolytes - Jiaze Li; Rong Yang; Aoyi Jiang; Qianwei Zhang; Xin Dong; Hongyu Shang; Yinglin Yan; Yunhua Xu; Jou-Hyeon Ahn (Chemical Engineering Journal, 2025)

Regulating the gradient water distribution via hydro-philic/phobic compositional design in ionogels for stable zinc ion batteries - Rong Zheng; Nan Jiang; Baojun Wang; Chengyi Hou; Qinghong Zhang; Hongzhi Wang; Yaogang Li; Kerui Li (Chemical Engineering Journal, 2025)

SIRT3 deficiency reduces PFKFB3-driven T-cell glycolysis and promotes arthritic inflammation - Ting-Ting Wang; Taotao Han; Xinyue Xiao; Dan Guo; Xin Sun; Yudong Liu; Lidan Zhao; Haojie Xu; Rong Li; Lingjuan Jiang; Bo Zhang; Beidi Chen; et al. (Science China Life Sciences, 2025)

Integrating straw return and tillage practices to enhance soil organic carbon sequestration in wheat–maize rotation systems in the North China Plain - Hua Han; Daijia Fan; Shuxia Liu; Rong Jiang; Daping Song; Guoyuan Zou; Ping He; Minyu Wang; Wentian He (Agriculture, Ecosystems & Environment, 2025)

Wind Direction and Strength Determine the Genetic Structure of an Insect‐Pollinated Plant Across Heterogeneous Landscape - Jun‐Yin Deng; Rong‐Hua Fu; Stephen G. Compton; Chuan Yuan; Matthew M. Kling; Xiao‐Yong Chen; Yao‐Bin Song; Kai Jiang; Mei Liu; Jaco M. Greeff; Yan Chen (Journal of Biogeography, 2025)
Aim Dispersal of plant propagules and their genes is crucial for plant responses to landscape heterogeneities, yet the mechanisms behind this dispersal remain unclear. Ficus species depend on wind‐borne fig wasps for pollination, but research on airflow effects on Ficus genetic structure has produced conflicting results. Our study aims to clarify the role of wind in shaping the genetic structure of such plants with wind‐borne insect pollinators by examining how geomorphological complexity interacts with air movements to influence genetic structures. Location Southwest China: Sichuan, Yunnan, Guangxi and Guizhou provinces. Taxon Ficus tikoua Bur., Ficus , Moraceae. Methods We sampled 56 F. tikoua sites across southwest China, characterised by high geomorphologic complexity. River basins and predominant winds were visualised across the sampled regions. Wind connectivity between sampled sites during the main pollination season was modelled based on hourly daily wind data. The maternal and biparental genetic structure of sites were reconstructed using chloroplast DNA (cpDNA) and nuclear SSR (nuSSR) markers. Links between genetic structure, location, and wind parameters were estimated by Mantel or partial Mantel tests. Results The plant's maternal genetic structure was defined by river systems, with two distinct cpDNA groups located in the Yangtze and Pearl River basins, respectively. The boundaries for nuclear variation were less clearly delimited geographically. Sites with mixtures of nuSSR groups were concentrated where prevailing winds arrived from several directions. Stronger between‐site air flows increased nuSSR geneflow and genetic similarities, while populations receiving more wind flow were also more genetically variable. Main Conclusions Our study reveals how plant gene dispersal reflects air and water movements that in turn respond to geomorphologic complexity, thereby directly demonstrating the effects of wind on gene flow of plants with wind‐borne insect pollinators. Wind data matching pollinator flight times and large sample sizes are crucial for testing wind effects.

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Evaluating soil dissolved organic matter as a proxy for soil organic matter properties across diverse ecosystems - Shanyi Tian; Songbo Yao; Sihua Zhu; Peng Li; Tongwen Zhang; Xiaolei Su; Rong Huang; Yongguang Yin; Jitao Lv; Tao Jiang; Dingyong Wang (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Exogenous melatonin enhancing the accumulation of flavonoids and carotenoids in wolfberry fruit at cold storage - Rong Jiang; Zhiqiang Wang; Yixin Jia; A. Biao; Yuan Zong; Chao Yang; Minglin Li; Hongjiao Wang; Yuling Zhao; Ying Wang; Shaohua Zeng (Food Research International, 2025)

Microbial interactions between Lactoplantibacillus plantarum and Rhodotorula mucilaginosa in the fermented fish juice system - Xiayin Ma; Bingqian Zhou; Lina Jiang; Mingyang Xie; Zhixing Rong; Shixian Yin; Faxiang Wang; Yongle Liu; Xianghong Li (Food Research International, 2025)

Preparation of sodium alginate/pectin/cellulose nanofibrils films containing black soybean seed coat anthocyanins for monitoring goat meat freshness - Siying Wang; Xinyue Han; Ya Chen; Yikai Shao; Jiaqing Song; Chunjie Yang; Shengqi Jiang; Rong Bai; Xiang Ye; Wu Ding (Food Control, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Hydraulic and mechanical response of loess to different chemical components in root exudates - Rong Li; Chaobo Zhang; Siyu Zhang; Ruihan Jiang; Jing Jiang (Plant and Soil, 2025)

Stem trichome polarity development in Gossypium hirsutum: insights into GhPRP gene regulation - Huanying Deng; Longen Ma; Li Yu; Yanhao Zhao; Yurong Jiang; Junkang Rong (Plant Cell Reports, 2025)

AaRgs2 regulates growth and virulence of Alternaria alternata by maintaining reactive oxygen species (ROS) balance - Yuanping Nan; Miao Zhang; Yangyang Yang; Rong Li; Qianqian Jiang; Xuexue Wang; Yongcai Li; Yang Bi (Postharvest Biology and Technology, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

The process, mechanisms and regulation of Cu electrolyte sulfidation based on spectroscopy direct determination towards high-purity Cu recovery - Guangbin Zhu; Linhua Jiang; Ning Duan; Yong Liu; Liye Bao; Rong Zhang; Xiaolu Sun; Shaoshuai Sheng; Hao Jin (Journal of Environmental Chemical Engineering, 2025)

Petrogenesis and age of granitoids associated with the Dongshan Cu polymetallic deposit, East Kunlun Orogenic Belt, NW China: Implications for the Middle to Late Triassic tectonic setting and Cu polymetallic mineralization - Yi-Chen Chen; Zheng-Jiang Ding; Jun-Wei Bo; Shi-Jiong Han; Ting-Ting Li; Pan Ji; Rong-Qiang Guo (Geochemistry, 2025)

Micromotors assisted in vivo dopamine polymerization for anti-tumor therapy - Dailing Du; Ye Feng; Miaomiao Ding; Jinghui Rong; Bin Chen; Chao Gao; Tingting Jiang; Yingfeng Tu; Fei Peng (Chemical Engineering Journal, 2025)

Double-network hydrogel dressing regulated by cationic polymer-grafted bacterial cellulose for promote rapid healing of infected wounds - Xuhui Rong; Guoliang Gao; Jiang Lou; Xiaolei Wang; Wenjia Han (Carbohydrate Polymers, 2025)

The diverse sleep structure of mid-day nap in college students - Qin Xiao; Xueqi Sun; Guoxin Zeng; Xin Luo; Qian Jiang; Rong Ren; Xiangdong Tang; Chao He; Zhian Hu; Fenlan Luo; Jie Yan (Sleep and Biological Rhythms, 2025)

Single-cell atlas profiling revealed cellular characteristics and dynamic changes after PD-1 blockade therapy of brain metastases from laryngeal squamous cell carcinoma - Yunzhi Zou; Hao Duan; Zekun Deng; Rong Xiang; Jixiang Zhao; Zhenhua Zhang; Wanming Hu; Yuanzhong Yang; Zeming Yan; Shujuan Wen; Zexian Liu; Gao Zhang; et al. (Molecular and Cellular Biochemistry, 2025)
Brain metastasis (BM) in laryngeal squamous cell carcinoma (LSCC) is uncommon but prognosis is poor. Anti-PD-1 immunotherapy benefits some advanced LSCC cases, yet its efficiency is limited by tumor complexity. We analyzed paired metastatic tumor samples from before and after immunotherapy using single-cell RNA sequencing (scRNA-seq), along with a primary LSCC dataset and bulk RNA sequencing. This identified changes post-immunotherapy and revealed differences in single-cell transcriptomes among LSCC, primBM, and neoBM. Our findings show that anti-PD-1 treatment suppresses metastasis-promoting pathways like VEGF and EMT in cancer cells, and alters immune cell functions. Notably, it upregulates T cell activation, leading to CD8 T cell exhaustion from excess heat shock proteins, notably HSPA8. However, CD8 T cell cytotoxic functions improve post-treatment. In myeloid cells, anti-PD-1 therapy enhances antigen presentation and promotes a proinflammatory shift post-metastasis. Additionally, NUPR1 is linked to BM in LSCC, and NEAT1 is a potential metastatic cancer cell cycle participant. Our study provides insights into cancer heterogeneity and the impact of PD-1 immunotherapy on metastasis, aiding precise diagnosis and prognosis.

Understanding the increased maize productivity of intercropping systems from interactive scenarios of plant roots and arbuscular mycorrhizal fungi - Yizhe Wang; Pan Jiang; Chaolin Liao; Jiangchi Fei; Yuping Zhang; Rong Xiangmin; Jianwei Peng; Gongwen Luo (Agriculture, Ecosystems & Environment, 2025)

Recent advances in the role of gasotransmitters in necroptosis - Meng-Yuan Hao; Hong-Jie Li; Hang-Shen Han; Ti Chu; Yan-Wen Wang; Wei-Rong Si; Qi-Ying Jiang; Dong-Dong Wu (Apoptosis, 2025)

Observed seasonal evolution and origins of the western Yellow Sea Cold Water Mass - Chuanjie Wei; Xiaohui Tang; Kai Ge; Anqi Xu; Yuanlong Li; Yong Jiang; Zengrui Rong; Fei Yu (Frontiers in Marine Science, 2025)
The Yellow Sea Cold Water Mass (YSCWM) is one of the most prominent hydrological features of the Yellow Sea. As a low-temperature, nutrient-rich subsurface water mass, the YSCWM fundamentally regulates biogeochemical cycles, functions of marine ecosystems, and fishery resources of the YS. In boreal summer, the YSCWM shows a robust triple-core structure, in which the western component, dubbed the “western YSCWM”, is revisited in this study. Through analyzing in-situ observational data collected by research cruises of the Institute of Oceanology, Chinese Academy of Sciences (IOCAS) and Lagrangian tracing experiments based on a high-resolution ocean model, we provide a thorough investigation for seasonal evolution and origins of the western YSCWM. In-situ observations during 2006-2007 and 2014-2015 suggest that the western YSCWM bears a tight connection to the colder coastal waters near the Shandong Peninsula and achieves the coldest temperature in summer. Analysis of model simulations confirms that the cooling of the western YSCWM in spring and summer is caused mainly by southward cold-water transport of the Shandong Coastal Current (SDCC) from the Shandong coasts and the northern Yellow Sea. We also reveal a contribution of the Subei Shoal water via the Subei Coastal Current (SCC) in summer, which plays a critical role in the quick vanishing of the western YSCMW in early autumn. These findings contribute to our understanding of the formation, seasonal evolution, and heat budgets of the YSCWM.

Enhancing aquaculture sustainability: the role of rice floating beds in improving Gibel carp growth and microbiota composition - Yangyang Jiang; Yongxu Sun; Beibei Zhou; Chaozhen Rong; Shouyun Ruan; Minglin Wu (Frontiers in Marine Science, 2025)
To explore the effects of rice floating beds on fish growth and intestinal microbiota, the present study compared the fish growth performance and the microbial diversity, microbial construction, and microbial composition of water and Gibel carp ( Carassius auratus gibelio ) intestine in rice floating beds ponds and normal ponds. The results revealed that the Gibel carp raised in rice floating beds ponds exhibited significantly greater body length, body weight, and weight gain rates than those in normal ponds. Microbial community analysis showed enhanced richness and diversity in water and intestine of the rice floating beds group. Furthermore, the assembly processes of these microbial communities were predominantly influenced by stochastic mechanisms in rice floating beds ponds. The bacterial phyla associated with nutrient cycling, such as Cyanobacteria, Chloroflexi, and Ignavibacteria, were significantly assembled in the rice floating beds group. Overall, these results highlight the potential of rice floating bed systems as a sustainable aquaculture technique, fostering improved growth performance and microbial diversity, which are critical for the health of cultured fish.

Recombinant probiotic Escherichia coli delivers the polymeric protein of swine influenza virus for protection - Jin-Mei Sun; Wen-Qiang Zhang; Yan-Jin Li; Tian-Kui Guo; Rong-Rong Zhang; Yong-Lei Yang; Ying Zhao; Ling-Jiao Yu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; et al. (Veterinary Microbiology, 2025)

Regulation of ethanol production from anaerobic fermentation of food waste using aromatic alcohol-based quorum-sensing molecules - Rong Ma; Zhuoshen Huang; Yi Jiang; Anqi Zhao; Guangwei Yu; Changquan Lin; Langping Zhu; Xiaozhi Zhang; Xiaotian Li; Chunming Wang (Journal of Environmental Management, 2025)

A novel directed enzymolysis strategy for the preparation of umami peptides in Stropharia rugosoannulata and its mechanism of taste perception - Daoyou Chen; Mingli Rong; Shuting Tang; Chuanxi Zhang; Hao Wei; Zhaoting Yuan; Tingwei Miao; Hucheng Song; Haiming Jiang; Yan Yang; Lujia Zhang (Food Chemistry, 2025)

Toxic aldehydes in fried foods: Formation, analysis, and reduction strategies - Xing-yang Guo; Liang-yu Cheng; Chao Chang; Xiao-ming Jiang; Pan Gao; Wu Zhong; Chuan-rong Hu; Dong-ping He; Jiao-jiao Yin (Food Control, 2025)

Auxin regulates leaf senescence and nitrogen assimilation to promote grain filling in maize (Zea mays L.) - Na Jiang; Peng Wang; Zhiqi Yang; Changwei Li; Yixiang Xia; Xiangmin Rong; Yongliang Han; Lan Yang (Field Crops Research, 2025)

Trade-offs between agronomic and environmental benefits: A comparison of inhibitors with controlled release fertilizers in global maize systems - Minyu Wang; Ping He; Daijia Fan; Rong Jiang; Guoyuan Zou; Daping Song; Libo Zhang; Yu Zhang; Wentian He (Field Crops Research, 2025)

Signal-amplification strategy and advances in electrochemistry-based CRISPR/Cas12 biosensing - Liuyu Pan; Weiwei Jiang; Fei Deng; Rong Fang; Shaoyue Jin; Danting Yang (Chemical Engineering Journal, 2025)

Identification of Potential Causal Genes for Neurodegenerative Diseases by Mitochondria-Related Genome-Wide Mendelian Randomization - Kang-Fu Yin; Ting Chen; Xiao-Jing Gu; Zheng Jiang; Wei-Ming Su; Qing-Qing Duan; Xiang-Jin Wen; Bei Cao; Ju-Rong Li; Li-Yi Chi; Yong-Ping Chen (Molecular Neurobiology, 2025)

Comammox and ammonia-oxidizing archaea dominated the nitrification under different nitrogen fertilizer levels in acid purple soil of Southwest China - Jun Xie; Jianguo Jiang; Jie Lu; Wencai Dai; Huarong Guo; Yuanxue Chen; Rong Huang; Zifang Wang; Ming Gao (Applied Soil Ecology, 2025)

The effect of soil depth on stoichiometry was greater than that of elevation in Abies georgei var. Smithii forest in Southeastern Tibet, China - Si-jie Zhu; Jiang-rong Li; Bo Zhang; Fang-wei Fu; Liang-na Guo (Acta Oecologica, 2025)

Research on Optimization Method for Irregular Seismic Acquisition in Curved Wave Domain Based on Simulated Annealing - Hu Zhao; Meng-yang Chen; Yu-dong Ni; Rong-rong Zhao; Fu-hao Jiang; Wei Chen; Jing-yun Dai (Applied Geophysics, 2025)

3D Computational Modeling of Blast Transmission through the Fluid-Filled Cochlea and Hair Cells - John J. Bradshaw; Marcus A. Brown; Yijie Jiang; Rong Z. Gan (Annals of Biomedical Engineering, 2025)

Climate change enhances greening while human activities accelerate degradation in northern China's grasslands - Feifei Cao; Leizhen Liu; Yuping Rong; Nan Jiang; Lin Zhao; Qian Zhang; Zhitao Wu; Wenhui Zhao; Sheng Li (Science of The Total Environment, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Distributions of DMS and DMSP and the influences of planktonic community assemblages in the Bohai Sea and Yellow Sea - Juan Yu; Yu Jiang; Rong Chen; Jing-Guang Lai; Hou-Jin Zhou; Yong-Qiao Chen; Qi Zhang; Gui-Peng Yang (Marine Environmental Research, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

Severity and risk to inhalation of pathogen-laden aerosol in large public spaces: Insights from fangcang shelter hospitals under multi-location release - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jingwei Liu (Journal of Hazardous Materials, 2025)

Mechanistic insights into efficient phosphorus adsorption and recovery from water using functional ZnO/ZnFe-LDHs alginate hydrogels - Shilong Cao; Xiangling Zhang; Shuqin Xie; Chen Wang; Jing Bai; Xuhao Li; Rong Zhang; Xinlu Xiao; Jiezhou Hu; Xiaoxia Jiang (Journal of Environmental Chemical Engineering, 2025)

Enhanced carrier separation and photocatalytic degradation of oxytetracycline via S-scheme MIL-53(Fe)/FeOCl heterojunction composites with peroxydisulfate activation - Wei Dong; Chunyan Du; Yin Zhang; Jiao Cao; Jingyi Jiang; Lu Zhou; Guanlong Yu; Yulv Zou; Huaiyuan Peng; Rong Yan; Yu Yang (Journal of Environmental Chemical Engineering, 2025)

Lipid peroxidation inhibition by icaritin and its glycosides as a strategy to combat iron overload-induced osteoporosis in zebrafish - Chang-Yu Yan; Xiao-Yuan Gu; Shuo-Yan Tan; Ao-Yu Mei; Jiang-Hao Mao; Yi Dai; Jie Niu; Wei-Xi Li; Hiroshi Kurihara; Yi-Fang Li; Rong-Rong He (Food Research International, 2025)

Contribution of phosphorylation modification by sodium tripolyphosphate to the functional properties of hollow zein nanoparticles - Sheng-qi Rao; Cao-chen Jia; Lin Du; Wei-biao Zhou; Wen-xuan Hu; Yi Jiang; Zhi-rong Wang; Zhen-quan Yang (Food Research International, 2025)

Scalable deposition of SnO2 ETL via SALD for large-area inverted perovskite solar modules - Xuewei Jiang; Bin Shan; Geng Ma; Yan Xu; Xing Yang; Wenbin Zhou; Chenhui Li; Fan Yang; Rong Chen (Chemical Engineering Journal, 2025)

Advancing treatment strategies against MRSA: unveiling the potency of tubuloside A in targeting sortase A and mitigating pathogenicity - Yangming Xu; Yanhe Luan; Rong Wang; Zhengjie Su; Li Wang; Yinghui Liu; Guangzhi Jiang; Bingmei Wang (World Journal of Microbiology and Biotechnology, 2025)

LINC01224 promotes the Warburg effect in gastric cancer by activating the miR-486-5p/PI3K axis - Yuling Bin; Minji Liu; Rong He; Pingfei Tang; Weiming Qu; Dajun Wu; Lin Tan; Qian Wang; Peng Jiang; Hongsai Hu (In Vitro Cellular & Developmental Biology - Animal, 2025)

The role of bile acid in regulating head-kidney, spleen and skin immune function of on-growing grass carp (Ctenopharyngodon idella) - Fei Zhao; Xiu-Rong Peng; Wei-Dan Jiang; Pei Wu; Yang Liu; Lin Feng; Xiao-Qiu Zhou (Aquaculture, 2025)

Susceptibility and risk to inhalation of pathogen-laden aerosol in large public spaces: Evidence from Fangcang Shelter Hospitals under multiple ventilation rates - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Junzhou He; Shiyue Li; Rui Rong; Zhenyu Liang; Jiaqi Chu; Jingwei Liu (Sustainable Cities and Society, 2025)

Migration and risk assessment of heavy metals from swine manure in an organic fertilizer - soil - ryegrass - rex rabbit system: Based on field trials - Xiaoxia Hao; Kai Liu; Li Zhu; Li Rong; Dongmei Jiang; Lin Bai (Science of The Total Environment, 2025)

CSF multi-omics of intracerebral hemorrhage from onset to reperfusion underscores lipid metabolism in functional outcome - Yibin Jiang; Sin Man Lam; Shuixian Zhang; Huan Miao; Yong Zhou; Qian Zhang; Tengyuan Zhou; Hui Feng; Ning Ding; Haomiao Wang; Ran Luo; Yi Yin; et al. (Science Bulletin, 2025)

Impacts of lake basin topography predicted by long short-term memory on difference of lake area and water resource evolution - Ruirui Jiang; Rong Ma; Lefan Zhao; Wanggang Dong; Ruiqing Zhou (Journal of Cleaner Production, 2025)

Selective recovery of Cu and efficient removal of As(V) from Cu electrolyte via four-stage continuous coupled sulfide precipitation - Hao Jin; Linhua Jiang; Ning Duan; Jinyu Wang; Xiaolu Sun; Yong Liu; Guangbin Zhu; Liye Bao; Rong Zhang (Journal of Cleaner Production, 2025)

Mechanism of extracellular electron transport and reactive oxygen mediated Sb(III) oxidation by Klebsiella aerogenes HC10 - Qun Rong; Chaolan Zhang; Caiyuan Ling; Dingtian Lu; Linjiang Jiang (Journal of Environmental Sciences, 2025)

Nickel-iron layered double hydroxide and CoMoO4 composites supported on nickel foam as efficient bifunctional catalyst for water electrolysis - Xin Xiao; Rao Ma; Ke Jiang; Lushan Ma; Qiyao Wang; Shuang Meng; Tong Yang; Zhuo Qiu; Rong Hu; Long Huang (Fuel, 2025)

Dynamic estimation of the soil environmental carrying capacity for Benzo(a)pyrene in an industrial city, China: Insight from both duration and rate of regional emission - Xinyue Chen; Meie Wang; Tian Xie; Rong Jiang; Weiping Chen (Environmental Pollution, 2025)

MOFs meets wood: Renewable, self-supporting carbon-based composites for electromagnetic interference shielding with heat-resistant and electrothermal management - Yujun Rong; Xin Zhou; Shaohua Jiang; Wenkai Zhu; Hanwei Wang; Baokang Dang; Qingfeng Sun; Xiaofan Ma (Chemical Engineering Journal, 2025)

Physical hydrogel evaporators with uniformly dispersed hydrophobic components for freshwater and electricity cogeneration - Lichao Jiang; Honglang Lu; Wei Cui; Rong Ran (Chemical Engineering Journal, 2025)

High/Low-Index Faceted PdNi Alloy Nanocrystals as Highly Active and Stable Electrocatalyst for Oxygen Reduction - Jun Zhang; Xinlan Xu; Lanyu Luo; Tiantian Peng; Boyu Liu; Lingying Jiang; Meng Jin; Rong Wang; Huan Yi; Weimin Wu; Shi-Yu Lu (Chemical Engineering Journal, 2025)

Enriching bottom acceptors for high-performance inkjet-printed organic solar cells - Xingze Chen; Lifeng Sang; Yuanyuan Jiang; Yiyu Chen; Qing Zhang; Rong Huang; Fengqi Guo; Guanghao Lu; Xiaozhang Zhu; Qi Chen; Chang-Qi Ma; Qun Luo (Chemical Engineering Journal, 2025)

Characterization of Gut Microbiota in Rats and Rhesus Monkeys After Methamphetamine Self-administration - Li He; Jia-hui Zhou; Huan Li; Wen-lei Zhang; Tie-qiao Liu; Hai-feng Jiang; Rong-wei Zhai; Xiao-jie Zhang (Molecular Neurobiology, 2025)

Observations of daytime topside ionospheric irregularities in the afternoon equatorial ionosphere - Chunhua Jiang; Lehui Wei; Tatsuhiro Yokoyama; Rong Tian; Tongxin Liu; Guobin Yang (Advances in Space Research, 2025)

Leaf Photosynthetic and Respiratory Thermal Acclimation in Terrestrial Plants in Response to Warming: A Global Synthesis - Ting Wu; David T. Tissue; Mingkai Jiang; Martijn Slot; Kristine Y. Crous; Junfeng Yuan; Juxiu Liu; Shaofei Jin; Chenxi Wu; Yan Deng; Chao Huang; Fuxi Shi; et al. (Global Change Biology, 2025)
Leaf photosynthesis and respiration are two of the largest carbon fluxes between the atmosphere and biosphere. Although experiments examining the warming effects on photosynthetic and respiratory thermal acclimation have been widely conducted, the sensitivity of various ecosystem and vegetation types to warming remains uncertain. Here we conducted a meta‐analysis on experimental observations of thermal acclimation worldwide. We found that the optimum temperature for photosynthetic rate ( T opt ) and the maximum rate of carboxylation of Rubisco ( T opt V) in tropical forest plants increased by 0.51°C and 2.12°C per 1°C of warming, respectively. Similarly, T opt and the optimum temperature for maximum electron transport rate for RuBP regeneration ( T opt J) in temperate forest plants increased by 0.91°C and 0.15°C per 1°C of warming, respectively. However, reduced photosynthetic rates at optimum temperature ( A opt ) were observed in tropical forest (17.2%) and grassland (16.5%) plants, indicating that they exhibited limited photosynthetic thermal acclimation to warming. Warming reduced respiration rate ( R 25 ) in boreal forest plants by 6.2%, suggesting that respiration can acclimate to warming. Photosynthesis and respiration of broadleaved deciduous trees may adapt to warming, as indicated by higher A opt (7.5%) and T opt (1.08°C per 1°C of warming), but lower R 25 (7.7%). We found limited photosynthetic thermal acclimation in needleleaved evergreen trees (−14.1%) and herbs (−16.3%), both associated with reduced A opt . Respiration of needleleaved deciduous trees acclimated to warming (reduced R 25 and temperature sensitivity of respiration (Q 10 )); however, broadleaved evergreen trees did not acclimate (increased R 25 ). Plants in grasslands and herbaceous species displayed the weakest photosynthetic acclimation to warming, primarily due to the significant reductions in A opt . Our global synthesis provides a comprehensive analysis of the divergent effects of warming on thermal acclimation across ecosystem and vegetation types, and provides a framework for modeling responses of vegetation carbon cycling to warming.

Associations between volatile organic compounds exposure and multiple oxidative damage biomarkers: Method development, human exposure, and application for e-waste pollution prediction - Jia-Rong Wang; Hong-Xuan Kuang; Ye Liu; Xin-Yi Li; Tian-Hong Chen; Xiao-Hui Zhu; Rui-Fang Fan; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Occurrence and fate of atmospheric short/medium chain chlorinated paraffins: Size distribution and inhalation exposure - Naibing Liang; Rong Cao; Nan Jiang; Chengcheng Shi; Zhangpeng Guo; Yuan Gao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Deciphering the evolution and biogeography of ant-ferns Lecanopteris s.s - Li-Ju Jiang; Jing Zhao; Jia-Guan Wang; Sven Landrein; Ji-Pu Shi; Chuan-Jie Huang; Miao Luo; Xin-Mao Zhou; Hong-Bin Niu; Zhao-Rong He (Molecular Phylogenetics and Evolution, 2024)

Experimental study of interception effect by submerged dam on microplastics - Jianhao Jiang; Lulu He; Junping Liu; Xu Liu; Junbao Huang; Li Rong (Journal of Hazardous Materials, 2024)

Unveiling the release mechanism of potentially toxic elements from Pb/Zn smelter contaminated soils under the coupled effects of freeze–thaw and acidification: Insights from mineralogical analysis - Da–Mao Xu; Bai–Hong An; Shao–Jun Jiang; Dong–Sheng Dai; Ze–Lin Xu; Lai Zhou; Xue–Qiang Zhu; Hong Yang; Rong–Bing Fu (Journal of Hazardous Materials, 2024)

Dominant drivers of vegetation changes in key ecological barrier of northeastern Tibetan Plateau since 2000: Human impacts or natural forces? - Fuguang Zhang; Biao Zeng; Puguang Wang; Rong Jiang; Qing Zhang (Journal of Environmental Management, 2024)

Analytical model of three-dimensional concentric ellipsoidal soil arching in geosynthetic-reinforced pile-supported embankments - Rong Sun; Xin Jiang; Lei Zhang; Canyang Cui; Zhengxian Li; Yanjun Qiu (Geotextiles and Geomembranes, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Effects of different fermentation modes on tea leaves: Revealing the metabolites modification by quasi-targeted metabolomics - Xin Fang; Rong Xue; Jingyi Xiao; Qian Pu; Yufei Wang; Yuan Yuan; Bin Liu; Mengyuan Sui; Guangxian Jiang; Rida Niaz; Yongping Sun; Ziming Yu; et al. (Food Bioscience, 2024)

Immunoprotective effect of recombinant Lactobacillus plantarum expressing largemouth bass virus MCP on largemouth bass - Yong-Lei Yang; Rong-Rong Zhang; Jing-Yi Pang; Jun-Hong Xing; Tian-Kui Guo; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Yan-Long Jiang; Jian-Zhong Wang; Xin Cao; Nan Wang; et al. (Fish & Shellfish Immunology, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Sensing host and environmental cues by fungal GPCRs - Cong Jiang; Aliang Xia; Daiying Xu; Jin-Rong Xu (Current Opinion in Plant Biology, 2024)

Engineered multienzyme-mimicking 2D bismuthene catalytic nanotriggers enable cascade enzyodynamic-boosted and synergistic GPX4/FSP1-mediated ferroptosis amplification for cancer radiosensitization - Yipengchen Yin; Li Zhu; Tiaoyan Jiang; Rong Chai; Ya Zhang; Tianyu Li; Kai Wang; Sheng Wang; Qin Zhang (Chemical Engineering Journal, 2024)

Characterization and expression analysis of the MADS-box gene AGL8 in cotton: insights into gene function differentiation in plant growth and stress resistance - Zhicheng Wang; Yuefen Cao; Yurong Jiang; Mingquan Ding; Junkang Rong (Molecular Biology Reports, 2024)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Synthesis of β-ionone from xylose and lignocellulosic hydrolysate in genetically engineered oleaginous yeast Yarrowia lipolytica - Jiang‑Ting Shi; Ying-Ying Wu; Rong-Zi Sun; Qiang Hua; Liu‑Jing Wei (Biotechnology Letters, 2024)

Neutralizing chimeric heavy-chain antibody targeting the L-HN domain of Clostridium botulinum neurotoxin type F - Kaiyue Sun; Shudi Luo; Yujia Jiang; Jiazheng Guo; Xi Wang; Kexuan Cheng; Changyan Xu; Yixiao Zhang; Chen Gao; Jiansheng Lu; Peng Du; Yunzhou Yu; et al. (Archives of Toxicology, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Microplastics and copper impacts on feeding, oxidative stress, antioxidant enzyme activity, and dimethylated sulfur compounds production in Manila clam Ruditapes philippinarum - Yu Jiang; Juan Yu; Ji-Yuan Tian; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song; Rong Chen (Marine Pollution Bulletin, 2024)

PM2.5 constituents associated with mortality and kidney failure in childhood-onset lupus nephritis: A 19-year cohort study - Guohua He; Yaqi Wang; Cheng Cheng; Jianhui Guo; Zhilang Lin; Ziyun Liang; Bei Jin; Liyuan Tao; Liping Rong; Lizhi Chen; Tianxin Lin; Yining Hua; et al. (Science of The Total Environment, 2024)

First report of bacterial blotch disease caused by Burkholderia gladioli in Grifola frondosa from China - Zhihan Shen; Na Rong; Jiaqi Wang; Donghua Jiang; Zhenzhen Zhang (Physiological and Molecular Plant Pathology, 2024)

Transfer from ciliate to zebrafish: Unveiling mechanisms and combined effects of microplastics and heavy metals - Yan Zhang; Caixia Wang; Ruiqi Jia; Hongan Long; Jianfeng Zhou; Gaojingwen Sun; YunLong Wang; Zhaoji Zhang; Xiaozhi Rong; Yong Jiang (Journal of Hazardous Materials, 2024)

Surrogate-model-based low-carbon optimization method for tolerance allocation of mechanical components under bidirectional constraints - Rong Duan; Zhigang Jiang; Jie Yang; Xin Zeng; Hua Zhang; Xianfeng Ai (Journal of Cleaner Production, 2024)

Dynamic changes in the aroma profiles and volatiles of Enshi Yulu tea throughout its industrial processing - Guangxian Jiang; Rong Xue; Jun Xiang; Yufei Wang; Bin Liu; Yuan Yuan; Qian Pu; Xin Fang; Xingming Hu; Xiaoying Liu; Youyi Huang (Food Chemistry, 2024)

Perfluorooctane sulfonate (PFOS) and benzo[a]pyrene (BaP) synergistically induce neurotoxicity in C6 rat glioma cells via the activation of neurotransmitter and Cyp1a1-mediated steroid hormone synthesis pathways - Yu-Shun Lu; Ju Chen; Xiao-Rong He; Shang-Lin Yang; Bing-Jie Ma; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Food and Chemical Toxicology, 2024)

Size-dependent influences of nano- and micro-plastics exposure on feeding, antioxidant systems, and organic sulfur compounds in ciliate Uronema marinum - Long-Fei Liu; Juan Yu; Yu Jiang; Qian Liu; Yong Jiang; Rong Chen; Gui-Peng Yang; Xin-Ran Song (Environmental Pollution, 2024)

Impacts of nano- and micro-plastics exposure on zooplankton grazing, bacterial communities, and dimethylated sulfur compounds production in the microcosms - Yu Jiang; Juan Yu; Rong Chen; Su Wang; Gui-Peng Yang; Long-Fei Liu; Xin-Ran Song (Environmental Pollution, 2024)

Diversified competitive sulfuration behaviors of concomitant heavy metal ions on copper recovery from copper smelting waste acid - Xiaolu Sun; Linhua Jiang; Ning Duan; Liye Bao; Hao Jin; Guangbin Zhu; Yong Liu; Zhiguo Song; Rong Zhang (Chemical Engineering Journal, 2024)

Heterostructured GCN Nanosheets/ZnO nanoflowers for enhanced TMO loading: From high-performance three electrode systems to printed flexible asymmetric supercapacitors - Xuhao Wang; Fenglin Sun; Fuhao Jiang; Binxuan Diao; Rong Wang; Hongjiang Li; Sang Woo Joo; Rong Li; Se Hyun Kim; Chenhao Cong; Xinlin Li (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Gene expression profiles and metabolic pathways responsible for male sterility in cybrid pummelo - Rong Wang; Yang-Cao Shi; Bo Zhang; Wan-Rong Liu; Feng-Quan Tan; Fang Lu; Nan Jiang; Lai-Chao Cheng; Kai-Dong Xie; Xiao-Meng Wu; Wen-Wu Guo (Plant Cell Reports, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Structurally diverse diterpenoids from the leaves of Croton mangelong and their anti-diabetic activity - Zhi-Yong Jiang; Qi Niu; Hao-Xin Wang; Hao-Nan Xu; Hong-Xi Xie; Lin Chen; Rong Chen; Hong-Lei Zhang; Lu Gao; Ai-Xue Zuo; Hong-Ping He (Phytochemistry, 2024)

Interactions between fibroblasts and monocyte-derived cells in chronic lung injuries induced by real-ambient particulate matter exposure - Youjin Zeng; Rui Zhang; Yue Jiang; Daochuan Li; Liping Chen; Guanghui Dong; Rong Zhang; Yujie Niu; Wen Chen; Shen Chen (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Environmental high temperature affects pre-implantation embryo development by impairing the DNA repair ability - Si-Jing Qu; Shi-Yong Zhu; En-Yan Wang; Xin-Lei Yan; Rong-Feng Cao; Hua-Tao Li; Zhong-Ling Jiang (Journal of Thermal Biology, 2024)

The sulfurization precipitation and competition mechanisms of Cu(II) and As(V) in electrolyte towards efficient recovery of copper - Guangbin Zhu; Linhua Jiang; Ning Duan; Yong Liu; Rong Zhang; Xiaolu Sun; Hao Jin (Journal of Cleaner Production, 2024)

Recent advances and perspectives of biochar for livestock wastewater: Modification methods, applications, and resource recovery - Rong Gao; Sujuan Ding; Zhuangzhuang Liu; Hongmei Jiang; Gang Liu; Jun Fang (Journal of Environmental Chemical Engineering, 2024)

Construction of oxygen-doped g-C3N4/BiOCl (S-scheme) heterojunction: Efficient degradation of tetracycline in wastewater - Yuan Wei; Yu-Bing Liu; Chao Liu; Xin Li; Guang-Hong Zhao; Rong-Hui Liu; Hong-Yu Wang; Yan-Yan Jiang; Yu-Lan Zhang; Yu-Hui Gao; Gao-Feng Shi; Guo-Ying Wang (Journal of Environmental Chemical Engineering, 2024)

Fe-doping accelerated magnesium storage kinetics in rutile TiO2 cathode materials - Qianwei Zhang; Xin Liu; Changliang Du; Mingwei Jin; Lifen Yang; Rong Jiang; Xilan Ma; Youqi Zhu; Chuanbao Cao; Meishuai Zou (Chemical Engineering Journal, 2024)

Simultaneous carbon, nitrogen and phosphorus removal in sequencing batch membrane aerated biofilm reactor with biofilm thickness control via air scouring aided by computational fluid dynamics - Chun-Hai Wei; Xin-Yu Zhai; Yu-Duo Jiang; Hong-Wei Rong; Li-Gong Zhao; Peng Liang; Xia Huang; Huu Hao Ngo (Bioresource Technology, 2024)

Integrating genetic analysis of germplasm wealth for enhanced selection and improvement in olive (Olea europaea L.): insights from leaves - Wenjun Wu; Miao Shao; Jianli Qi; Gaoming Jin; Rong Zhang; Yufang Yao; Chengying Jiang (Plant Cell Reports, 2024)

Numerical study on thermal–hydraulic behaviors of a natural circulation system with petal-shaped fuel rod bundle - Jian-Chuang Sun; Rong-Jiang Zhou; Xiang-Fei Meng; Jin-Yi Cao; Wen-Chao Zhang; Jin-Cheng Wang; Wei-Hua Cai (Annals of Nuclear Energy, 2024)

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

p‑Phenylenediamine antioxidants in PM2.5: New markers for traffic in positive matrix factorization source apportionment - Nan Jiang; Xuexin Hao; Zichen Wang; Minzhen Li; Dong Zhang; Rong Cao; Ruiqin Zhang; Haijun Zhang; Jiping Chen; Ningbo Geng (Journal of Hazardous Materials, 2024)

Multifaceted anomaly detection framework for leachate monitoring in landfills - Rong Liu; Shiyu Jiang; Jian Ou; Kouao Laurent Kouadio; Bo Xiong (Journal of Environmental Management, 2024)

Synthesis and application of gelatin-based controlled-release antibacterial films containing oregano essential oil/β-cyclodextrin microcapsules for chilling preservation of grass carp fillets - Tianhao Ying; Chenghong Jiang; Sadia Munir; Ru Liu; Tao Yin; Juan You; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

Two-stage exhumation, uplift, and basinward propagation of the Tian Shan during the late Cenozoic - Yutong Jiang; Honghua Lu; Rong Yang; Lichen Pang; Ruohong Jiao; Ying Wang; Jianzhang Pang; Youli Li (Earth-Science Reviews, 2024)

BBB-penetrating magnetoelectric nanoparticles with sustainable Gel formulation for enhanced chemotherapy and reduced postoperative glioma recurrence - Rong Huang; Chenteng Lin; Guangwei Jiang; Meng Zhang; Wenjia Gao; Kamiran Aihemaiti; Qianqian Liu; Jinlong Shi; Wei Shi; Rongqin Huang (Chemical Engineering Journal, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Structured carbon for electromagnetic shielding and microwave absorption from carbonization of waste Polymer: A review - Jiang-Tao Liu; Yu-Chen Zheng; Xin Hou; Xue-Rong Feng; Ke Jiang; Ming Wang (Chemical Engineering Journal, 2024)

New approach for raw biogas: Production of single cell protein by sulfide-tolerant methane-oxidizing bacteria consortia - Hai-Ming Huang; Zhi-Xin Xue; Yu-Feng Jiang; Rui Li; Rong-Bo Guo; Xiao-Lei Fan; Shan-Fei Fu (Chemical Engineering Journal, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

DOTAD: A Database of Therapeutic Antibody Developability - Wenzhen Li; Hongyan Lin; Ziru Huang; Shiyang Xie; Yuwei Zhou; Rong Gong; Qianhu Jiang; ChangCheng Xiang; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2024)

Basic study on cryopreservation of rat calvarial osteoblasts with different cryoprotectants - Xu Jiang; Tan Zhijian; Cao Min; Yu Rong; Tan Xinghui; Xin Gong (Cell and Tissue Banking, 2024)

Sustainable design of photo-Fenton-like oxidation process in actual livestock wastewater through the highly dispersed FeCl3 anchoring on a g-C3N4 substrate - Yanfang Feng; Yunyi Liang; Chenman Ding; Yue Jiang; Hongmei Jin; Shaopeng Rong; Jun Wu; Shiying He; Changlei Xia; Lihong Xue (Water Research, 2024)

Unraveling the early human impacts on the ecosystem of Dianchi Lake: A 20,000-year diatom record from the southeastern Tibetan Plateau - Qian Wang; Xiayun Xiao; Alice Yao; Aubrey L. Hillman; Zhilong Jiang; Rong Wang; Xiangdong Yang (Quaternary Science Reviews, 2024)

Modeling the impact of non-human host predation on the transmission of Chagas disease - Xuan Dai; Xiaotian Wu; Jiao Jiang; Libin Rong (Mathematical Biosciences, 2024)

Spatial distribution of bioaerosols and evaluation of four ventilation method on controlling their diffusion in a typical enhanced biosafety level 2 laboratory - Zhijian Liu; Yongxin Wang; Chuan Jiang; Junzhou He; Rui Rong; Shiyue Li; Zhenyu Liang (Journal of Hazardous Materials, 2024)

High-accuracy quantitative model for phosphate anions in solution based on absorption spectroscopy and machine learning algorithms - Rong Zhang; Linhua Jiang; Ning Duan; Weisong Fu; Jun Ma; Xiaolu Sun; Jiaqi Liao; Hao Jin (Journal of Cleaner Production, 2024)

Removal of fishy flavor in kelp (Laminaria japonica) by natural antioxidant soaking combined with microbial fermentation - Rong Wei; Bo Jiang; Jingjing Chen; Longbei Xiang; Xiaoyong Liu (Food Bioscience, 2024)

Organic substitution regime with optimized irrigation improves potato water and nitrogen use efficiency by regulating soil chemical properties rather than microflora structure - Xiya Wang; Binggeng Yang; Lingling Jiang; Shicheng Zhao; Mengjiao Liu; Xinpeng Xu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Field Crops Research, 2024)

Phosphoric acid pre-swelling strategy constructing acid-doped fluoropoly(aryl pyridinium) membranes to enable high-performance vanadium flow batteries - Tao Ban; Zihui Wang; Yinfei Wang; Yifei Xu; Zhanpeng Jiang; Rong Zeng; Xiuling Zhu (Chemical Engineering Journal, 2024)

Constructing Cu9S5@CuSe heterostructures under microwave irradiation for rechargeable magnesium batteries - Mingwei Jin; Zhaoyu Xue; Heng Cao; Qianwei Zhang; Rong Jiang; Changliang Du; Lifen Yang; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Coastal citizen science monitoring and suggested conservation strategy: ghost crab survey at Suao Dakenggu, Taiwan - Chia-Hsuan Hsu; Wei-Ta Fang; Hung-Kai Chiu; Bing-Rong Jiang; Tsung-Shun Huang (Journal of Coastal Conservation, 2024)

Exposure, Distribution, and Ecological Risk of Four New Bisphenol Analogs in the Typical Lake Region of Taihu Lake - Ying Han; Yuxuan Liu; Xiaolong Rong; Mingxin Wang; Yingang Xue; Hao Dai; Haixia Jiang (Exposure and Health, 2024)

Integrated Information for Pathogenicity and Treatment of Spiroplasma - Yixue You; Jianmin Xiao; Jiaxin Chen; Yuxin Li; Rong Li; Siyuan Zhang; Qichen Jiang; Peng Liu (Current Microbiology, 2024)

A Quantitative Seismic Topographic Effect Prediction Method Based upon BP Neural Network Algorithm and FEM Simulation - Qifeng Jiang; Mianshui Rong; Wei Wei; Tingting Chen (Journal of Earth Science, 2024)

Environmental changes impact on vegetables physiology and nutrition – Gaps between vegetable and cereal crops - Rong Zhou; Fangling Jiang; Yi Liu; Xiaqing Yu; Xiaoming Song; Zhen Wu; Davide Cammarano (Science of The Total Environment, 2024)

Efficacy of BPNS/TiO2 in catalyzing the visible-light-driven degradation of BPA - Hao Dai; Ying Han; Xiaolong Rong; Haixia Jiang; Lulu Jiang; Yingang Xue; Wenbin Liu (Journal of Water Process Engineering, 2024)

Synthesis of proton-conductive Perfluoro(Benzylphosphonic Acid)s via polymer side chain phosphorylation - Elizabeth Salako; Matthew Thompson; Rong Jiang; Yong Gao (Journal of Fluorine Chemistry, 2024)

Fluoride exposure during puberty induces testicular impairment via ER stress-triggered apoptosis in mice - Rong Wang; Wenjing Gong; Yumeng Jiang; Qizi Yin; Ziyue Wang; Jie Wu; Mingming Zhang; Mengyuan Li; Yehao Liu; Juan Wang; Yuanhua Chen; Yanli Ji (Food and Chemical Toxicology, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Cratonic strike-slip fault systems in the central Sichuan Basin, China - Shuwei Guan; Yiqiong Zhang; Hua Jiang; Xuesong Lu; Han Liang; Shipeng Huang; Guangyou Zhu; Rong Ren; Nan Su (Earth-Science Reviews, 2024)

A study on construction of a prognosis model for liver cancer based on analgesic targets and screening therapeutic drugs - Xueyan Jiang; Yaodong Ping; Yuan Chen; Benben Zhu; Rong Fu; Yiwei Hao; Lei Fan (Genes & Genomics, 2024)

Bidirectional biotic interchange between Taiwan Island and Mainland China via land bridges—A case study of Obeidia Walker (Geometridae, Lepidoptera) - Rui Cheng; Nan Jiang; A’rong Luo; Michael Orr; Qingsong Zhou; Xiaoyu Shi; Hongxiang Han; Chaodong Zhu (Zoologica Scripta, 2024)
Biotic exchanges between Taiwan and Mainland China have shaped the biodiversity and ecosystems of both regions. Exchanges from Mainland China to Taiwan have received more attention, mainly studied in terrestrial vertebrates, while the reverse direction and invertebrates have largely been overlooked. Here, we explore the dispersal events between these two regions based on the moths of three species groups of Obeidia , including Taiwan taxa and its relatives from mainland. We conducted mixed methods and analysis, including reconstructing a phylogenetic tree, estimating associated divergence times and inferring ancestral areas and source regions, to explore the phylogeographical structure and genetic pattern of three groups based on eight genes. Our results revealed a structure of three clades and every clade included at least one Taiwanese taxa and its closest relatives of mainland of China, and also served Taiwan as an important source region of two mainland taxa. Our study revealed various origin pattern and dispersal models on the basis of three species groups of Obeidia . Bi‐directional biotic exchange via a land bridge were found: four Taiwanese taxa originated from mainland, and two of them migrated back to mainland. Both eastern Himalayas and south China are important origin areas for Taiwan biota, and the dominant source region may need multiple insect cases to confirm. Our study also provided evidences for disjunct distribution from the perspective of insecta molecular phylogeny.

Profiling of fungal communities in functional food Cistanches herba using high–throughput sequencing - Chune Fan; Rong Xu; Mengyue Guo; Wenjun Jiang; Meihua Yang; Yujie Dao; Xiaohui Pang (Food Bioscience, 2024)

Effects of dietary supplementation with green lentil (Lens culinaris) hulls on NAFLD: Focus on intestinal and hepatic metabolism - Fanghua Guo; Dongying Chen; Rong Tsao; Fereidoon Shahidi; Hua Xiong; Hua Zhang; Li Jiang; Yong Sun (Food Bioscience, 2024)

Enhancing the efficient degradation of BPS using the BPNS-CdS composite catalyst under visible light - Xiaolong Rong; Ying Han; Hao Dai; Haixia Jiang; Yingang Xue (Environmental Research, 2024)

A new simple index for characterizing the labile heavy metal concentration in soil by diffusive gradients in thin films technique - Yang-xiao-xiao Shi; Hai-rong Xu; Jia Shen; Lin-yu Guo; Jing Yan; Jun Jiang; Zhi-neng Hong; Ren-kou Xu (Environmental Pollution, 2024)

Hydrophilic phthalocyanine covalent organic frameworks for enhanced electrocatalytic H2O2 production - Rong Jiang; Qianjun Zhi; Bin Han; Ning Li; Kang Wang; Dongdong Qi; Wenjun Li; Jianzhuang Jiang (Chemical Engineering Journal, 2024)

Tanshinone IIA is superior to paricalcitol in ameliorating tubulointerstitial fibrosis through regulation of VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy - Jing-Yi Zeng; Yu Wang; Fu-Yuan Hong; Miao Miao; Yu-Ying Jiang; Zi-Xuan Qiao; Yun-Tao Wang; Xiao-Rong Bao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Glomerulosclerosis and tubulointerstitial fibrosis (TIF) are closely involved in the development of diabetic nephropathy (DN). Moreover, the development of TIF is closely related to epithelial-to-mesenchymal transition (EMT). Tanshinone IIA (Tan) has various pharmacological effects, especially the anti-fibrotic effect. And it is mainly used in the clinical treatment of cardiovascular diseases. Currently, the protective effect of Tan on DN and its possible mechanism have not been clearly elucidated. Our previous studies illustrated that Tan could improve the EMT of HK-2 cells induced by high glucose by regulating the vitamin D receptor (VDR)/Wnt/β-catenin pathway. Here, we collected demographic information and laboratory results from the National Health and Nutrition Examination Survey (NHANES) database in order to investigate the relationship between VD and DN. Then, we established a DN model and treated DN rats with Tan and paricalcitol (Par) for 6 weeks. We subsequently compared the changes in general condition, renal function, pathological changes, and TIF-related protein expression levels of control rats, DN rats induced by STZ, DN rats with Tan at 5.4 mg/kg, DN rats with Tan at 10.8 mg/kg, and DN rats with Par at 0.054 µg/kg, to explore the effect and mechanism of Tan and Par on DN rats. The results showed that VD had a protective effect against DN in diabetic patients. And we found that Tan had a protective effect on renal fibrosis in DN rats, which was superior to Par in improving the symptoms of “three more and one less,” reducing fasting blood glucose level, improving renal index, BUN/SCr, and UACR, reducing histopathological damage of kidney, and improving the expression of fibrosis-related proteins in kidney tissue by regulating VDR/Wnt/β-catenin pathway. Tan was superior to Par in ameliorating tubulointerstitial fibrosis by regulating VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy.

Structural elucidation a complex galactosyl and glucosyl-rich pectin from the pericarp of immature fruits of Juglans mandshurica Maxim. - Xi-Zhe Sun; Qing-Yu Zhang; Si-Liang Jiang; Rong-Jian Zhu; Jun-Hong Chai; Jun Liang; Hai-Xue Kuang; Yong-Gang Xia (Glycoconjugate Journal, 2024)

New diterpenoid alkaloids from Delphinium pachycentrum Hemsl - Yuan-Feng Yan; Ya-Rong Wang; Hong-Jun Jiang; Zong-Bao Ding; Tian-Peng Yin (Natural Product Research, 2024)

Increasing spray volume and ozone spray of tetraconazole improve control against strawberry powdery mildew - Lili Jiang; Bingjie Liu; Shouan Zhang; Rong Zhang; Chong Wu; Kang Qiao (Crop Protection, 2024)

Stress response of Microcystis aeruginosa to chlorine during transportation: The significance of surface-adsorbed organic matter - Jing Qi; Yuancheng Jiang; Rong Ni; Xi Wang; Chengzhi Hu; Jiuhui Qu (Water Research, 2024)

Fate of sulfamethoxazole in wetland sediment under controlled redox conditions - Yujie He; Longxue Jiang; Xuan Wu; Wenhui Zhang; Yao Zong; Jiacheng Wang; Jinmei Chen; Jun Shan; Deyang Kong; Rong Ji (Water Research, 2024)

Global impact of enhanced-efficiency fertilizers on vegetable productivity and reactive nitrogen losses - Zhaolong Pan; Ping He; Daijia Fan; Rong Jiang; Daping Song; Lei Song; Wei Zhou; Wentian He (Science of The Total Environment, 2024)

Enhanced atomic H* utilization on urchin-like TiO2-supported palladium nanoparticles for efficient electrocatalytic detoxification of chlorinated organics - Jun Zhang; Shuyue Liu; Shiyu Lu; Chunyuan Wang; Pingjuan Liang; Huan Yi; Mengjie Li; Laizheng Luo; Rong Wang; Guangming Jiang (Fuel, 2024)

Dual-edged sword effects of sulfation/hydration on Ce-doped TiO2(001) single-atom catalyst for NH3-SCR reaction: A first-principles study - Ye Jiang; Yichao Xu; Xin Sun; Guomeng Zhang; Zihan Rong; Yinsheng Jiang; Jiayao Song; Zhengda Yang (Fuel, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

Space-specific flux estimation of atmospheric chemicals from point sources to soil - Xinyue Chen; Meie Wang; Tian Xie; Rong Jiang; Weiping Chen (Environmental Pollution, 2024)

In vitro degradation and dual responsively antibacterial zeolitic imidazolate frameworks-8@Rhein composite coating on magnesium alloy - Chen-Hui Duan; Kui Xue; Lan-Yue Cui; Xue-Wen Jiang; Yan-Yu Zhang; Cheng-Bao Liu; Shuo-Qi Li; Fen Zhang; Rong-Chang Zeng (Chemical Engineering Journal, 2024)

Large-scale production of graphene encapsulated silicon nanospheres as flexible anodes for lithium ion batteries - Yanlin Zhang; Dafang He; Junhong Lu; Jie Huang; Haoyang Jiang; Junfeng Rong; Guolin Hou; Haiqun Chen (Chemical Engineering Journal, 2024)

Microwave-induced defect-rich vanadium sulfide cathodes for highly reversible electrochemical magnesium storage - Rong Jiang; Bolin Liu; Changliang Du; Mingwei Jin; Xin Liu; Xilan Ma; Youqi Zhu; Meishuai Zou; Chuanbao Cao (Chemical Engineering Journal, 2024)

Effect of space electric field on the shelf-life extension of plum fruit (GuoFeng17) - Yuzhuo Lu; Yongfeng Jiang; Hairong Wang; Jumeng Yu; Huifeng Hou; Chuansheng Rong; Ning Liu; Yi Hao (Journal of Food Engineering, 2024)

Efficient recovery of copper resources from copper smelting waste acid based on Cu(Ⅱ)/As(Ⅲ) competitive sulfuration mechanism - Xiaolu Sun; Linhua Jiang; Ning Duan; Guangbin Zhu; Yanli Xu; Hao Jin; Yong Liu; Rong Zhang (Journal of Cleaner Production, 2024)

Investigation of pathogen-laden aerosol aerodynamics and ventilation rates on their long-range transmission: A study on the Fangcang shelter hospital - Chuan Jiang; Zhijian Liu; Yongxin Wang; Guangpeng Yao; Shiyue Li; Rui Rong; Zhenyu Liang; Haiyang Liu; Jingwei Liu; Tongliang Wan; Junzhou He (Journal of Cleaner Production, 2024)

Early warning of urban heavy metal pollution based on PMF- MeteoInfo model combined with physicochemical properties of dust - Yue Zeng; Yajie Jiang; Yunqin Li; Xiang Xu; Xinying Zhang; Wei Yu; Rong Yu; Xinyu Liu (Stochastic Environmental Research and Risk Assessment, 2024)

Soil carbon storage and accessibility drive microbial carbon use efficiency by regulating microbial diversity and key taxa in intercropping ecosystems - Ziyu Yang; Qirui Zhu; Yuping Zhang; Pan Jiang; Yizhe Wang; Jiangchi Fei; Xiangmin Rong; Jianwei Peng; Xiaomeng Wei; Gongwen Luo (Biology and Fertility of Soils, 2024)

Response of soil microbial properties in the life cycle of potatoes to organic substitution regimes in North China - Xiya Wang; Shicheng Zhao; Xinpeng Xu; Mengjiao Liu; Rong Jiang; Jun Zhang; Yu Duan; Ping He; Wei Zhou (Soil and Tillage Research, 2024)

Biodiversity and core microbiota of key-stone ecological clusters regulate compost maturity during cow-dung-driven composting - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Yong Yang; Xingxiang Deng; Guixian Xie; Gongwen Luo (Environmental Research, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Controlling airborne pathogen within Fangcang shelter hospitals: Aerodynamic analysis of bioaerosols released from various locations through experiment and simulation - Chuan Jiang; Zhijian Liu; Xia Xiao; Haiyang Liu; Junzhou He; Rui Rong; Jingwei Liu; Zhenzhe Huang; Yongxin Wang (Building and Environment, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Comprehensive plasmid toolkit for multipart assembly in the Dunaliella salina nuclear system - Hao-Hong Chen; Yu-Chen Xie; Shan-rong Xie; Jian-Guo Jiang (Algal Research, 2024)

27-Hydroxycholesterol inhibits trophoblast fusion during placenta development by activating PI3K/AKT/mTOR signaling pathway - Xiaoyan Zhao; Xiaxia Cai; Haiyan Zhu; Qinyu Dang; Qian Yang; Yandi Zhu; Yadi Zhang; Mengling Zhang; Xinyin Jiang; Zhuo Hu; Yuchen Wei; Rong Xiao; et al. (Archives of Toxicology, 2024)

Comparative study on anthropogenic impacts on soil PAHs: Accumulation and source apportionment in tourist and industrial cities in Hebei Province, China - Tian Xie; Meie Wang; Rong Jiang; Lei Li; Xinyue Chen; Suriyanarayanan Sarvajayakesavalu; Weiping Chen (Science of The Total Environment, 2024)

Composition of DOM along the depth gradients in the paddy field treated with crop straw for 10 years - Rong Huang; Zheng Li; Yi Xiao; Jiang Liu; Tao Jiang; Ouping Deng; Xiaoyang Tang; Yingjie Wu; Qi Tao; Qiquan Li; Youlin Luo; Xuesong Gao; et al. (Journal of Environmental Management, 2024)

Reliability-based design optimization scheme of isolation capacity of nonlinear vibration isolators - Huizhen Liu; Xianzhen Huang; Zhiyuan Jiang; Shangjie Li; Zhiming Rong (Engineering Structures, 2024)

Negative thermopower anisotropic ionic thermoelectric hydrogels based on synergistic coordination and hydration for low-grade heat harvesting - Luzheng Chen; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Wenjia Han; Jiang Lou (Chemical Engineering Journal, 2024)

Reactant enrichment in yolk-shell structured Pd/TiN nanoreactors for boosting electrocatalytic hydrodechlorination performance - Jun Zhang; Chunyuan Wang; Shiyu Lu; Shuyue Liu; Pingjuan Liang; Huan Yi; Mengjie Li; Meng Jin; Rong Wang; Guangming Jiang (Chemical Engineering Journal, 2024)

Modelling adaptation measures to improve maize production and reduce soil N2O emissions under climate change in Northeast China - Daijia Fan; Daping Song; Rong Jiang; Ping He; Yaoyao Shi; Zhaolong Pan; Guoyuan Zou; Wentian He (Atmospheric Environment, 2024)

Toxicity of common biocides used in aquaculture to embryos and larvae of Brachymystax tsinlingensis Li - Xing‐chen Guo; Zhi‐peng Chu; Rong‐qun Song; Zhen‐lu Wang; Rui‐jiao Li; Dong‐mei Xiong; Mu‐zi Zhang; Hai‐bo Jiang; Jian Shao (Journal of Fish Biology, 2024)
Brachymystax tsinlingensis Li is a threatened fish species endemic to China. With the problems of environmental factors and seeding breeding diseases, it is important to further improve the efficiency of seeding breeding and the basis of resource protection. This study investigated the acute toxicity of copper, zinc and methylene blue (MB) on hatching, survival, morphology, heart rate (HR) and stress behaviour of B. tsinlingensis . Eggs (diameter: 3.86 ± 0.07 mm, weight: 0.032 ± 0.004 g) of B. tsinlingensis were selected randomly from artificial propagation and developed from eye‐pigmentation‐stage embryos to yolk‐sac stage larvae (length: 12.40 ± 0.02 mm, weight: 0.03 ± 0.001 g) and exposed to different concentrations of Cu, Zn and MB for 144 h in a series of semi‐static toxicity tests. The acute toxicity tests indicated that the 96‐h median lethal concentration (LC 50 ) values of the embryos and larvae were 1.71 and 0.22 mg l −1 for copper and 2.57 and 2.72 mg l −1 for zinc, respectively, whereas the MB LC 50 after 144‐h exposure for embryos and larvae were 67.88 and 17.81 mg l −1 , respectively. The safe concentrations of copper, zinc and MB were 0.17, 0.77 and 6.79 mg l −1 for embryos and 0.03, 0.03 and 1.78 mg l −1 for larvae, respectively. Copper, zinc and MB treatments with concentrations greater than 1.60, 2.00 and 60.00 mg l −1 , respectively, led to a significantly low hatching rate and significantly high embryo mortality ( P −1 led to significantly high larvae mortality ( P P P B. tsinlingensis embryos or larvae might be more resistant to copper, zinc and MB than other members of the Salmonidae family, which benefits their resource protection and restoration.

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

An appropriate amount of straw replaced chemical fertilizers returning reduced net greenhouse gas emissions and improved net ecological economic benefits - Lian Zhang; Guoliang Jiang; Rusheng Xiao; Kun Hou; Xin Liu; Xinyu Liu; Pei Yuan; Feng Tian; Lichu Yin; Hongmei Zhu; Chang Tian; Lan Yang; et al. (Journal of Cleaner Production, 2024)

Impacts of climate change on fractional vegetation coverage of temperate grasslands in China from 1982 to 2015 - Rong Ma; Jiaqi Zhang; Xiangjin Shen; Binhui Liu; Xianguo Lu; Ming Jiang (Journal of Environmental Management, 2024)

A novel approach for evaluating the transport capacity of sandstone carriers and determining effective hydrocarbon migration channels: Application to the Pinghu Slope Belt of the Xihu Depression, East China Sea Basin - Fuwei Wang; Dongxia Chen; Meijun Li; Zhangxin Chen; Qiaochu Wang; Khawaja Hasnain Iltaf; Sha Li; Wenzhi Lei; Mengya Jiang; Yuqi Wang; Lanxi Rong (Journal of Asian Earth Sciences, 2024)

Effect of blending ratio on the compatibility and stability of konjac glucomannan/starch composite systems - Qian Zhang; Sicong Yan; Rong Zhou; Xu Yan; Peineng Zhu; Lingyun Chen; Fatang Jiang (Food Hydrocolloids, 2024)

Stability analysis of unsaturated soil slopes with cracks under rainfall infiltration conditions - Lei Zhang; Xin Jiang; Rong Sun; Hanyan Gu; Yongguo Fu; Yanjun Qiu (Computers and Geotechnics, 2024)

A pleiotropic SIS-based hydrogel with immunomodulation via NLRP3 inflammasome inhibition for diabetic bone regeneration - Ning Sheng; Fei Xing; Qing-Yi Zhang; Jie Tan; Rong Nie; Kai Huang; He-Xi Li; Yan-Lin Jiang; Bo Tan; Zhou Xiang; Hui-Qi Xie (Chemical Engineering Journal, 2024)

A co-located QTL for seven spike architecture-related traits shows promising breeding use potential in common wheat (Triticum aestivum L.) - Jieguang Zhou; Qian Liu; Rong Tian; Huangxin Chen; Jian Wang; Yaoyao Yang; Conghao Zhao; Yanlin Liu; Huaping Tang; Mei Deng; Qiang Xu; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

A near-infrared fluorescent probe for viscosity: Differentiating cancer cells from normal cells and dual-modal imaging in tumor mice - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Yongfei Li; Chun-Yan Li (Analytica Chimica Acta, 2024)

Farnesane sesquiterpenoids from Rubus delavayi and their anti- Trichinella spiralis activities - Yi Hao; Xiao-Lei Luo; Min Wang; Rong Liu; Wei Zhang; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Effect comparisons of different conditioners and microbial agents on the degradation of estrogens during dairy manure composting - Yan Li; Dong Zeng; Xiao-Lu Jiang; De-Chun He; Jia-Wu Hu; Zi-Wei Liang; Jia-Cheng Wang; Wang-Rong Liu (Chemosphere, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Dynamic human exposure to airborne bacteria-associated antibiotic resistomes revealed by longitudinal personal monitoring data - Rong-min Zhang; Xin-lei Lian; Li-wei Shi; Liuyiqi Jiang; Shan-shan Chen; Wen-qing Haung; Jia-en Wu; Fei-jing Wu; Jian Sun; Xiao-ping Liao; Yun-xiao Chong; Ya-hong Liu; et al. (Science of The Total Environment, 2023)

Low-cost ZIF-67-modified fabrics with effective photothermal disinfection for antimicrobial personal protective equipment production - Nan Jiang; Qian Wang; Huiqiong Zhang; Ziwei Liu; Hao Yang; Rong Chen; Zhong Lu (Journal of Environmental Chemical Engineering, 2023)

Widely targeted metabolic profiling provides insights into variations in bioactive compounds and antioxidant activity of sesame, soybean, peanut, and perilla - Habtamu Kefale; Senouwa Segla Koffi Dossou; Feng Li; Nanjun Jiang; Rong Zhou; Lei Wang; Yanxin Zhang; Donghua Li; Jun You; Linhai Wang (Food Research International, 2023)

Effect of cooking methods on metabolites of deep purple-fleshed sweetpotato - Xia Jiang; Rong Zhang; Yanqiang Yao; Yiling Yang; Bin Wang; Zhangying Wang (Food Chemistry, 2023)

Effect of geographical origins and pile-fermentation on the multi-element profiles of ripen Pu-erh tea revealed by comprehensive elemental fingerprinting - Jiayi Zhu; Le Chen; Yue Chen; Yuting Rong; Yongwen Jiang; Fuqiao Liu; Qinghua Zhou; Xuehong Wei; Haibo Yuan; Junjie Zhang; Jia Li (Food Control, 2023)

Separated two-stage hydrothermal liquefaction of livestock manure for high-quality bio-oil with low-nitrogen content: Insights on nitrogen migration and evolution - Siyuan Long; Haiwei Jiang; Jinming Shi; Xianbin Ai; Zhigang Que; Hanbing Nie; Chunbao Charles Xu; Rong Huang; Yinxuan Fu; Weiran Yang (Chemical Engineering Journal, 2023)

Super-stretching and high-performance ionic thermoelectric hydrogels based on carboxylated bacterial cellulose coordination for self-powered sensors - Luzheng Chen; Jiang Lou; Xuhui Rong; Zhuqing Liu; Qijun Ding; Xia Li; Yifei Jiang; Xingxiang Ji; Wenjia Han (Carbohydrate Polymers, 2023)

Biology and morphology of the larvae of Uropyia meticulodina (Lepidoptera: Notodontidae), with discussion on their feeding and defensive strategies - Jia-Xin Liu; Di Zhao; Hui-Rong Hu; Yi-Yi Liu; Shi-Ci Zhao; Lu Jiang (Zoomorphology, 2023)

Tree species mixture effect on extracellular enzyme kinetics varies with enzyme type and soil depth in subtropical plantations - Xue-Li Jiang; Rong Mao; Zhong-Liang Li; Fu-Sheng Chen; Bin Xu; Jin He; Yu-Xin Huang; Xiang-Min Fang (Plant and Soil, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

An integrated risk assessment framework for multiple natural disasters based on multi-dimensional correlation analysis - Weichao Yang; Xuebo Dun; Xuelian Jiang; Yadong Zhou; Bingtao Hou; Ruiqing Lang; Rong Zhuang; Qingling Meng (Natural Hazards, 2023)

Echinacoside, a promising sortase A inhibitor, combined with vancomycin against murine models of MRSA-induced pneumonia - Tao Jiang; Dai Yuan; Rong Wang; Chunhui Zhao; Yangming Xu; Yinghui Liu; Wu Song; Xin Su; Bingmei Wang (Medical Microbiology and Immunology, 2023)

Morphological and Pull-Out Mechanical Properties of Alfalfa Roots in the Seedling Stage - Chaobo Zhang; Rong Li; Jing Jiang; Qihong Yang (Journal of Soil Science and Plant Nutrition, 2023)

The expression of CD86 in CD3+CD56+ NKT cells is associated with the occurrence and prognosis of sepsis-associated encephalopathy in sepsis patients: a prospective observational cohort study - Sheng-long Chen; Xiao-yu Liu; Jun-hong Huang; Lu-hua Xian; Xu-sheng Li; Kang-rong Wang; Jing Li; Tian-cao Zhang; Guo-ge Huang; Xin-qiang Liu; Hong-ke Zeng; Mao-hua Zhou; et al. (Immunologic Research, 2023)

Exploring Environmental Nanoplastics Research: Networks and Evolutionary Trends - Qisheng Yu; Chia-Ying Anderin Chuang; Yuelu Jiang; Huan Zhong; Andrew Cundy; Raymond W. M. Kwong; Chao Min; Xiaoshan Zhu; Rong Ji (Reviews of Environmental Contamination and Toxicology, 2023)
Analyzing scientific advances and networks in NPs research can provide valuable insights into the evolving trends, research gaps, and priorities for future research efforts, highlighting the importance of scientific research in pollution control and risk management of uncontrolled and unknown nanoplastics (NPs) that pose a potential global threat, and have raised concerns in the scientific community and media. A total of 2055 nanoplastics (NPs) studies published from 1995 onwards were retrieved from the Web of Science Core Collection database. Bibliometric methods were applied to assess evolving scientific advances and networks. The general term, “nanoplastics,” was first introduced in 1995 as “intelligent” materials. Before 2009, defined as the ambiguous stage, NPs were produced and applied in many different manufacturing areas and processes. The first research referring to nano-scale plastic particles/debris as potential hazardous contaminants appeared in 2010. Thereafter, the number of annual publications on NPs has increased rapidly, particularly from 2018 onwards. Results showed China published 822 scientific papers, overtaking the United States’ 229 papers, whereas European researches, i.e., the Netherlands, Portugal, German, and the United Kingdom, led in quality and citation with extensive international collaborations. Furthermore, we concluded three main research themes from keyword cluster analysis: environmental monitoring (identification, quantification, fresh-water, marine-environment); environmental behaviors (fate, adsorption, aggregation, transport); and toxicology (toxicity, exposure, ingestion, oxidative stress). Toxicology and environmental behaviors of NPs were the leading themes. An overview of the current understanding of NPs in the above three major themes provides perspectives to identify future research directions based on knowledge gaps, e.g., advancing analytical methods, and exploring the mobility and fate of NPs in different ecosystems. Scientific research on NPs is a key fundamental requirement for their pollution control and risk management. To bridge the gap between research and reality, future efforts are required to promote the dissemination of scientific research findings and encourage actions in engineering, policy, education, etc., to support a sustainable society. Graphical Abstract

Climatic aridification restrained late Cenozoic denudation of the Tian Shan in the inland of Asia - Yutong Jiang; Honghua Lu; Ruohong Jiao; Lichen Pang; Rong Yang; Menghan Wu; Xiangmin Zheng; Youli Li (Global and Planetary Change, 2023)

ZC3H4 governs epithelial cell migration through ROCK/p-PYK2/p-MLC2 pathway in silica-induced pulmonary fibrosis - Rong Jiang; Yichao Zhou; Qianqian Gao; Lei Han; Zhen Hong (Environmental Toxicology and Pharmacology, 2023)

Linear relationship between CH4 fluxes and atmospheric CO2 concentration levels controlled by rice biomass and soil methanogenic communities - Yuanyuan Wang; Zhenghua Hu; Shuqi He; Qiang Jing; Lidong Shen; Chao Liu; Zhurong Wu; Wei Huang; Guihua Lu; Rui Cao; Kezhi Zheng; Ning Dong; et al. (Nutrient Cycling in Agroecosystems, 2023)

Properly interpret metabolic inhibition results to identify primary mercury methylating microbes - Pei Lei; Ri-Qing Yu; Yaqi Kong; Stefan Bertilsson; Martin Tsz-Ki Tsui; Tao Jiang; Jiating Zhao; Yu-Rong Liu; Rinklebe Jörg; Huan Zhong (Critical Reviews in Environmental Science and Technology, 2023)

An integrative analysis of lipidomics and transcriptomics in various mouse brain regions in response to real-ambient PM2.5 exposure - Shuangjian Qin; Huixian Zeng; Qizhen Wu; Qingqing Li; Mohammed Zeeshan; Lizhu Ye; Yue Jiang; Rui Zhang; Xinhang Jiang; Miao Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Cardiovascular effects of wearing respirators against particulate matter: A randomized crossover trial - Xin Meng; Meilin Yan; Meijie Jiang; Xueling Meng; Liang Qi; Xinyan Hu; Ruiwei Xu; Yunxiu Shi; Weiju Li; Shiyi Chen; Tong Zhu; Jing Deng; et al. (Science of The Total Environment, 2023)

The divergent effects of nitrate and ammonium application on mercury methylation, demethylation, and reduction in flooded paddy slurries - Ji Chen; Gongren Hu; Jiang Liu; Alexandre J. Poulain; Qiang Pu; Rong Huang; Bo Meng; Xinbin Feng (Journal of Hazardous Materials, 2023)

Heavy metal pollution triggers a shift from bacteria-based to fungi-based soil micro-food web: Evidence from an abandoned mining-smelting area - Rong Jiang; Meie Wang; Weiping Chen (Journal of Hazardous Materials, 2023)

Alignment of Fe3O4/CNT electrodes via magnetic blade printing for wireless stress-direction-recognizing strain sensor - Guangwei Wang; Chenhao Cong; Xianbing Zheng; Hongjiang Li; Fuhao Jiang; Xuhao Wang; Rong Li; Mingliang Jin; Pengfei Zhang; Junru Li; Chuanwei Zhang; SeHyun Kim; et al. (Chemical Engineering Journal, 2023)

Neuroglobin Facilitates Neuronal Oxygenation through Tropic Migration under Hypoxia or Anemia in Rat: How Does the Brain Breathe? - Chun-Yang Li; Hai-Feng Jiang; Li Li; Xiao-Jing Lai; Qian-Rong Liu; Shang-Bin Yu; Cheng-La Yi; Xiao-Qian Chen (Neuroscience Bulletin, 2023)

Evaluating the service quality of insular and coastal recreational fisheries by integration of the SERVQUAL-fuzzy Kano model and importance-performance analysis - Xinqiang Jiang; Junbo Zhang; Chenxing Yang; Rong Wan (Ocean & Coastal Management, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Magma process of the ore-forming gabbrodiorite porphyry of the Meishan iron deposit, eastern China: Insights from the phenocrysts chemistry - Wen-Hao Liu; Man-Rong Jiang; Yan Xia; Xiao-Jun Zhang (Journal of Geochemical Exploration, 2023)

Mechanism of arsenic distribution and migration during iron extraction by copper slag-steel slag combined reforming: A potential solution to refractory wastes - Yun Zhou; Hongyang Wang; Haichuan Wang; Kai Dong; Rong Zhu; Zhenqiang Jiang; Guangsheng Wei (Journal of Cleaner Production, 2023)

Machine learning-based predictive analysis of total polar compounds (TPC) content in frying oils: A comprehensive electrochemical study of 6 types of frying oils with various frying timepoints - Anoop C. Patil; Arjun Kesav Mugilvannan; Junmei Liang; Yuan-Rong Jiang; Untzizu Elejalde (Food Chemistry, 2023)

Multiomics reveals new biomarkers and mechanistic insights into the combined toxicity effects of 2,2′,4,4′,5,5′-hexachlorobiphenyl and atrazine exposures in MCF-7 cells - Yu-Shun Lu; Xing Wen; Ju Chen; Xiao-Rong He; Jiang Yu; Jing Qiu; Yong-Zhong Qian; Yan-Yang Xu (Environmental Pollution, 2023)

Identification and evaluation of a novel PARP1 inhibitor for the treatment of triple-negative breast cancer - Rong Gong; ZhongYe Ma; LinHao He; ShiLong Jiang; DongSheng Cao; Yan Cheng (Chemico-Biological Interactions, 2023)

Does accountability audit of natural resource promote corporate environmental performance? An external supervision perspective - Cailou Jiang; Rong Liu; Jie Han (Environment, Development and Sustainability, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Nitrogen-containing malodorous gas pollutants emission characteristics and health risk assessment from an A/O wastewater treatment plant - Yufan Dong; Linlin Ma; Yi Peng; Zhanhong Hu; Zongze Xu; Xiancong Jiang; Rong Cheng; Haolin Chen; Qing Yang (Journal of Water Process Engineering, 2023)

Interaction of metabolism-related pathway gene variants with bisphenol A exposure on serum lipid profiles - Heng He; Fuwei Zhang; Shuang Zhou; Shanshan Zhang; Lu Wang; Jiaoyuan Li; Qiang Zeng; Ying Zhu; Jianbo Tian; Jiang Chang; Liming Cheng; Qing Lu; et al. (Environmental Toxicology and Pharmacology, 2023)

Involvement of Abnormal p-α-syn Accumulation and TLR2-Mediated Inflammation of Schwann Cells in Enteric Autonomic Nerve Dysfunction of Parkinson’s Disease: an Animal Model Study - Wenwen Jiang; Yue Cheng; Ye Wang; Jing Wu; Zhe Rong; Li Sun; Yan Zhou; Kezhong Zhang (Molecular Neurobiology, 2023)

TFEB: a double-edged sword for tumor metastasis - Jun-Hu Hu; Shou-Ye Li; Li-Hua Yu; Zhen-Rong Guan; Ya-Ping Jiang; Die Hu; Hao-Jie Wang; Li-Ping Zhao; Zhao-Huang Zhou; Ya-Xin Yan; Tian Xie; Zhi-Hui Huang; et al. (Journal of Molecular Medicine, 2023)

Dauer larva-derived extracellular vesicles extend the life of Caenorhabditis elegans - Jing Ma; Yi-ting Wang; Ling-hui Chen; Bang-ya Yang; Yong-zhu Jiang; Lan-xi Wang; Zhi-qi Chen; Guan-rong Ma; Liao-qiong Fang; Zhi-biao Wang (Biogerontology, 2023)
There is growing evidence that extracellular vesicles (EVs) play a functional role in tissue repair and anti-aging by transferring the contents of donor cells to recipient cells. We hypothesized that Dauer ( C. elegans ), known as “ageless” nematodes, can also secrete extracellular vesicles and influence the lifespan of C. elegans . Here, we isolated EVs of dauer larvae (dauer EVs). Dauer EVs were characterized using transmission electron microscopy, nanoparticle tracking analysis (NTA), and Western blot analysis. Wild-type C. elegans were fed in the presence or absence of dauer EVs and tested for a range of phenotypes, including longevity, mobility and reproductive capacity. Results showed that dauer EVs increased the average lifespan of nematodes by 15.74%, improved mobility, slowed age-related pigmentation as well as body length, and reduced the accumulation of reactive oxygen species and lipids, while not impairing nematode reproductive capacity. These findings suggest that dauer EVs can extend the lifespan of C. elegans as well as the healthy lifespan by reducing ROS accumulation, with potential anti-aging capacity.

A cascade electro-dehydration process for simultaneous extraction and enrichment of uranium from simulated seawater - Ruirui Li; Huangying Wang; Junying Yan; Rong Fu; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Water Research, 2023)

Ergostane-type sterols and sesquiterpenes with anti-neuroinflammatory activity from a Nigrograna species associated with Clematis shensiensis - Liang-Liang Zhai; Ting-Ting Jiang; Rong Zhang; Jian-Nan Li; Yi-Jie Zhai; Qiang Zhang; Ding Li; Wen-Bo Han (Phytochemistry, 2023)

Identification and characterization of goat milk key flavor compounds and their precursors in electron beam irradiation and pasteurization on raw - Chunlu Wen; Ya Chen; Madina; Linlu Zhang; Yue Peng; Bai Rong; Linjie Xi; Shengqi Jiang; Jiangtao Yu; Junqing Bai; Niu Wei; Li Kui; et al. (Innovative Food Science & Emerging Technologies, 2023)

Label-free detection of trace level zearalenone in corn oil by surface-enhanced Raman spectroscopy (SERS) coupled with deep learning models - Jiaji Zhu; Xin Jiang; Yawen Rong; Wenya Wei; Shengde Wu; Tianhui Jiao; Quansheng Chen (Food Chemistry, 2023)

Deeply removal of trace Cd2+ from water by bacterial cellulose membrane loaded with nanoscale zerovalent iron: Practical application and mechanism - Rong Cheng; Yating Chen; Peiwen Jiang; Jianzhong Zheng; Xiang Zheng (Chemical Engineering Journal, 2023)

A direct electrochemical substitution electrodialytic system for CO2 conversion into high value-added soda - Huangying Wang; Haiyang Yan; Kang Peng; Junying Yan; Rong Fu; Ruirui Li; Baoying Wang; Chenxiao Jiang; Yaoming Wang; Tongwen Xu (Chemical Engineering Journal, 2023)

A spatial downscaling method for multielement meteorological data: case study from a water conservation area of the upper Yellow River basin - Ying Cao; Biao Zeng; Fuguang Zhang; Yanqi Shen; Zhenhua Meng; Rong Jiang (Theoretical and Applied Climatology, 2023)

Research Progress on the Osteogenesis-Related Regulatory Mechanisms of Human Umbilical Cord Mesenchymal Stem Cells - Zhengqi Hu; Zhiliang Jiang; Shengzi Meng; Rong Liu; Kun Yang (Stem Cell Reviews and Reports, 2023)

Synergistic effect of elevated glucose levels with SARS-CoV-2 spike protein induced NOX-dependent ROS production in endothelial cells - Jiahao Zhang; Li He; Rong Huang; Juan Felipe Alvarez; David H. Yang; Qihao Sun; Fengqin Wang; Zhiyong Peng; Nanhui Jiang; Lianjiu Su (Molecular Biology Reports, 2023)

Environmental polycyclic aromatic hydrocarbon exposure is associated with low back pain - Jiang Chen; Yangjie Liao; Mingjiang Luo; Siliang Tang; Jinshan Huang; Rong Chen; Zhihong Xiao (Environmental Geochemistry and Health, 2023)

Broad humoral immunity generated in mice by a formulation composed of two antigens from the Delta variant of SARS-CoV-2 - Yadira Lobaina; Rong Chen; Edith Suzarte; Panchao Ai; Vivian Huerta; Changyuan Tan; Liz Alvarez-Lajonchere; Yang Liling; Alexis Musacchio; Ricardo Silva; Gerardo Guillén; Jiang Zaixue; et al. (Archives of Virology, 2023)

Genomic insights into secondary metabolites of pharmaceutical utility for Hyphococcus flavus MCCC 1K03223T, isolated from bathypelagic seawater - Jin-Cheng Rong; Li Sheng; Li-Hua Jiang; Mao-Li Yi; Jin-Ying Wu; Qi Zhao (Marine Genomics, 2023)

Impacts of land use conversions on soil organic carbon in a warming-induced agricultural frontier in Northern Ontario, Canada under historical and future climate - Rong Jiang; Susantha Jayasundara; Brian B. Grant; Ward N. Smith; Budong Qian; Adam Gillespie; Claudia Wagner-Riddle (Journal of Cleaner Production, 2023)

Coaxial electrospun nanofibrous substrates with tunable wettability for constructing cucurbit[n]uril-embedded organic solvent nanofiltration membranes - Qian Wang; Qin-Yuan He; Liu-Lin Zhao; Yue Wang; Rong Fang; Cong Luo; Wei-Tong Lu; Hong-Ya Jiang; Shi-Peng Sun; Xue-Li Cao (Chemical Engineering Journal, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Efficacy of Aidi injection combined with chemotherapy, radiotherapy or chemoradiotherapy for unresectable esophageal cancer treatment: A meta-analysis and systematic review of 29 randomized controlled trials based on Asian populations (China) - Jinsheng Huang; Teng Fan; Yuming Rong; Xujia Li; Qi Jiang; Jun Kan; Huijuan Qiu; Qi Quan; Bei Zhang; Guifang Guo (European Journal of Clinical Pharmacology, 2023)

Lithium extraction from salt lake brines with high magnesium/lithium ratio: a review - Rong Zhu; Shixin Wang; C. Srinivasakannan; Shiwei Li; Shaohua Yin; Libo Zhang; Xiaobin Jiang; Guoli Zhou; Ning Zhang (Environmental Chemistry Letters, 2023)

Improving potato productivity and mitigating nitrogen losses using enhanced-efficiency fertilizers: A global meta-analysis - Zhaolong Pan; Daijia Fan; Rong Jiang; Naeem Abbasi; Daping Song; Guoyuan Zou; Dan Wei; Ping He; Wentian He (Agriculture, Ecosystems & Environment, 2023)

A mathematical model for intracellular NO and ROS dynamics in vascular endothelial cells activated by exercise-induced wall shear stress - Xiao Zeng; Chun-Dong Xue; Yong-Jiang Li; Kai-Rong Qin (Mathematical Biosciences, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Bioaccessibility and transport of lentil hull polyphenols in vitro, and their bioavailability and metabolism in rats - Fanghua Guo; Li Peng; Hua Xiong; Rong Tsao; Hua Zhang; Li Jiang; Yong Sun (Food Research International, 2023)

Environmental-thermal-economic performance trade-off for rural residence retrofitting in the Beijing–Tianjin–Hebei region, Northern China: A multi-objective optimisation framework under different scenarios - Yuan Gao; Shulong Luo; Jiabin Jiang; Yuan Rong (Energy and Buildings, 2023)

Extracellular Vesicles from NMN Preconditioned Mesenchymal Stem Cells Ameliorated Myocardial Infarction via miR-210-3p Promoted Angiogenesis - Yanan Pu; Chunyu Li; Xin Qi; Rui Xu; Liyang Dong; Yi Jiang; Qingyun Gong; Di Wang; Rong Cheng; Cheng Zhang; Yan Chen (Stem Cell Reviews and Reports, 2023)
Mesenchymal stem cell-derived extracellular vesicles (MSCs-EVs) possess cardioprotection in acute myocardial infarction. Nevertheless, the therapeutic intervention potential and the molecular mechanism of EVs from NMN (Nicotinamide mononucleotide) preconditioned hUCMSCs (N-EVs) in acute myocardial infarction remains unknown. In the present study, EVs from hUCMSCs (M-EVs) and N-EVs were identified by electron microscopy, immunoblotting and nanoparticle tracking analysis. Compared with M-EVs, N-EVs significantly increased the proliferation, migration, and angiogenesis of HUVECs. Meanwhile, N-EVs markedly reduced apoptosis and cardiac fibrosis and promoted angiogenesis in the peri-infarct region in the MI rats. A high-throughput miRNA sequencing and qPCR methods analysis revealed that miR-210-3p was abundant in N-EVs and the expression of miR-210-3p was obviously upregulated in HUVECs after N-EVs treated. Overexpression of miR-210-3p in HUVECs significantly enhanced the tube formation, migration and proliferative capacities of HUVECs. However, downregulation of miR-210-3p in HUVECs markedly decreased the tube formation, migration and proliferative capacities of HUVECs. Furthermore, bioinformatics analysis and luciferase assays revealed that EphrinA3 (EFNA3) was a direct target of miR-210-3p. Knockdown of miR-210-3p in N-EVs significantly impaired its ability to protect the heart after myocardial infarction. Altogether, these results indicated that N-EVs promoted the infarct healing through improvement of angiogenesis by miR-210-3p via targeting the EFNA3. Graphical Abstract Created with Biorender.com.

CRISPR/Cas9-based point-of-care lateral flow biosensor with improved performance for rapid and robust detection of Mycoplasma pneumonia - Rong Zhu; Han Jiang; Chaoyou Li; Yan Li; Min Peng; Junfeng Wang; Qian Wu; Chao Yan; Qingli Bo; Jie Wang; Chenlin Shen; Panzhu Qin (Analytica Chimica Acta, 2023)

Orange protein (DbOR) from the salt-tolerant green alga Dunaliella bardawil mediates photosynthesis against heat stress via interacting with DbPsbP1 - Ming-Hua Liang; Jv-Liang Dai; Shan-Rong Xie; Jing-Xuan Wu; Hao-Hong Chen; Jian-Guo Jiang (Algal Research, 2023)

3D Finite Element Model of Human Ear with 3-Chamber Spiral Cochlea for Blast Wave Transmission from the Ear Canal to Cochlea - John J. Bradshaw; Marcus A. Brown; Shangyuan Jiang; Rong Z. Gan (Annals of Biomedical Engineering, 2023)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Four new phenolic glycosides from Dobinea delavayi - Xiu-Rong Wu; Li-Juan Lang; Yi Shen; Xiang Dong; Chao-Jiang Xiao; Bei Jiang (Natural Product Research, 2023)

Changes of dissolved organic matter fractions and formation of oxidation byproducts during electrochemical treatment of landfill leachates: Development of spectroscopic indicators for process optimization - Bi-Cun Jiang; Ye-Chao Tian; Ai-Min Li; Yu-Ze Han; Ze-Tao Wu; Chang Lu; Hai-Ou Song; Rong Ji; Wen-Tao Li; Gregory V. Korshin (Water Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Amycolatolides A and B: Two new secondary metabolites from the lichen-derived actinomycete Amycolatopsis sp. YIM 130923 - Qing-Rong Yang; Yi Jiang; Chuan-Sheng Liu; Tang-Chang Xu; Rong Huang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Social environments still matter: The role of physical and social environments in place attachment in a transitional city, Guangzhou, China - Jiang Chang; Zihan Lin; Igor Vojnovic; Jiaguo Qi; Rong Wu; Dixiang Xie (Landscape and Urban Planning, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

A machine learning based approach for estimating site-specific partition coefficient Kd of organic compounds: Application to nonionic pesticides - Wankai Ma; Meie Wang; Rong Jiang; Weiping Chen (Environmental Pollution, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Neoproterozoic tungsten mineralization: Geology, chronology, and genesis of the Huashandong W deposit in northwestern Jiangxi, South China - Xu-Dong Huang; Di Huang; Jian-Jun Lu; Rong-Qing Zhang; Dong-Sheng Ma; Yao-Hui Jiang; Hao-Wen Chen; Jin-Xian Liu (Mineralium Deposita, 2023)

Identification of a novel eighteen-gene signature of recurrent metastasis neuroblastoma - Shufan Zhang; Rong Jiang; Manqiu Yang; Tao Wang; Hui Chen; Yifan Shi; Wei Liu; Moli Huang (Journal of Molecular Medicine, 2023)

Retraction Note: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2023)

High-throughput data on circular RNA reveal novel insights into chronic glomerulonephritis - Ya-chen Gao; Nan-nan Jiang; Xiu-juan Qin; Hui Jiang; Liang-bing Wei; Jia-rong Gao (Genes & Genomics, 2023)

Study of coexisting upstream solitary wave packet and downstream wakes induced by Diaoyu Dao and its affiliated islands detected by satellite sun glitter - Lina Cai; Xiaoqi Jiang; Xiaojun Yan; Yan Bai; Jianqiang Liu; Menghan Yu; Rong Tang; Jingjing Jiang (Acta Oceanologica Sinica, 2023)

Does Accountability Audit of Natural resources promote green innovation in heavily polluting enterprises? Evidence from China - Cailou Jiang; Rong Liu; Jie Han (Environment, Development and Sustainability, 2023)

Site-specific ecological effect assessment at community level for polymetallic contaminated soil - Rong Jiang; Meie Wang; Tian Xie; Weiping Chen (Journal of Hazardous Materials, 2023)

Flexible three-dimensional covalent organic frameworks for ultra-fast and selective extraction of uranium via hydrophilic engineering - Xiao-Juan Chen; Cheng-Rong Zhang; Xin Liu; Jia-Xin Qi; Wei Jiang; Shun-Mo Yi; Cheng-Peng Niu; Yuan-Jun Cai; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Evaluation of moisture migration characteristics of permeable asphalt pavement: Field research - Rong Lu; Wei Jiang; Jingjing Xiao; Dongdong Yuan; Yupeng Li; Yukai Hou; Congcong Liu (Journal of Environmental Management, 2023)

Lipid metabolic characteristics and marker compounds of ripened Pu-erh tea during pile fermentation revealed by LC-MS-based lipidomics - Jia Li; Haibo Yuan; Yuting Rong; Michael C. Qian; Fuqiao Liu; Jinjie Hua; Qinghua Zhou; Yuliang Deng; Jun Zeng; Yongwen Jiang (Food Chemistry, 2023)

Dorsal root ganglia P2X4 and P2X7 receptors contribute to diabetes-induced hyperalgesia and the downregulation of electroacupuncture on P2X4 and P2X7 - Qun-qi Hu; Xiao-fen He; Yi-qi Ma; Li-qian Ma; Si-ying Qu; Han-zhi Wang; Yu-rong Kang; Lu-hang Chen; Xiang Li; Bo-yu Liu; Xiao-mei Shao; Jun-fan Fang; et al. (Purinergic Signalling, 2023)

Inhibition of phosphorylated calcium/calmodulin-dependent protein kinase IIα relieves streptozotocin-induced diabetic neuropathic pain through regulation of P2X3 receptor in dorsal root ganglia - Xiao-fen He; Yu-rong Kang; Xue-yu Fei; Lu-hang Chen; Xiang Li; Yi-qi Ma; Qun-qi Hu; Si-ying Qu; Han-zhi Wang; Xiao-mei Shao; Bo-yi Liu; Yi-Liang; et al. (Purinergic Signalling, 2023)
Diabetic neuropathic pain (DNP) is frequent among patients with diabetes. We previously showed that P2X3 upregulation in dorsal root ganglia (DRG) plays a role in streptozotocin (STZ)-induced DNP but the underlying mechanism is unclear. Here, a rat model of DNP was established by a single injection of STZ (65 mg/kg). Fasting blood glucose was significantly elevated from the 1 st to 3 rd week. Paw withdrawal thresholds (PWTs) and paw withdrawal latencies (PWLs) in diabetic rats significantly reduced from the 2 nd to 3 rd week. Western blot analysis revealed that elevated p-CaMKIIα levels in the DRG of DNP rats were accompanied by pain-associated behaviors while CaMKIIα levels were unchanged. Immunofluorescence revealed significant increase in the proportion of p-CaMKIIα immune positive DRG neurons (stained with NeuN) in the 2 nd and 3 rd week and p-CaMKIIα was co-expressed with P2X3 in DNP rats. KN93, a CaMKII antagonist, significantly reduce mechanical hyperalgesia and thermal hyperalgesia and these effects varied dose-dependently, and suppressed p-CaMKIIα and P2X3 upregulation in the DRGs of DNP rats. These results revealed that the p-CaMKIIα upregulation in DRG is involved in DNP, which possibly mediated P2X3 upregulation, indicating CaMKIIα may be an effective pharmacological target for DNP management.

Erythropoietin promotes energy metabolism to improve LPS-induced injury in HK-2 cells via SIRT1/PGC1-α pathway - Kan Li; Li Gao; Sen Zhou; Yan-Rong Ma; Xiao Xiao; Qian Jiang; Zhi-Hong Kang; Ming-Long Liu; Tian-Xi Liu (Molecular and Cellular Biochemistry, 2023)

Extended seasonal prediction of spring precipitation over the Upper Colorado River Basin - Siyu Zhao; Rong Fu; Michael L. Anderson; Sudip Chakraborty; Jonathan H. Jiang; Hui Su; Yu Gu (Climate Dynamics, 2023)
This study provides extended seasonal predictions for the Upper Colorado River Basin (UCRB) precipitation in boreal spring using an artificial neural network (ANN) model and a stepwise linear regression model, respectively. Sea surface temperature (SST) predictors are developed taking advantage of the correlation between the precipitation and SST over three ocean basins. The extratropical North Pacific has a higher correlation with the UCRB spring precipitation than the tropical Pacific and North Atlantic. For the ANN model, the Pearson correlation coefficient between the observed and predicted precipitation exceeds 0.45 ( p -value < 0.01) for a lead time of 12 months. The mean absolute percentage error (MAPE) is below 20% and the Heidke skill score (HSS) is above 50%. Such long-lead prediction skill is probably due to the UCRB soil moisture bridging the SST and precipitation. The stepwise linear regression model shows similar prediction skills to those of ANN. Both models show prediction skills superior to those of an autoregression model (correlation < 0.10) that represents the baseline prediction skill and those of three of the North American Multi-Model Ensemble (NMME) forecast models. The three NMME models exhibit different skills in predicting the precipitation, with the best skills of the correlation ~ 0.40, MAPE < 25%, and HSS > 40% for lead times less than 8 months. This study highlights the advantage of oceanic climate signals in extended seasonal predictions for the UCRB spring precipitation and supports the improvement of the UCRB streamflow prediction and related water resource decisions.

Blasting dust diffuse characteristics of spiral tunnel and dust distribution model: similar experiment and numerical modeling - Rong Liu; Deyi Jiang; Jie Chen; Song Ren; Jinyang Fan; Yi He (Environmental Science and Pollution Research, 2023)

CH4 and CO2 emissions in water networks of rice cultivation regions - Ouping Deng; Jiangyou Ran; Xuesong Gao; Xiangjun Lin; Ting Lan; Ling Luo; Yalan Xiong; Jiang Liu; Dinghua Ou; Jianbo Fei; Rong Huang (Environmental Research, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Rapid, linear, and highly reliable structural-color switching enabled by thermal regulation of chiral nematic mesophases - Dong Li; Rong-Rong Jiang; Si-Kai Chen; Jia-Min Wu; Xiu Dong; Xiu-Li Wang; Yu-Zhong Wang; Fei Song (Chemical Engineering Journal, 2023)

Community succession of microbial populations related to C N P S biological transformations regulates product maturity during cow-manure-driven composting - Xin Liu; Xiangmin Rong; Junyan Yang; Han Li; Wang Hu; Yong Yang; Guoliang Jiang; Rusheng Xiao; Xingxiang Deng; Guixian Xie; Gongwen Luo; Jiachao Zhang (Bioresource Technology, 2023)

An integrated process for co-producing fermentable sugars and xylonate from sugarcane bagasse based on xylonic acid assisted pretreatment - Zhen Zhu; Rong Huang; Shuangquan Yao; Yiruo Liu; Qibo Zhang; Xin Zhou; Kankan Jiang (Bioresource Technology, 2023)

Short-Term Limited Water Irrigation Influences the Photosynthetic Pigments, Enzymatic and Non-Enzymatic Activities in Saccharum spontaneum L. at Vegetative Stage - Zhi-Nian Deng; Hai-Rong Huang; Cheng-Mei Huang; Krishan K. Verma; Hai-Bin Luo; Sheng-Li Jiang; Yi-Jie Li; Hui-Qing Cao; Kai-Chao Wu; Lin Xu (Sugar Tech, 2023)

Elevated Levels of Naturally-Occurring Autoantibodies Against the Extracellular Domain of p75NTR Aggravate the Pathology of Alzheimer’s Disease - Chen-Yang He; Ding-Yuan Tian; Si-Han Chen; Wang-Sheng Jin; Yuan Cheng; Jia-Yan Xin; Wei-Wei Li; Gui-Hua Zeng; Cheng-Rong Tan; Jie-Ming Jian; Dong-Yu Fan; Jun-Rong Ren; et al. (Neuroscience Bulletin, 2023)

A near-infrared fluorescent probe for monitoring abnormal mitochondrial viscosity in cancer and fatty-liver mice model - Jing-Jing Chao; Hui Zhang; Zhi-Qing Wang; Qiao-Rong Liu; Guo-Jiang Mao; Dong-Hua Chen; Chun-Yan Li (Analytica Chimica Acta, 2023)

A new acylated iridoid and other chemical constituents from Valeriana jatamansi and their biological activities - Yun Wang; Dao-Qun Shi; Na Jiang; Kai-Rui Rao; Shi-Xian Zhang; Dan Liu; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2023)

Environmental protection tax and the labor income share of companies: evidence from a quasi-natural experiment in China - Qian Xiao; Yaohui Jiang; Rong Li; Sidi Xiao (Environmental Science and Pollution Research, 2023)

Optimization and design of pre-reinforcement for a subsea tunnel crossing a fault fracture zone - Yang Zheng; Ke Wu; Yujing Jiang; Rong Chen; Jingchuan Duan (Marine Georesources & Geotechnology, 2023)

Nondestructive and rapid method for sex identification of the tropical sea cucumber Holothuria scabra by anal swab sampling - Zixuan E; Chuhang Cheng; Feifei Wu; Chunhua Ren; Rong Chen; Yingzhu Rao; Bo Ma; Xiao Jiang; Peng Luo; Xiaomin Li; Xin Zhang; Fajun Jiang; et al. (Aquaculture, 2023)

Moderate physical activity against effects of short-term PM2.5 exposure on BP via myokines-induced inflammation - Mengqi Wu; Yaxian Pang; Meiyu Chen; Lipeng Li; Lina Yan; Jie Ning; Qingping Liu; Yaling Zhang; Tao Jiang; Aijuan Kang; Xiaoyan Huang; Wentao Hu; et al. (Science of The Total Environment, 2023)

Enhanced preservation effects of clove (Syzygium aromaticum) essential oil on the processing of Chinese bacon (preserved meat products) by beta cyclodextrin metal organic frameworks (β-CD-MOFs) - Ying Wang; Yi-Tong Du; Wan-Yu Xue; Liang Wang; Rong Li; Zi-Tao Jiang; Shu-Hua Tang; Jin Tan (Meat Science, 2023)

Experimental study on the temperature-regulating function of road thermoelectric generator system - Dongdong Yuan; Wei Jiang; Jingjing Xiao; Xianwu Ling; Yufei Zhang; Rong Lu (Journal of Cleaner Production, 2023)

Modelling the impacts of inhibitors and fertilizer placement on maize yield and ammonia, nitrous oxide and nitrate leaching losses in southwestern Ontario, Canada - Rong Jiang; Jingyi Yang; Craig F. Drury; Brian B. Grant; Ward N. Smith; Wentian He; Daniel W. Reynolds; Ping He (Journal of Cleaner Production, 2023)

Effects of substituting municipal waste incineration fly ash for lime on generating a bonding phase during the sintering process - Zhenqiang Jiang; Kai Dong; Hongyang Wang; Yun Zhou; Bohan Tian; Xin Li; Rong Zhu (Journal of Cleaner Production, 2023)

Modelling maize yield, soil nitrogen balance and organic carbon changes under long-term fertilization in Northeast China - Jingmin Yang; Rong Jiang; Hongwei Zhang; Wentian He; Jingyi Yang; Ping He (Journal of Environmental Management, 2023)

Microwave discharge for rapid introduction of bimetallic-synergistic configuration to conductive catecholate toward long-term supercapacitor - Huiyu Jiang; Jinglin Xian; Rong Hu; Shiyun Mi; Liyun Wei; Guangyu Fang; Zhiao Wu; Siqi Xu; Mingzhao Fan; Kaisi Liu; Huimin Yu; Weilin Xu; et al. (Chemical Engineering Journal, 2023)

Sn2P2S6: A lead-free reversible thermochromic ferroelectric with high near-infrared reflectance - Meixia Wu; Xiao Zhou; Xihui Liang; Yifeng Han; Yonghong Li; Xingan Jiang; Xueyun Wang; Yisheng Chai; Xiang Zhou; Hui Yang; Dan Lin; Ping Xu; et al. (Chemical Engineering Journal, 2023)

Coassisted carbonization with HCOOK/(HCOO)2Ca for the fabrication of bamboo-derived oxygen-doped porous carbons exhibiting high-performance sorption of diethyl phthalate from aqueous solutions - Fei Gu; Rongting Ji; Qian Sun; Shengcun Chen; Rong Bai; Yuying Shen; Xinran Liu; Yang Song; Jiangang Han; Xin Jiang; Hu Cheng; Jianming Xue (Bioresource Technology, 2023)

The genomic, transcriptomic, and immunological profiles of perineural invasion in pancreatic ductal adenocarcinoma - Shu-Heng Jiang; Rong-Kun Li; De-Jun Liu; Jun-Li Xue; Min-Hao Yu; Shan Zhang; Li-Min Liu; Jun-Feng Zhang; Rong Hua; Yong-Wei Sun; Xu Wang; Qin Yang; et al. (Science China Life Sciences, 2023)

Dysregulation of Circulatory Levels of lncRNAs in Parkinson’s Disease - Ting Huang; Jin-Ying Zhao; Rong-Rong Pan; Teng Jiang; Xin-Xin Fu; Qing Huang; Xi-Xi Wang; Peng-Yu Gong; You-Yong Tian; Ying-Dong Zhang (Molecular Neurobiology, 2023)

Quality improvement of the thermal gel of horse mackerel by sodium citrate and its inhibition of the insoluble metalloproteinase - Yan-Rong Jiang; Asami Yoshida; Megumi Ohta; Yi-Li Gao; Erika Noguchi; Koichi Kuwahara; Kenji Hara; Kiyoshi Osatomi (Fisheries Science, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Influence of different soil properties on the failure behavior of deposit slope under earthquake after rainfall - Bing Yang; Jiang-rong Hou; Zi-hong Zhou; Jin-cheng Gou (Journal of Mountain Science, 2023)

Hominibacterium faecale gen. nov., sp. nov., an anaerobic l-arginine-degrading bacterium isolated from human feces - Noori Borhanudin; Min Yang; Andrei V. Chaplin; Jiang Li; Qiong Wang; Li-rong Dai; Ke-jia Wu; Shi-chun Ma; Boris A. Efimov; Lei Cheng (Archives of Microbiology, 2023)

Dibenzofurans from Crataegus oresbia and their lipid-lowering activity - Ying Wang; Li-Juan Lang; Qi-Jie Zhu; Xiu-Rong Wu; Lei Shen; Bei Jiang; Chao-Jiang Xiao (Natural Product Research, 2022)

Lead absorption capacity in different parts of plants and its influencing factors: a systematic review and meta-analysis - Lulu Jia; Hongkun Ma; Yue Guan; Lina Zou; Lan Jiang; Yongzheng Hang; Xiaoyan feng; Xiaowei Ren; Yuting Tian; Hongzhi Pan; Shengzhong Rong (Environmental Science and Pollution Research, 2022)

Manganese addition accelerates litter decomposition and alters litter mixing effects in the late stage in subtropical plantations of southern China - Pan-Pan Wu; Ling-Xin Jiang; Yan Zhang; Qi-Han Tu; Rong Mao (Plant and Soil, 2022)

Effect of Cu2+ on the Laccase-Inducted Formation of Non-Extractable Residues of Tetrabromobisphenol A in Humic Acids - Yue Zhou; Bingqi Jiang; Yongfeng Wang; Feifei Sun; Rong Ji (Bulletin of Environmental Contamination and Toxicology, 2022)

Neural mechanisms underlying empathy during alcohol abstinence: evidence from connectome-based predictive modeling - Guanzhong Yao; Luqing Wei; Ting Jiang; Hui Dong; Chris Baeken; Guo-Rong Wu (Brain Imaging and Behavior, 2022)

Establishment of a novel myocarditis mouse model based on cyclosporine A - Tian Hao Zhao; Yi Xuan Jiang; Kai Qin Chen; Dan Qiu; Yan Zhe Xu; Chun Ye; Ting Ren; Bo Zhang; Bin Dai; Jue Hu; Jun Lu; Fang Liang Zhou; et al. (Genes & Genomics, 2022)

The spatial-temporal consistency of chlorophyll-a and fishery resources in the water of the Zhoushan archipelago revealed by high resolution remote sensing - Lina Cai; Rong Tang; Xiaojun Yan; Yongdong Zhou; Jingjing Jiang; Menghan Yu (Frontiers in Marine Science, 2022)
Details of the chlorophyll- a (Chl- a ) distribution in the water of the Zhoushan archipelago were analyzed based on data from the panchromatic multispectral sensor (PMS) of the GaoFen-6 (GF-6). A new Chl- a inversion model was built using in-situ Chl- a and the green-red bands of the 2 m spatial resolution GF-6/PMS image. Combined with fishery data, the relationship between Chl- a concentration and fish resources were revealed. The results show that: (1) High Chl- a concentration area was mainly concentrated in the nearshore intensive islands waters, and Chl- a concentration changes obviously with the change of tidal currents. Chl- a concentration around islands increases, especially downstream of islands. Seasonally, Chl- a concentration is higher in spring and summer, lower in autumn, and lowest in winter. (2) The change of fish eggs and larvae in the water of the Zhoushan archipelago shows consistency with the spatial distribution and seasonal variation of Chl- a . (3) The interaction between tidal currents and islands results in the diverse currents (upstream upwelling and downstream vortex currents) around the islands, promoting vertical water exchange and the uplifting of nutrients, resulting in a high overall Chl- a concentration in the waters around the islands. The diverse flow conditions, the ideal nutrient-rich environment, and the abundant phytoplankton attract a large number of fish to gather and breed in the waters around the islands. (4) Chl- a of intensive island waters is an essential indicator for fish spawning grounds.

Abscisic acid induces the expression of AsKIN during the recovery period of garlic cryopreservation - Xiaodong Xing; Min Liu; Fangling Jiang; Rong Zhou; Yunhe Bai; Hanyu Wei; Deng Zhang; Jingjing Wei; Zhen Wu (Plant Cell Reports, 2022)

Phosphorylation of Truncated Tau Promotes Abnormal Native Tau Pathology and Neurodegeneration - Longfei Li; Yanli Jiang; Gang Wu; Yacoubou Abdoul Razak Mahaman; Dan Ke; Qun Wang; Bin Zhang; Jian-Zhi Wang; Hong-Lian Li; Rong Liu; Xiaochuan Wang (Molecular Neurobiology, 2022)

Naturally-Occurring Antibodies Against Bim are Decreased in Alzheimer’s Disease and Attenuate AD-type Pathology in a Mouse Model - Jie-Ming Jian; Dong-Yu Fan; Ding-Yuan Tian; Yuan Cheng; Pu-Yang Sun; Cheng-Rong Tan; Gui-Hua Zeng; Chen-Yang He; Ye-Ran Wang; Jie Zhu; Xiu-Qing Yao; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2022)

MicroRNA-339-5p inhibits lipopolysaccharide-induced rat mesangial cells by regulating the Syk/Ras/c-Fos pathway - Jia Rong Gao; Miao Miao Shi; Hui Jiang; Xiao Li Zhu; Liang Bing Wei; Xiu Juan Qin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Coffin-Siris syndrome in two chinese patients with novel pathogenic variants of ARID1A and SMARCA4 - Mingjie Liu; Linlin Wan; Chunrong Wang; Hongyu Yuan; Yun Peng; Na Wan; Zhichao Tang; Xinrong Yuan; Daji Chen; Zhe Long; Yuting Shi; Rong Qiu; et al. (Genes & Genomics, 2022)

Global evaluation of inhibitor impacts on ammonia and nitrous oxide emissions from agricultural soils: A meta‐analysis - Daijia Fan; Wentian He; Ward N. Smith; Craig F. Drury; Rong Jiang; Brian B. Grant; Yaoyao Shi; Daping Song; Yanhua Chen; Xuexia Wang; Ping He; Guoyuan Zou (Global Change Biology, 2022)
Inhibitors are widely considered an efficient tool for reducing nitrogen (N) loss and improving N use efficiency, but their effectiveness is highly variable across agroecosystems. In this study, we synthesized 182 studies (222 sites) worldwide to evaluate the impacts of inhibitors (urease inhibitors [UI], nitrification inhibitors [NI] and combined inhibitors) on crop yields and gaseous N loss (ammonia [NH 3 ] and nitrous oxide [N 2 O] emissions) and explored their responses to different management and environmental factors including inhibitor application timing, fertilization regime, cropping system, water management, soil properties and climatic conditions using subgroup meta‐analysis, meta‐regression and multivariate analyses. The UI were most effective in enhancing crop yields (by 5%) and reducing NH 3 volatilization (by 51%), whereas NI were most effective at reducing N 2 O emissions (by 49%). The application of UI mitigates NH 3 loss and increases crop yields especially in high NH 3 ‐N loss scenarios, whereas NI application would minimize the net N 2 O emissions and the resultant environmental impacts especially in low NH 3 ‐N loss scenarios. Alternatively, the combined application of UI and NI enables producers to balance crop production and environmental conservation goals without pollution tradeoffs. The inhibitor efficacy for decreasing gaseous N loss was dependent upon soil and climatic conditions and management practices. Notably, both meta‐regression and multivariate analyses suggest that inhibitors provide a greater opportunity for reducing fertilizer N inputs in high‐N‐surplus systems and presumably favor crop yield enhancement under soil N deficiency situations. The pursuit of an improved understanding of the interactions between plant‐soil‐climate‐management systems and different types of inhibitors should continue to optimize the effectiveness of inhibitors for reducing environmental losses while increasing productivity.

Geochronology and geochemistry of the felsic-intermediate dikes from Xiangshan uranium ore field, South China: Implications for petrogenesis, tectonic setting and uranium mineralization - Yong-Jian Wang; Jiang-Tao Nie; Jin-Rong Lin; Hong-Zuo Wang (Mineralogy and Petrology, 2022)

NGF/TrkA promotes the vitality, migration and adhesion of bone marrow stromal cells in hypoxia by regulating the Nrf2 pathway - Cui-Ni Fang; Hai-Qun Tan; Ao-Bo Song; Ni Jiang; Qian-Rong Liu; Tao Song (Metabolic Brain Disease, 2022)

Progranulin, a moderator of estrogen/estrogen receptor α binding, regulates bone homeostasis through PERK/p-eIF2 signaling pathway - Yuyou Yang; Naibo Feng; Li liang; Rong Jiang; Yiming Pan; Nana Geng; Mengtian Fan; Xiaoli Li; Fengjin Guo (Journal of Molecular Medicine, 2022)

Recognition of the Multi-class Schizophrenia Based on the Resting-State EEG Network Topology - Fali Li; Lin Jiang; Yuanyuan Liao; Cunbo Li; Qi Zhang; Shu Zhang; Yangsong Zhang; Li Kang; Rong Li; Dezhong Yao; Gang Yin; Peng Xu; et al. (Brain Topography, 2022)

Associations Between Fundus Types and Clinical Manifestations in Patients with RDH12 Gene Mutations - Jing Jin; Liang Liang; Kun Jin; Hai-jiang Zhang; Rong Liu; Yin Shen (Brain Topography, 2022)

Identification of the Largest SCA36 Pedigree in Asia: with Multimodel Neuroimaging Evaluation for the First Time - Yue Xie; Zhao Chen; Zhe Long; Rui-Ting Chen; Yi-Zheng Jiang; Ming-Jie Liu; Lin-Liu Peng; Hui-Rong Peng; Na Wan; Guangdong Zou; Chun-Rong Wang; Yu-Ting Shi; et al. (The Cerebellum, 2022)

Four new triterpene glucosides from Salacia cochinchinensis Lour - Lu Gao; Li-Kun Duan; Jin-E Feng; Yun-Tao Jiang; Jun Gao; Jun-Ting Fan; Rong Dai; Zhi-Yong Jiang (Natural Product Research, 2022)

Dominant species and evenness level co-regulate litter mixture decomposition in a boreal peatland - Xinhou Zhang; Yuanhang Zhang; Shuangshuang Jiang; Changchun Song; Jinbo Zhang; Rong Mao (Plant and Soil, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Three new C 21 steroidal glycosides isolated from Metaplexis japonica and their potential inhibitory effects on tyrosine protein kinases - Xu Wang; Qing-Yun Ma; Chen Liu; Jia Yang; Qing-Tao Lv; Zhen-Hua Tian; Hai-Qiang Jiang; Rong Rong (Natural Product Research, 2022)

Quinolizidine alkaloids from the roots of Sophora flavescens - Jian-Chun Li; Zhi-Jun Zhang; Dan Liu; Ming-Yan Jiang; Rong-Tao Li; Hong-Mei Li (Natural Product Research, 2022)

Damage Evaluation and Statistic Constitutive Model of High-Temperature Granites Subjected to Liquid Nitrogen Cold Shock - Zhiheng Chen; Song Sha; Lida Xu; Junsong Quan; Guan Rong; Maiyong Jiang (Rock Mechanics and Rock Engineering, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

The Predictability of Ocean Environments that Contributed to the 2020/21 Extreme Cold Events in China: 2020/21 La Niña and 2020 Arctic Sea Ice Loss - Fei Zheng; Ji-Ping Liu; Xiang-Hui Fang; Mi-Rong Song; Chao-Yuan Yang; Yuan Yuan; Ke-Xin Li; Ji Wang; Jiang Zhu (Advances in Atmospheric Sciences, 2022)
Several consecutive extreme cold events impacted China during the first half of winter 2020/21, breaking the low-temperature records in many cities. How to make accurate climate predictions of extreme cold events is still an urgent issue. The synergistic effect of the warm Arctic and cold tropical Pacific has been demonstrated to intensify the intrusions of cold air from polar regions into middle-high latitudes, further influencing the cold conditions in China. However, climate models failed to predict these two ocean environments at expected lead times. Most seasonal climate forecasts only predicted the 2020/21 La Niña after the signal had already become apparent and significantly underestimated the observed Arctic sea ice loss in autumn 2020 with a 1–2 month advancement. In this work, the corresponding physical factors that may help improve the accuracy of seasonal climate predictions are further explored. For the 2020/21 La Niña prediction, through sensitivity experiments involving different atmospheric–oceanic initial conditions, the predominant southeasterly wind anomalies over the equatorial Pacific in spring of 2020 are diagnosed to play an irreplaceable role in triggering this cold event. A reasonable inclusion of atmospheric surface winds into the initialization will help the model predict La Niña development from the early spring of 2020. For predicting the Arctic sea ice loss in autumn 2020, an anomalously cyclonic circulation from the central Arctic Ocean predicted by the model, which swept abnormally hot air over Siberia into the Arctic Ocean, is recognized as an important contributor to successfully predicting the minimum Arctic sea ice extent.

Polysaccharide Krestin Prevents Alzheimer’s Disease-type Pathology and Cognitive Deficits by Enhancing Monocyte Amyloid-β Processing - Si-Han Chen; Chen-Yang He; Ying-Ying Shen; Gui-Hua Zeng; Ding-Yuan Tian; Yuan Cheng; Man-Yu Xu; Dong-Yu Fan; Cheng-Rong Tan; An-Yu Shi; Xian-Le Bu; Yan-Jiang Wang (Neuroscience Bulletin, 2022)

Activation of Autophagy Ameliorates Age-Related Neurogenesis Decline and Neurodysfunction in Adult Mice - Na Yang; Xueqin Liu; Xiaojie Niu; Xiaoqiang Wang; Rong Jiang; Na Yuan; Jianrong Wang; Chengwu Zhang; Kah-Leong Lim; Li Lu (Stem Cell Reviews and Reports, 2022)

Correction to: A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2022)

Control of chronic obstructive pulmonary disease in urban populations: findings from a cross-sectional prevalence survey in Shenzhen, China - Le-Cai Ji; Jin-Feng Yin; Chun-Rong Lu; Hong-Yun Guan; Wei-Guo Tan; Ling-Wei Wang; Qi Jiang (Environmental Science and Pollution Research, 2022)

Apatite chemistry as a petrogenetic–metallogenic indicator for skarn ore-related granitoids: an example from the Daye Fe–Cu–(Au–Mo–W) district, Eastern China - Run-Jie Zhou; Guang Wen; Jian-Wei Li; Shao-Yong Jiang; Hao Hu; Xiao-Dong Deng; Xin-Fu Zhao; Dai-Rong Yan; Ke-Tao Wei; Heng-An Cai; Shi-Chao Shang; Bai-Cun Li; et al. (Contributions to Mineralogy and Petrology, 2022)

Detection of functional and structural brain alterations in female schizophrenia using elastic net logistic regression - Ying Wu; Ping Ren; Rong Chen; Hong Xu; Jianxing Xu; Lin Zeng; Donghui Wu; Wentao Jiang; NianSheng Tang; Xia Liu (Brain Imaging and Behavior, 2022)
Neuroimaging technique is a powerful tool to characterize the abnormality of brain networks in schizophrenia. However, the neurophysiological substrate of schizophrenia is still unclear. Here we investigated the patterns of brain functional and structural changes in female patients with schizophrenia using elastic net logistic regression analysis of resting-state functional magnetic resonance imaging data. Data from 52 participants (25 female schizophrenia patients and 27 healthy controls) were obtained. Using an elastic net penalty, the brain regions most relevant to schizophrenia pathology were defined in the models using the amplitude of low-frequency fluctuations (ALFF) and gray matter, respectively. The receiver operating characteristic analysis showed reliable classification accuracy with 85.7% in ALFF analysis, and 77.1% in gray matter analysis. Notably, our results showed eight common regions between the ALFF and gray matter analyses, including the Frontal-Inf-Orb-R, Rolandic-Oper-R, Olfactory-R, Angular-L, Precuneus-L, Precuenus-R, Heschl-L, and Temporal-Pole-Mid-R. In addition, the severity of symptoms was found positively associated with the ALFF within the Rolandic-Oper-R and Frontal-Inf-Orb-R. Our findings indicated that elastic net logistic regression could be a useful tool to identify the characteristics of schizophrenia -related brain deterioration, which provides novel insights into schizophrenia diagnosis and prediction.

The Sources and Burial of Marine Organic Carbon in the Eastern China Marginal Seas - Yali Cao; Rong Bi; Xingchen Wang; Xi Chen; Jingwen Hu; Yaoyao Wang; Yiqing Jiang; Hailong Zhang; Lei Xing; Meixun Zhao (Frontiers in Marine Science, 2022)
The ecological functions and biogeochemical processes of continental marginal seas are important for the global carbon cycle. In the eastern China marginal seas (ECMS), phytoplankton productivity has increased significantly in recent decades, but the sources and burial processes of marine organic carbon (OC) remain under-studied. We analyzed the contents of marine lipid biomarkers (brassicasterol, dinosterol, and C 37 alkenones) in surface suspended particles obtained from seven cruises between 2010 and 2015, and in surface sediments from eight cruises between 2006 and 2012 in the ECMS, to estimate marine OC sources and burial. The correlations between lipid biomarkers and environmental factors were quantified to reveal controlling factors. The study area was divided into four regions according to cluster analysis conducted based on sediment parameters. Our results showed that the concentrations of marine lipid biomarkers in surface water were high near large estuaries such as the Changjiang River Estuary and the Yellow River Estuary, but those in surface sediments were high in mud areas. Nutrient concentration was a key factor controlling phytoplankton biomass in surface water, with high nutrients enhancing the growth of diatoms and dinoflagellates, while haptophytes were more abundant in low-nutrient, high-salinity and cold environments. High marine OC contents calculated from total OC δ 13 C were mainly associated with fine sediments transported by coastal currents, and finally deposited in mud areas. The proto-burial efficiency of marine OC in the ECMS (7–19%) was markedly higher than the mean value in global marginal seas, with high values being located in the western coast of the ECMS. The proto-burial efficiency of total marine lipid biomarkers (6–24%) was quantified for the first time in our study, with overall values and spatial patterns similar to that of marine OC. A key parameter for marine OC and marine biomarker proto-burial efficiency was sediment grain size. The smaller the sediment grain size was, the better the marine OC and marine biomarker were retained. Our study provides an important basis to elucidate spatial distribution patterns and forcing mechanisms of marine OC in surface water (production process) and surface sediments (burial process), and to estimate carbon budgets in large marginal seas.

Inclusion of Ecological Water Requirements in Optimization of Water Resource Allocation Under Changing Climatic Conditions - Wencong Yue; Zhongqi Liu; Meirong Su; Meng Xu; Qiangqiang Rong; Chao Xu; Zhenkun Tan; Xuming Jiang; Zhixin Su; Yanpeng Cai (Water Resources Management, 2022)

Protease-activated receptor 2 activation induces behavioural changes associated with depression-like behaviour through microglial-independent modulation of inflammatory cytokines - Serge Moudio; Ashleigh Willis; Karolina Pytka; Roua Abulkassim; Ros R. Brett; Jack F. Webster; Christian Wozny; Mark Barbour; Hui-Rong Jiang; David G. Watson; Josie C. van Kralingen; Scott M. MacKenzie; et al. (Psychopharmacology, 2022)
Rationale Major depressive disorder (MDD) is a leading cause of disability worldwide but currently prescribed treatments do not adequately ameliorate the disorder in a significant portion of patients. Hence, a better appreciation of its aetiology may lead to the development of novel therapies. Objectives In the present study, we have built on our previous findings indicating a role for protease-activated receptor-2 (PAR2) in sickness behaviour to determine whether the PAR2 activator, AC264613, induces behavioural changes similar to those observed in depression-like behaviour. Methods AC264613-induced behavioural changes were examined using the open field test (OFT), sucrose preference test (SPT), elevated plus maze (EPM), and novel object recognition test (NOR). Whole-cell patch clamping was used to investigate the effects of PAR2 activation in the lateral habenula with peripheral and central cytokine levels determined using ELISA and quantitative PCR. Results Using a blood–brain barrier (BBB) permeable PAR2 activator, we reveal that AC-264613 (AC) injection leads to reduced locomotor activity and sucrose preference in mice but is without effect in anxiety and memory-related tasks. In addition, we show that AC injection leads to elevated blood sera IL-6 levels and altered cytokine mRNA expression within the brain. However, neither microglia nor peripheral lymphocytes are the source of these altered cytokine profiles. Conclusions These data reveal that PAR2 activation results in behavioural changes often associated with depression-like behaviour and an inflammatory profile that resembles that seen in patients with MDD and therefore PAR2 may be a target for novel antidepressant therapies.

Effect of water level on dynamic compaction in silty ground of Yellow River alluvial plain - Kai Yao; Yu Rong; Zhanyong Yao; Changyuan Shi; Chenjun Yang; Luchuan Chen; Baoshuo Zhang; Hongguang Jiang (Arabian Journal of Geosciences, 2022)

Synthesis, characterization and antitumor mechanism investigation of ruthenium(II) polypyridyl complexes with artesunate moiety - Bi-Chun Chen; Jun-Jian Lu; Ning Jiang; Xiu-Rong Ma; Rong-Tao Li; Rui-Rong Ye (JBIC Journal of Biological Inorganic Chemistry, 2021)

Dietary pectin caused great changes in bile acid profiles of Pelteobagrus fulvidraco - Xiamin Cao; Shengjie Ren; Chunfang Cai; Qin Ni; Xinyue Li; Yunhe Meng; Zijing Meng; Ye Shi; Huangen Chen; Rong Jiang; Ping Wu; Yuantu Ye (Fish Physiology and Biochemistry, 2021)

A drug–biomarker interaction model to predict the key targets of Scutellaria barbata D. Don in adverse-risk acute myeloid leukaemia - Teng Wang; Chun-yi Lyu; Yue-hua Jiang; Xue-yan Dong; Yan Wang; Zong-hong Li; Jin-xin Wang; Rui-rong Xu (Molecular Diversity, 2021)

Molecular cloning of myosin chaperone uncoordinate-45B (UNC-45B) and its heat stress response in the muscle of Pacific bluefin tuna Thunnus orientalis - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Uno Yamashita; Yan-Rong Jiang; Xiao-Mi Sun; Kazuya Shirota; Yasuhiko Shiina; Kiyoshi Osatomi (Fisheries Science, 2021)

Analysis on improvement effect of subgrade by dynamic compaction - Hui Qi; Chenjun Yang; Chao Hu; Yu Rong; Zhanyong Yao; Hongguang Jiang; Kai Yao; Luchuan Chen; Hui Li; Xianfei Teng (Arabian Journal of Geosciences, 2021)

Circular RNA circ_Cabin1 promotes DNA damage in multiple mouse organs via inhibition of non-homologous end-joining repair upon PM2.5 exposure - Huixian Zeng; Meizhen Li; Qiuhan Hua; Yufei Liu; Yueting Shao; Qinqin Diao; Yihui Ling; Han Zhang; Miaoyun Qiu; Jialu Zhu; Xun Li; Rong Zhang; et al. (Archives of Toxicology, 2021)

Mystery of methamphetamine-induced autophagosome accumulation in hippocampal neurons: loss of syntaxin 17 in defects of dynein–dynactin driving and autophagosome–late endosome/lysosome fusion - Huaisha Xu; Yuanhui Zhu; Xufeng Chen; Tingyu Yang; Xi Wang; Xu Song; Xuexue Xie; Miaoyang Hu; Lei Jiang; Jie Cheng; Rong Gao; Jun Wang (Archives of Toxicology, 2021)

Activation of autophagy reverses gemcitabine-induced immune inhibition of RAW264.7 macrophages by promoting TNF-α, IL-6 and MHC-II expression - Shanshan Jiang; Rong Wang; Lu Han; Kudelaidi Kuerban; Li Ye; Shu Pan; Shengnan Li; Yongfang Yuan (Immunologic Research, 2021)
This research aims to investigate the effect of gemcitabine (GEM) on various activities and functions of macrophages. Phagocytosis, cell autophagy and reactive oxygen species (ROS) were analysed by laser scanning confocal microscope. The cell cycle status and major histocompatibility complex II (MHC-II) expression were examined by flow cytometry. Inflammatory cytokine secretion such as tumour necrosis factor α (TNF-α) and interleukin 6 (IL-6) was detected by Elisa assay. The expression of proteins was analysed by western blot method. The results revealed that GEM-induced immune inhibition of M1-type RAW264.7 macrophages activated by interferon-γ (IFN-γ) and lipopolysaccharide (LPS). We also found that GEM inhibited autophagy, as evidenced by the reduced formation of autophagosome-like vacuoles and autophagosomes. Further study showed that incubation of activated macrophages with the autophagy inhibitor 3-MA induced immune suppression. In contrast, treatment with the autophagy inducer trehalose (Tre) restored phagocytosis, TNF-α and IL-6 secretion, and MHC-II expression in GEM-induced immune-inhibited macrophages. GEM reduced immune effect of M1-type RAW264.7 macrophages via inhibiting TNF-α, IL-6 and MHC-II expression. Furthermore, activation of autophagy by Tre reversed GEM-induced immune inhibition of RAW264.7 macrophages.

Consuming Different Structural Parts of Bamboo Induce Gut Microbiome Changes in Captive Giant Pandas - Zheng Yan; Qin Xu; Walter H. Hsu; Stephan Schmitz Esser; James Ayala; Rong Hou; Ying Yao; Dandan Jiang; Shibin Yuan; Hairui Wang (Current Microbiology, 2021)
Giant pandas consume different structural parts of bamboo (shoots, leaves and culms) during different seasons. Previous research showed different bamboo parts have varying nutritional content and that a long-term diet consisting of a single part of bamboo resulted in remarkable metabolic changes within captive giant pandas. However, the effects on the gut microbiome of giant pandas, as a result of a single bamboo part diet, have not been investigated. Here, we evaluated the changes in gut microbial communities based on single bamboo part diets and their potential implications by using 16S rRNA gene-based amplicon sequencing and metagenome shotgun sequencing. We found that the composition and function of the gut microbiome from captive giant pandas fed exclusively culms were significantly different from that of individuals fed shoots or leaves. During the culm feeding period, the gut microbiome showed strongest digestive capabilities for cellulose, hemicellulose and starch, and had the highest potential abilities for the biosynthesis of bile acids, fatty acids and amino acids. This suggests the microbiome aids in breaking down culm, which is more difficult for giant pandas to digest, as a means to compensate for the nutrient poor content of the culm. Genes related to fatty acid metabolism and tricarboxylic acid cycle enzymes were more abundant during the leaf stage diet than that in the shoot and culm stages. Thus, the microbiome may help giant pandas, which typically have low lipase levels, with fat digestion. These results illustrate that adaptive changes in the gut microbiome community and function may be an important mechanism to aid giant panda digestion when consuming different structural parts of bamboo.

Oceanobacillus salinisoli sp. nov., a bacterium isolated from saline soil of Turpan city in Xinjiang province, north–west China - Wen-Yong Zhu; Li Yang; Zhou-Tian-Le Zhang; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Gang-Qiang Jiang; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2021)

Shrub encroachment balances soil organic carbon pool by increasing carbon recalcitrance in a temperate herbaceous wetland - Xinhou Zhang; Shuangshuang Jiang; Wei Jiang; Wenwen Tan; Rong Mao (Plant and Soil, 2021)

Differential responses of litter decomposition in the air and on the soil surface to shrub encroachment in a graminoid-dominated temperate wetland - Xinhou Zhang; Wei Jiang; Shuangshuang Jiang; Wenwen Tan; Rong Mao (Plant and Soil, 2021)

Small-sized extracellular vesicles (EVs) derived from acute myeloid leukemia bone marrow mesenchymal stem cells transfer miR-26a-5p to promote acute myeloid leukemia cell proliferation, migration, and invasion - Dexiang Ji; Yue He; Wei Lu; Yanyan Rong; Fei Li; Xianbao Huang; Ruibin Huang; Yanxia Jiang; Guoan Chen (Human Cell, 2021)

MiR-150-5p regulate T cell activation in severe aplastic anemia by targeting Bach2 - Yingmei Li; Jifeng Yu; Fang Wang; Rong Guo; Haizhou Xing; Yali Chen; Dandan Chen; Xinsheng Xie; Dingming Wan; Zhongxing Jiang (Cell and Tissue Research, 2021)

Haloechinothrix aidingensis sp. nov., an actinomycete isolated from salt lake in Xinjiang province, north-west China - Li Yang; Ya-Rong Kou; Tong-Wei Guan; Min Yin; Bing-Bing Liu; Yong-Jiang Shi; Wen-Yong Zhu; Shu-Kun Tang (Archives of Microbiology, 2021)

A native Trichoderma harzianum strain Th62 displays antagonistic activities against phytopathogenic fungi and promotes the growth of Celosia cristata - Xue-Yue Hou; Yue-Feng Wang; Chuan-Ying Jiang; Tong-Tong Zhai; Rui Miao; Jun-Jie Deng; Zhi-Hong Yao; Rong-Shu Zhang (Horticulture, Environment, and Biotechnology, 2021)

Development of a Microfluidics-Based Quantitative Real-Time PCR to Rapidly Identify Photobacterium damselae subsp. damselae with Different Pathogenicity by Detecting the Presence of mcp or dly Gene - Zheng Zhang; Yongxiang Yu; Jing Chen; Yingeng Wang; Yong Jiang; Meijie Liao; Xiaojun Rong; Hao Zhang (Journal of Ocean University of China, 2021)

Identification of genetic variants in m6A modification genes associated with pancreatic cancer risk in the Chinese population - Pingting Ying; Yao Li; Nan Yang; Xiaoyang Wang; Haoxue Wang; Heng He; Bin Li; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Xiaoping Miao; et al. (Archives of Toxicology, 2021)

Carnosic acid alleviates depression-like behaviors on chronic mild stressed mice via PPAR-γ-dependent regulation of ADPN/FGF9 pathway - Xiao-qing Wang; Ya-hui Tang; Gui-rong Zeng; Li-feng Wu; Ying-jun Zhou; Ze-neng Cheng; De-Jian Jiang (Psychopharmacology, 2021)

Flavonoids as key bioactive components of Oxytropis falcata bunge, a traditional anti-inflammatory and analgesic Tibetan medicine - Mei-Rong Zhang; Kan Jiang; Jun-Li Yang; Yan-Ping Shi (Natural Product Research, 2020)

Management of Gout-associated MSU crystals-induced NLRP3 inflammasome activation by procyanidin B2: targeting IL-1β and Cathepsin B in macrophages - Chun-Ying Qiao; Ying Li; Yue Shang; Min Jiang; Jian Liu; Zi-Ying Zhan; Huan Ye; Yong-Ce Lin; Jing-Ya Jiao; Rong-Hui Sun; Zhi-Hong Zhang; Mei-Hua Piao; et al. (Inflammopharmacology, 2020)

Patterns of intrinsic brain activity in essential tremor with resting tremor and tremor-dominant Parkinson’s disease - Jun-ying Li; Zhong-jiao Lu; Xue-ling Suo; Nan-nan Li; Du Lei; Ling Wang; Jia-xin Peng; Li-ren Duan; Jing Xi; Yi Jiang; Qi-yong Gong; Rong Peng (Brain Imaging and Behavior, 2020)

The intestine of artificially bred larval turbot (Scophthalmus maximus) contains a stable core group of microbiota - Zheng Zhang; Yongxiang Yu; Yan Jiang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Qian Liu (Archives of Microbiology, 2020)

Soil bio-cementation using an improved 2-step injection method - Ming-Juan Cui; Jun-Jie Zheng; Rong-Jun Zhang; Han-Jiang Lai (Arabian Journal of Geosciences, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Small grain and semi-dwarf 3, a WRKY transcription factor, negatively regulates plant height and grain size by stabilizing SLR1 expression in rice - Jie Lan; Qibing Lin; Chunlei Zhou; Yakun Ren; Xi Liu; Rong Miao; Ruonan Jing; Changling Mou; Thanhliem Nguyen; Xingjie Zhu; Qian Wang; Xin Zhang; et al. (Plant Molecular Biology, 2020)

Influence of soil moisture content on pullout properties of Hippophae rhamnoides Linn. roots - Chao-bo Zhang; Ya-ting Liu; Dong-rong Li; Jing Jiang (Journal of Mountain Science, 2020)

Quantitative Angiographic Hemodynamic Evaluation After Revascularization Surgery for Moyamoya Disease - Yu Chen; Li Ma; Shuo Yang; Jan-Karl Burkhardt; Junlin Lu; Xun Ye; Weijian Jiang; Zeguang Ren; Rong Wang; Xiaolin Chen; Yuanli Zhao (Translational Stroke Research, 2020)
The corresponding hemodynamic changes of the internal carotid artery (ICA) after the revascularization surgery for moyamoya disease (MMD) remain unclear. The aim of this study was to analyze the hemodynamic changes of the ipsilateral ICA after the combined direct and indirect extracranial-intracranial (EC-IC) bypass. MMD patients undergoing combined EC-IC bypass were retrospectively reviewed. The mean transit time (MTT) of ICA was evaluated by color-coding angiography before revascularization and at follow-up. The MTT defined as the blood transit time between the end of cervical portion (C1) and the C7 segment of ICA. The clinical prognosis was assessed with Matsushima grading system, moyamoya vessel reduction system, and modified Rankin Scale (mRS). The correlation between hemodynamic parameter and prognosis was analyzed. Subgroup analysis was conducted between different presentations and different ages. Fifty-one patients were identified and the mean imaging follow-up interval was 5.5 months. The ICA-MTT was increased after the combined revascularization ( P < 0.001) compared with contralateral ICA. Faster preoperative ICA-MTT was significantly associated with improved mRS in the ischemic group ( P = 0.05). The increased ICA-MTT was significantly associated with favorable neoangiogenesis ( P = 0.04), moyamoya vessel reduction (> 50%) ( P = 0.023), and improved mRS score ( P = 0.008). In subgroup analysis, the correlation in the ischemic subgroup and adult subgroup remained significant. In this cohort, the ICA-MTT increased after the combined EC-IC bypass, and there was a positive correlation between the increased blood transit time and favorable outcomes. Color-coding DSA proved to be useful as a quantitative and serial method to monitor postoperative courses after revascularization in MMD.

Identification, functional characterization, and estrogen regulation on gonadotropin-releasing hormone in the spotted scat, Scatophagus argus - Hua-pu Chen; Xue-fan Cui; Yao-rong Wang; Zhi-yuan Li; Chang-xu Tian; Dong-neng Jiang; Chun-Hua Zhu; Yong Zhang; Shui-sheng Li; Guang-li Li (Fish Physiology and Biochemistry, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Probiotic and Safety Properties Screening of Enterococcus faecalis from Healthy Chinese Infants - Juan Wang; Rong Da; Xiaohong Tuo; Yue Cheng; Jie Wei; Kaichong Jiang; Jia Lv; Omolade Monisayo Adediji; Bei Han (Probiotics and Antimicrobial Proteins, 2020)

NLRP6 contributes to inflammation and brain injury following intracerebral haemorrhage by activating autophagy - Han Xiao; Hui Chen; Rong Jiang; Li Zhang; Lu Wang; Hui Gan; Ning Jiang; Jing Zhao; Xuan Zhai; Ping Liang (Journal of Molecular Medicine, 2020)

Diverse Secondary Metabolites from a Lichen-Derived Amycolatopsis Strain - Chuansheng Liu; Yi Jiang; Rong Huang; Boguang Jiang; Kaixuan Zheng; Shaohua Wu (Current Microbiology, 2020)

Changes in leaf vein traits among vein types of alpine grassland plants on the Tibetan Plateau - Chang-shun Wang; Wang-wang Lyu; Li-li Jiang; Shi-ping Wang; Qi Wang; Fan-dong Meng; Li-rong Zhang (Journal of Mountain Science, 2020)

Retraction Note to: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng‑Jin Guo (Histochemistry and Cell Biology, 2020)

Oceanobacillus halotolerans sp. nov., a bacterium isolated from salt lake in Xinjiang province, north-west China - Wen-Yong Zhu; Li Yang; Yong-Jiang Shi; Chang-Gai Mu; Yun Wang; Ya-Rong Kou; Min Yin; Shu-Kun Tang (Archives of Microbiology, 2020)

GaHD1, a candidate gene for the Gossypium arboreum SMA-4 mutant, promotes trichome and fiber initiation by cellular H2O2 and Ca2+ signals - Mingquan Ding; Yuefen Cao; Shae He; Jian Sun; Huaqin Dai; Hua Zhang; Chendong Sun; Yurong Jiang; Andrew H. Paterson; Junkang Rong (Plant Molecular Biology, 2020)

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

How does experience impact the adoption willingness of battery electric vehicles? The role of psychological factors - Rong Liu; Zhihua Ding; Xin Jiang; Jing Sun; Yanling Jiang; Wei Qiang (Environmental Science and Pollution Research, 2020)

Effects of nitrogen source and N/P on growth and photosynthesis in the invasive marine macroalga Chaetomorpha valida - Chen Li-hong; Xing Rong-lian; Jiang Ai-li; Yao Ya-nan; Zhou Ge-fei (Environmental Science and Pollution Research, 2020)

Transcriptome analysis reveals genes associated with leaf color mutants in Cymbidium longibracteatum - Jiang Yu; Wang Qiang; Shen Qin-Qin; Zhuo Bi-Ping; He Jun-Rong (Tree Genetics & Genomes, 2020)

Effect of expanded shrub litter on decomposition of graminoid litter in a temperate freshwater marsh - Xinhou Zhang; Yiping Wang; Wei Jiang; Rong Mao (Plant and Soil, 2020)

Functional characterization of a low-frequency V1937I variant in FASN associated with susceptibility to esophageal squamous cell carcinoma - Xiaoyang Wang; Jianbo Tian; Qianyu Zhao; Nan Yang; Pingting Ying; Xiating Peng; Danyi Zou; Ying Zhu; Rong Zhong; Ying Gao; Jiang Chang; Xiaoping Miao (Archives of Toxicology, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Development and characterization of novel microsatellite markers in chestnut tiger butterfly Parantica sita (Lepidoptera: Nymphalidae) using next-generation sequencing - Ping Hu; Chia-Lung Huang; Min-Xin Luo; Yu-Feng Hsu; Rong-Jiang Wang (Applied Entomology and Zoology, 2020)

Reduced mineral fertilization coupled with straw return in field mesocosm vegetable cultivation helps to coordinate greenhouse gas emissions and vegetable production - Rong Huang; Jiang Liu; Xinhua He; Deti Xie; Jiupai Ni; Chang Xu; Yarong Zhang; En Ci; Zifang Wang; Ming Gao (Journal of Soils and Sediments, 2020)

Predictors of nasal bacterial culture rates in patients with chronic rhinosinusitis - Jing-Jie Wang; Chih-Yi Chen; Kai-Li Liang; Rong-San Jiang (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Community structure of Anaeromyxobacter in Fe(III) reducing enriched cultures of paddy soils - Kun Wang; Rong Jia; Lina Li; Rui Jiang; Dong Qu (Journal of Soils and Sediments, 2020)

Roles of PTBP1 in alternative splicing, glycolysis, and oncogensis - Wei Zhu; Bo-lun Zhou; Li-juan Rong; Li Ye; Hong-juan Xu; Yao Zhou; Xue-jun Yan; Wei-dong Liu; Bin Zhu; Lei Wang; Xing-jun Jiang; Cai-ping Ren (Journal of Zhejiang University-SCIENCE B, 2020)

Preferential insertion of a Ty1 LTR-retrotransposon into the A sub-genome’s HD1 gene significantly correlated with the reduction in stem trichomes of tetraploid cotton - Mengling Tang; Xingcheng Wu; Yuefen Cao; Yuan Qin; Mingquan Ding; Yurong Jiang; Chengdong Sun; Hua Zhang; Andrew H. Paterson; Junkang Rong (Molecular Genetics and Genomics, 2020)

RETRACTED ARTICLE: Emerging protective roles of shengmai injection in septic cardiomyopathy in mice by inducing myocardial mitochondrial autophagy via caspase-3/Beclin-1 axis - Yan Cao; Xiaotong Han; Hongwei Pan; Yu Jiang; Xiang Peng; Weiwei Xiao; Jingjing Rong; Fang Chen; Jin He; Lianhong Zou; Yi Tang; Yanfang Pei; et al. (Inflammation Research, 2020)

Three functional variants were identified to affect RPS24 expression and significantly associated with risk of colorectal cancer - Danyi Zou; Hongli Zhang; Juntao Ke; Jiaoyuan Li; Ying Zhu; Yajie Gong; Yang Yang; Jianbo Tian; Yi Zhang; Xiating Peng; Kailin Cai; Rong Zhong; et al. (Archives of Toxicology, 2020)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Symbiotic fungi undergo a taxonomic and functional bottleneck during orchid seeds germination: a case study on Dendrobium moniliforme - Yuan-Yuan Meng; Xu-Li Fan; Lv-Rong Zhou; Shi-Cheng Shao; Qiang Liu; Marc-André Selosse; Jiang-Yun Gao (Symbiosis, 2019)

Urinary Metal Concentrations and the Incidence of Hypertension Among Adult Residents Along the Yangtze River, China - Qi Zhong; Chun-xiao Jiang; Chi Zhang; Qian Zhang; Qi-rong Qin; Xiao-dong Wang; Fen Huang (Archives of Environmental Contamination and Toxicology, 2019)

Predicting trait-like individual differences in fear of pain in the healthy state using gray matter volume - Xiaowan Wang; Chris Baeken; Mengxia Fang; Jiang Qiu; Hong Chen; Guo-Rong Wu (Brain Imaging and Behavior, 2019)

Trends of sea surface wind energy over the South China Sea - Bo Jiang; Yongliang Wei; Jie Ding; Rong Zhang; Yuxin Liu; Xiaoyong Wang; Yizhou Fang (Journal of Oceanology and Limnology, 2019)

Critical regulation of atherosclerosis by the KCa3.1 channel and the retargeting of this therapeutic target in in-stent neoatherosclerosis - Yan-Rong Zhu; Xiao-Xin Jiang; Dai-Min Zhang (Journal of Molecular Medicine, 2019)

Identification and mapping of a photoperiod response gene (QPpd.zafu-4A) on wild emmer wheat (Triticum turgidum L.) chromosome 4AL - Jinsheng Yu; Yunzheng Miao; Siqing Yang; Zhaobin Shi; Nana Miao; Mingquan Ding; Hua Zhang; Yurong Jiang; Junkang Rong (Euphytica, 2019)

Identification of cis-regulatory regions responsible for developmental and hormonal regulation of HbHMGS1 in transgenic Arabidopsis thaliana - Xiao-Xiao Gong; Bing-Yu Yan; Yu-Rong Tan; Xuan Gao; Dan Wang; Heng Zhang; Peng Wang; Shuang-Jiang Li; Yi Wang; Lu-Yao Zhou; Jin-Ping Liu (Biotechnology Letters, 2019)

Coordinated regulation of three kinds of thermotolerance in tomato by antioxidant enzymes - Mintao Sun; Fangling Jiang; Rong Zhou; Benjian Cen; Zhen Wu (Acta Physiologiae Plantarum, 2019)

Recent advances in carbohydrate-based cancer vaccines - Ke-Tao Jin; Huan-Rong Lan; Xiao-Yi Chen; Shi-Bing Wang; Xiao-Jiang Ying; Yan Lin; Xiao-Zhou Mou (Biotechnology Letters, 2019)

Non-monotonic Relaxation and Memory Effect of Rock Salt - Yi He; Deyi Jiang; Jie Chen; Rong Liu; Jinyang Fan; Xiang Jiang (Rock Mechanics and Rock Engineering, 2019)

Allopolyploidization facilitates gene flow and speciation among corn, Zea perennis and Tripsacum dactyloides - Muhammad Zafar Iqbal; Mingjun Cheng; Yuegui Su; Yang Li; Weiming Jiang; Huaxiong Li; Yanli Zhao; Xiaodong Wen; Lei Zhang; Asif Ali; Tingzhao Rong; Qilin Tang (Planta, 2019)

Hydrogen peroxide and nitric oxide are involved in programmed cell death induced by cryopreservation in Dendrobium protocorm-like bodies - Xue-ru Jiang; Rui-fen Ren; Wei Di; Meng-xue Jia; Ze-di Li; Yan Liu; Rong-fu Gao (Plant Cell, Tissue and Organ Culture (PCTOC), 2019)

Pericarp and seed of litchi and longan fruits: constituent, extraction, bioactive activity, and potential utilization - Xiang-rong Zhu; Hui Wang; Jian Sun; Bao Yang; Xue-wu Duan; Yue-ming Jiang (Journal of Zhejiang University-SCIENCE B, 2019)

Polymorphisms in the APOBEC3G gene of Chinese rhesus macaques affect resistance to ubiquitination and degradation mediated by HIV-2 Vif - Zhi-Qiang Jiang; Xu-Rong Yao; Hang Yu; Yue-Er Lu; Bei-Lei Liu; Feng-Liang Liu; Ya-Bin Jin; Min Zhuo; Yong-Tang Zheng; Fei Ling (Archives of Virology, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Quantitative Vulnerability Model of Earth Dam Overtopping and its Application - Chong-Xun Mo; Gui-Yan Mo; Liu Peng; Qing Yang; Xin-Rong Zhu; Qing-Ling Jiang; Ju-Liang Jin (Water Resources Management, 2019)

Genome-wide detection of additional fetal chromosomal abnormalities by cell-free DNA testing of 15,626 consecutive pregnant women - Hong Yao; Ya Gao; Jia Zhao; Rong Zhang; Huixin Xu; Huamei Hu; Yanmei Luo; Yuying Yuan; Meili Fu; Hongyun Zhang; Hui Jiang; Wei Wang; et al. (Science China Life Sciences, 2019)

Topical delivery of 3,5,4′-trimethoxy-trans-stilbene-loaded microemulsion-based hydrogel for the treatment of osteoarthritis in a rabbit model - Xiong-Bin Hu; Rong-Rong Kang; Tian-Tian Tang; Yong-Jiang Li; Jun-Yong Wu; Jie-Min Wang; Xin-Yi Liu; Da-Xiong Xiang (Drug Delivery and Translational Research, 2019)

Model parameter-related optimal perturbations and their contributions to El Niño prediction errors - Ling-Jiang Tao; Chuan Gao; Rong-Hua Zhang (Climate Dynamics, 2019)

Oxidative damage and antioxidant mechanism in tomatoes responding to drought and heat stress - Rong Zhou; Lingpeng Kong; Xiaqing Yu; Carl-Otto Ottosen; Tongmin Zhao; Fangling Jiang; Zhen Wu (Acta Physiologiae Plantarum, 2019)

What drives low-carbon consumption behavior of Chinese college students? The regulation of situational factors - Yan Liu; Rong Liu; Xin Jiang (Natural Hazards, 2019)

Can Chinese residential low-carbon consumption behavior intention be better explained? The role of cultural values - Xin Jiang; Zhihua Ding; Rong Liu (Natural Hazards, 2019)

A frameshift mutation in exon 19 of MLH1 in a Chinese Lynch syndrome family: a pedigree study - Qiao-qi Sui; Wu Jiang; Xiao-dan Wu; Yi-hong Ling; Zhi-zhong Pan; Pei-rong Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Grey Matter Volumes in the Executive Attention System Predict Individual Differences in Effortful Control in Young Adults - Luqing Wei; Nana Guo; Chris Baeken; Minghua Bi; Xiaowan Wang; Jiang Qiu; Guo-Rong Wu (Brain Topography, 2019)

Independent losses and duplications of autophagy‐related genes in fungal tree of life - Qinhu Wang; Huiquan Liu; Huaijian Xu; Ruonan Hei; Shijie Zhang; Cong Jiang; Jin‐Rong Xu (Environmental Microbiology, 2019)
Summary Autophagy is important for growth, development and pathogenesis in fungi. Although autophagic process is generally considered to be conserved, the conservation and evolution of ATG genes at kingdom‐wide remains to be conducted. Here we systematically identified 41 known ATG genes in 331 species and analyzed their distribution across the fungal kingdom. In general, only 20 ATG genes are highly conserved, including most but not all the yeast core‐autophagy‐machinery genes. Four functional protein groups involved in autophagosome formation had conserved and non‐conserved components, suggesting plasticity in autophagosome formation in fungi. All or majority of the key ATG genes were lost in several fungal groups with unique lifestyles and niches, such as Microsporidia, Pneumocystis and Malassezia . Moreover, majority of ATG genes had A‐to‐I RNA editing during sexual reproduction in two ascomycetes and deletion of FgATG11 , the ATG gene with the most editing sites in Fusarium affected ascospore releasing. Duplication and divergence also was observed to several core ATG genes, such as highly divergent ATG8 paralogs in dermatophytes and multiple ATG15 duplications in mushrooms. Taken together, independent losses and duplications of ATG genes have occurred throughout the fungal kingdom and variations in autophagy exist among different lineages and possibly different developmental stages.

Anti-senescence effect and molecular mechanism of the major royal jelly proteins on human embryonic lung fibroblast (HFL-I) cell line - Chen-min Jiang; Xin Liu; Chun-xue Li; Hao-cheng Qian; Di Chen; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Nutrient Balancing by Captive Golden Snub-Nosed Monkeys (Rhinopithecus roxellana) - Stephanie T. Chen; Xi Luo; Rong Hou; David Raubenheimer; Weihong Ji; Xuelin Jin; Zhi Jiang; Xuewei Yu; Jiajia Wang; Min Li; Songtao Guo; Baoguo Li (International Journal of Primatology, 2018)

A genetic system on chromosome arm 1BL of wild emmer causes distorted segregation in common wheat - Yunzheng Miao; Siqing Yang; Yurong Jiang; Junkang Rong; Jinsheng Yu (Journal of Genetics, 2018)

Association between serum somatostatin levels and glucose-lipid metabolism in the Jino ethnic minority and Han Chinese population - Shiyun Wang; Rong Zhang; Xuhong Hou; Fusong Jiang; Jie Wang; Zhen He; Feng Jiang; Cheng Hu; Weiping Jia (Science China Life Sciences, 2018)

Evaluating tacrolimus pharmacokinetic models in adult renal transplant recipients with different CYP3A5 genotypes - Can Hu; Wen-jun Yin; Dai-yang Li; Jun-jie Ding; Ling-yun Zhou; Jiang-lin Wang; Rong-rong Ma; Kun Liu; Ge Zhou; Xiao-cong Zuo (European Journal of Clinical Pharmacology, 2018)

Cretaceous A-type volcanic–intrusive rocks and simultaneous mafic rocks along the Gan-Hang Tectonic Belt, Southeast China: petrogenesis and implications for the transition of crust–mantle interaction - Hong-Zuo Wang; Pei-Rong Chen; Kai-Xing Wang; Hong-Fei Ling; Jun-Qi Wu; Jiang-Wei Tang; You-Dong Zhao (International Geology Review, 2018)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Identification and genetic mapping for rht-DM, a dominant dwarfing gene in mutant semi-dwarf maize using QTL-seq approach - Qian Chen; Jun Song; Wen-Ping Du; Li-Yuan Xu; Yun Jiang; Jie Zhang; Xiao-Li Xiang; Gui-Rong Yu (Genes & Genomics, 2018)

GDC-0152-induced autophagy promotes apoptosis in HL-60 cells - Liang Peiqi; Hu Rong; Dong Hongming; Liu Zhuogang; Jiang Wei; Miao Miao (Molecular and Cellular Biochemistry, 2018)

Modern pollen distribution in the northeastern Indian Ocean and its significance - Chuanxiu Luo; Weiming Jiang; Chixin Chen; Huanhuan Peng; Rong Xiang; Jianguo Liu; Jun Lu; Xiang Su; Qiang Zhang; Mingxi Yang (International Journal of Biometeorology, 2018)

An improved simulation of the 2015 El Niño event by optimally correcting the initial conditions and model parameters in an intermediate coupled model - Rong-Hua Zhang; Ling-Jiang Tao; Chuan Gao (Climate Dynamics, 2018)

ENSO Predictions in an Intermediate Coupled Model Influenced by Removing Initial Condition Errors in Sensitive Areas: A Target Observation Perspective - Ling-Jiang Tao; Chuan Gao; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2018)

Inhibitory Effect of Vaginal Lactobacillus Supernatants on Cervical Cancer Cells - Ke-Di Wang; Dong-Jiang Xu; Bao-Ya Wang; Dong-Hui Yan; Zhi Lv; Jian-Rong Su (Probiotics and Antimicrobial Proteins, 2018)

Atlas of the Striatum and Globus Pallidus in the Tree Shrew: Comparison with Rat and Mouse - Rong-Jun Ni; Zhao-Huan Huang; Yu-Mian Shu; Yu Wang; Tao Li; Jiang-Ning Zhou (Neuroscience Bulletin, 2018)

Variability of crack initiation and crack damage for various rock types - Jun Peng; Guan Rong; Maiyong Jiang (Arabian Journal of Geosciences, 2018)

Sucrose is involved in the regulation of iron deficiency responses in rice (Oryza sativa L.) - Peng-Fei Chen; Lin Chen; Zheng-Rong Jiang; Gao-Peng Wang; Shao-Hua Wang; Yan-Feng Ding (Plant Cell Reports, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

CD200Fc Attenuates Retinal Glial Responses and RGCs Apoptosis After Optic Nerve Crush by Modulating CD200/CD200R1 Interaction - Rong Huang; Qianqian Lan; Lifei Chen; Haibin Zhong; Ling Cui; Li Jiang; Hui Huang; Li Li; Siming Zeng; Min Li; Xin Zhao; Fan Xu (Journal of Molecular Neuroscience, 2018)

Exploration of the formation mechanism and source attribution of ambient ozone in Chongqing with an observation-based model - Rong Su; KeDing Lu; JiaYan Yu; ZhaoFeng Tan; MeiQing Jiang; Jing Li; ShaoDong Xie; YuSheng Wu; LiMin Zeng; ChongZhi Zhai; YuanHang Zhang (Science China Earth Sciences, 2018)

β-Arrestin-1 deficiency ameliorates renal interstitial fibrosis by blocking Wnt1/β-catenin signaling in mice - Huiyan Xu; Quanxin Li; Jiang Liu; Jiaqing Zhu; Liang Li; Ziying Wang; Yan Zhang; Yu Sun; Jinpeng Sun; Rong Wang; Fan Yi (Journal of Molecular Medicine, 2018)

Cyclooxygenase-2 (COX-2) polymorphism rs689466 may contribute to the increased susceptibility to post-traumatic osteomyelitis in Chinese population - Lei Wang; Nan Jiang; Qing-rong Lin; Cheng-he Qin; Yan-jun Hu; Bin Yu (Infectious Diseases, 2017)

Ketamine induces neuronal apoptosis and cognitive disorder via miR-199a-5p/HIF-1α in neonatal rats - Jia Yan; Yue Yu; Yu Sun; Rong Hu; Hong Jiang (Molecular & Cellular Toxicology, 2017)

Soil aggregate and organic carbon distribution at dry land soil and paddy soil: the role of different straws returning - Rong Huang; Muling Lan; Jiang Liu; Ming Gao (Environmental Science and Pollution Research, 2017)

Productive functional evolution of rural settlements: analysis of livelihood strategy and land use transition in eastern China - Bai-lin Zhang; Guang-hui Jiang; Wei-min Cai; Pi-ling Sun; Feng-rong Zhang (Journal of Mountain Science, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Characterization of a metagenome-derived protease from contaminated agricultural soil microorganisms and its random mutagenesis - Chengjian Jiang; Liang Zhang; Fajia Li; Can Meng; Rong Zeng; Jie Deng; Peihong Shen; Qian Ou; Bo Wu (Folia Microbiologica, 2017)

Nortirucallane A, a new tirucallane-type nortriterpenoid isolated from Lonicerae japonicae flos - Xu Wang; Jing Zhang; Ya-qun Li; Bao-xiang Du; Qi-hui Sun; Yun-jiao Cao; Hai-qiang Jiang; Yu-hong Liu; Hong-lei Zhou; Rong Rong (Natural Product Research, 2017)

Reduced weed seed shattering by silencing a cultivated rice gene: strategic mitigation for escaped transgenes - Huanxin Yan; Lei Li; Ping Liu; Xiaoqi Jiang; Lei Wang; Jia Fang; Zhimin Lin; Feng Wang; Jun Su; Bao-Rong Lu (Transgenic Research, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The contribution of component variation and phytoplankton growth to the distribution variation of chromophoric dissolved organic matter content in a mid-latitude subtropical drinking water source reservoir for two different seasons - Qiyuan Sun; Juan Jiang; Yuyi Zheng; Feifeng Wang; Chunshan Wu; Rong-rong Xie (Environmental Science and Pollution Research, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

Initial error-induced optimal perturbations in ENSO predictions, as derived from an intermediate coupled model - Ling-Jiang Tao; Rong-Hua Zhang; Chuan Gao (Advances in Atmospheric Sciences, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Zebrafish phosvitin-derived peptide Pt5 inhibits melanogenesis via cAMP pathway - Yuan-Yuan Liu; Xiu-Rong Su; Shou-Sheng Liu; Shuang-Shuang Yang; Cheng-Yan Jiang; Yu Zhang; Shicui Zhang (Fish Physiology and Biochemistry, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Use of electroacupuncture and transcutaneous electrical acupoint stimulation in reproductive medicine: a group consensus - Fan Qu; Rong Li; Wei Sun; Ge Lin; Rong Zhang; Jing Yang; Li Tian; Guo-gang Xing; Hui Jiang; Fei Gong; Xiao-yan Liang; Yan Meng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Chlorophyll fluorescence lifetime imaging provides new insight into the chlorosis induced by plant virus infection - Rong Lei; Hongshan Jiang; Fan Hu; Jin Yan; Shuifang Zhu (Plant Cell Reports, 2017)

Particle size distributions and organic-inorganic compositions of suspended particulate matters around the Bohai Strait - Xiao Wang; Changwei Bian; Rong Bi; Wensheng Jiang; Hua Zhang; Xueqing Zhang (Journal of Ocean University of China, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Optimization of conditions for an integrated multi-trophic aquaculture system consisting of sea cucumber Apostichopus japonicus and ascidian Styela clava - Bao Ju; Ai-li Jiang; Rong-lian Xing; Li-hong Chen; Li Teng (Aquaculture International, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Use of random forests and support vector machines to improve annual egg production estimation - Zengguang Li; Rong Wan; Zhenjiang Ye; Yong Chen; Yiping Ren; Hong Liu; Yiqian Jiang (Fisheries Science, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

ApoA-I induces S1P release from endothelial cells through ABCA1 and SR-BI in a positive feedback manner - Xing Liu; Kun Ren; Rong Suo; Sheng-Lin Xiong; Qing-Hai Zhang; Zhong-Cheng Mo; Zhen-Li Tang; Yue Jiang; Xiao-Shan Peng; Guang-Hui Yi (Journal of Physiology and Biochemistry, 2016)

Three-Dimensional Tricuspid Annular Motion Analysis from Cardiac Magnetic Resonance Feature-Tracking - Shuang Leng; Meng Jiang; Xiao-Dan Zhao; John Carson Allen; Ghassan S. Kassab; Rong-Zhen Ouyang; Ju-Le Tan; Ben He; Ru-San Tan; Liang Zhong (Annals of Biomedical Engineering, 2016)

Strategies to Determine Assay Format for the Assessment of Neutralizing Antibody Responses to Biotherapeutics - Bonnie Wu; Shan Chung; Xu-Rong Jiang; Jim McNally; Joao Pedras-Vasconcelos; Renuka Pillutla; Joleen T. White; Yuanxin Xu; Shalini Gupta (The AAPS Journal, 2016)

Brain natriuretic peptide for prevention of contrast-inducednephropathy: a meta-analysis of randomized controlled trials - Xue-biao Wei; Lei Jiang; Xin-rong Liu; Dan-qing Yu; Ning Tan; Ji-yan Chen; Ying-ling Zhou; Peng-cheng He; Yuan-hui Liu (European Journal of Clinical Pharmacology, 2016)

Metastasis associated genomic aberrations in stage II rectal cancer - Hong Zhao; Zhi-Zhou Shi; Rui Jiang; Dong-Bing Zhao; Hai-Tao Zhou; Jian-Wei Liang; Xin-Yu Bi; Jian-Jun Zhao; Zhi-Yu Li; Jian-Guo Zhou; Zhen Huang; Ye-Fan Zhang; et al. (Genes & Genomics, 2016)

TRI6 and TRI10 play different roles in the regulation of deoxynivalenol (DON) production by cAMP signalling in Fusarium graminearum - Cong Jiang; Chengkang Zhang; Chunlan Wu; Panpan Sun; Rui Hou; Huiquan Liu; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary The biosynthesis of mycotoxin deoxynivalenol (DON) in Fusarium graminearum is regulated by two pathway‐specific transcription factors Tri6 and Tri10 and affected by various host and environmental factors. In this study, we showed that cyclic adenosine monophosphate (cAMP) treatment induced DON production by stimulating TRI gene expression and DON‐associated cellular differentiation in F. graminearum . Interestingly, exogenous cAMP had no effects on the tri6 mutant but partially recovered the defect of tri10 mutant in DON biosynthesis. Although the two cAMP phosphodiesterase genes PDE1 and PDE2 had overlapping functions in vegetative growth, conidiation, sexual reproduction and plant infection, deletion of PDE2 but not PDE1 activated intracellular PKA activities and increased DON production. Whereas the tri6 pde2 mutant failed to produce DON, the tri10 pde2 double mutant produced a significantly higher level of DON than the tri10 mutant. Cellular differentiation associated with DON production was stimulated by exogenous cAMP or deletion of PDE2 in both tri10 and tri6 mutants. These data indicate that TRI6 is essential for the regulation of DON biosynthesis by cAMP signalling but elevated PKA activities could partially bypass the requirement of TRI10 for TRI gene‐expression and DON production, and Pde2 is the major cAMP phosphodiesterase to negatively regulate DON biosynthesis in F. graminearum .

Thioredoxins are involved in the activation of the PMK1 MAP kinase pathway during appressorium penetration and invasive growth in Magnaporthe oryzae - Shijie Zhang; Cong Jiang; Qiang Zhang; Linlu Qi; Chaohui Li; Jin‐Rong Xu (Environmental Microbiology, 2016)
Summary In Magnaporthe oryzae , the Mst11‐Mst7‐Pmk1 MAP kinase pathway is essential for appressorium formation and invasive growth. To determine their roles in Pmk1 activation and plant infection, we characterized the two thioredoxin genes, TRX1 and TRX2 , in M. oryzae . Whereas the Δ trx1 mutants had no detectable phenotypes, deletion of TRX2 caused pleiotropic defects in growth, conidiation, light sensing, responses to stresses and plant infection progresses. The Δ trx1 Δ trx2 double mutant had more severe defects than the Δ trx2 mutant and was non‐pathogenic in infection assays. The Δ trx2 and Δ trx1 Δ trx2 mutant rarely formed appressoria on hyphal tips and were defective in invasive growth after penetration. Pmk1 phosphorylation was barely detectable in the Δ trx2 and Δ trx1 Δ trx2 mutants. Deletion of TRX2 affected proper folding or intra‐/inter‐molecular interaction of Mst7 and expression of the dominant active MST7 allele partially rescued the defects of the Δ trx1 Δ trx2 mutant. Furthermore, Cys305 is important for Mst7 function and Trx2 directly interacts with Mst7 in co‐IP assays. Our data indicated that thioredoxins play important roles in intra‐cellular ROS signalling and pathogenesis in M. oryzae . As the predominant thioredoxin gene, TRX2 may regulate the activation of Pmk1 MAPK via its effects on Mst7.

Sympodial bamboo species differ in carbon bio-sequestration and stocks within phytoliths of leaf litters and living leaves - Tingting Xiang; Yuqi Ying; Jiangnan Teng; Zhangting Huang; Jiasen Wu; Cifu Meng; Peikun Jiang; Caixian Tang; Jianmin Li; Rong Zheng (Environmental Science and Pollution Research, 2016)

Experimental Study of Coal and Gas Outbursts Related to Gas-Enriched Areas - Qingyi Tu; Yuanping Cheng; Pinkun Guo; Jingyu Jiang; Liang Wang; Rong Zhang (Rock Mechanics and Rock Engineering, 2016)

The composition of pericarp, cell aging, and changes in water absorption in two tomato genotypes: mechanism, factors, and potential role in fruit cracking - Zeen Yang; Zhen Wu; Chuan Zhang; Enmei Hu; Rong Zhou; Fangling Jiang (Acta Physiologiae Plantarum, 2016)

A preliminary study on the potential value of a novel integrated aquaculture system on water purification - Li-hong Chen; Rong-lian Xing; Ai-li Jiang; Li Teng; Chang-hai Wang (Aquaculture International, 2016)

Relationship between leaf reddening, ROS and antioxidants in Buxus microphylla during overwintering - Xue-ru Jiang; Jin-gen Peng; Meng-xue Jia; Yan Liu; Ling Guo; Rong-fu Gao (Acta Physiologiae Plantarum, 2016)

Chromosome elimination of hexaploid common wheat mediated by interaction between Chinese Spring cytoplasm and a genetic factor(s) on chromosome arm 1BL of wild emmer - Y. R. Jiang; M. D. He; M. Q. Ding; J. K. Rong (Euphytica, 2016)

Comparison of DNA methylation in the developing seeds of yellow- and black-seeded Brassica napus through MSAP analysis - Y. Wang; H. Rong; T. Xie; J. Jiang; J. Wu; Y. Wang (Euphytica, 2016)

The influence of plant root system architectural properties upon the stability of loess hillslopes, Northeast Qinghai, China - Jiang-tao Fu; Xia-song Hu; Gary Brierley; Na Qiao; Qin-qin Yu; Hai-jing Lu; Guo-rong Li; Hai-li Zhu (Journal of Mountain Science, 2016)

Epigenetic mechanisms of salt tolerance and heterosis in Upland cotton (Gossypium hirsutum L.) revealed by methylation-sensitive amplified polymorphism analysis - Baohua Wang; Mi Zhang; Rong Fu; Xiaowei Qian; Ping Rong; Yan Zhang; Peng Jiang; Junjuan Wang; Xuke Lu; Delong Wang; Wuwei Ye; Xinyu Zhu (Euphytica, 2016)

Impact of urban land-use change in eastern China on the East Asian subtropical monsoon: A numerical study - Rong Yu; Zhihong Jiang; Panmao Zhai (Journal of Meteorological Research, 2016)

Valproic Acid Influences MTNR1A Intracellular Trafficking and Signaling in a β-Arrestin 2-Dependent Manner - Ling-juan Hong; Quan Jiang; Sen Long; Huan Wang; Ling-di Zhang; Yun Tian; Cheng-kun Wang; Jing-jing Cao; Rong-rong Tao; Ji-yun Huang; Mei-hua Liao; Ying-mei Lu; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Role of immune tolerance in BALB/c mice with anaphylactic shock after Echinococcus granulosus infection - Qin Zhang; Jian-Rong Ye; Hai-Mei Ma; Jian-Jiang Wu; Tao Jiang; Hong Zheng (Immunologic Research, 2016)

Preferable procedure for the screening of syphilis in clinical laboratories in China - Ke-Di Wang; Dong-Jiang Xu; Jian-Rong Su (Infectious Diseases, 2016)

Population pharmacokinetics of vancomycin in adult Chinese patients with post-craniotomy meningitis and its application in individualised dosage regimens - Wei-wei Lin; Wei Wu; Zheng Jiao; Rong-fang Lin; Chang-zhen Jiang; Pin-fang Huang; Yi-wei Liu; Chang-lian Wang (European Journal of Clinical Pharmacology, 2016)

Comparison of seven colchicine-induced tetraploid clones with their original diploid clones in purple coneflower (Echinacea purpurea L.) - Rong Chen; Wei-zhen Jiang; Qing-ling Li; Xin-lian Li; Xiao-lu Chen; Yue-sheng Yang; Hong Wu (Euphytica, 2016)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

Variability of sea surface height in the South China Sea and its relationship to Pacific oscillations - Yuhua Pei; Rong-Hua Zhang; Xiangming Zhang; Lianghong Jiang; Yanzhou Wei (Acta Oceanologica Sinica, 2015)

A Neutralizing Antibody Assay Based on a Reporter of Antibody-Dependent Cell-Mediated Cytotoxicity - Yuling Wu; Jia J. Li; Hyun Jun Kim; Xu Liu; Weiyi Liu; Ahmad Akhgar; Michael A. Bowen; Susan Spitz; Xu-Rong Jiang; Lorin K. Roskos; Wendy I. White (The AAPS Journal, 2015)

Tetrodotoxin detection and species identification of pufferfish in retail roasted fish fillet by DNA barcoding in China - Nan Li; Qing Shen; Jiahui Wang; Chunhui Han; Rong Ji; Fengqin Li; Tao Jiang (Food Additives & Contaminants: Part A, 2015)

High precision in-situ Pb isotopic analysis of sulfide minerals by femtosecond laser ablation multi-collector inductively coupled plasma mass spectrometry - HongLin Yuan; Cong Yin; Xu Liu; KaiYun Chen; ZhiAn Bao; ChunLei Zong; MenNing Dai; ShaoCong Lai; Rong Wang; ShaoYong Jiang (Science China Earth Sciences, 2015)

Effects of different microbes on fermenting feed for sea cucumber (Apostichopus japonicus) - Yan Jiang; Yingeng Wang; Kangsen Mai; Zheng Zhang; Meijie Liao; Xiaojun Rong (Journal of Ocean University of China, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Activation of the signalling mucin MoM sb2 and its functional relationship with C bp1 in M agnaporthe oryzae - Guanghui Wang; Guotian Li; Shijie Zhang; Cong Jiang; Jun Qin; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Various surface signals are recognized by M agnaporthe oryzae to activate the P mk1 MAP kinase that is essential for appressorium formation and invasive growth. One of upstream sensors of the P mk1 pathway is the MoM sb2 signalling mucin. However, the activation of MoM sb2 and its relationship with other sensors is not clear. In this study, we showed that the cleavage and transmembrane domains are essential for MoM sb2 functions. Cleavage of MoM sb2 was further confirmed by western blot analysis, and five putative cleavage sites were functionally characterized. Expression of the extracellular region alone partially rescued the defects of M omsb2 in appressorium formation and virulence. The cytoplasmic region of MoM sb2, although dispensable for appressorium formation, was more important for penetration and invasive growth. Interestingly, the M omsb2 cbp1 double mutant deleted of both mucin genes was blocked in P mk1 activation. It failed to form appressoria on artificial surfaces and was non‐pathogenic. In addition, we showed that MoM sb2 interacts with R as2 but not with MoC dc42 in co‐immunoprecipitation assays. Overall, results from this study indicated that the extracellular and cytoplasmic regions of MoM sb2 have distinct functions in appressorium formation, penetration and invasive growth, and MoM sb2 has overlapping functions with C bp1 in recognizing environmental signals for P mk1 activation.

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

The role of Cyclin G1 in cellular proliferation and apoptosis of human epithelial ovarian cancer - Lifei Jiang; Rong Liu; Yingying Wang; Chunmiao Li; Qinghua Xi; Jianxin Zhong; Jian Liu; Shuyun Yang; Juan Wang; Menghui Huang; Chunhui Tang; Zheng Fang (Journal of Molecular Histology, 2015)

Phosphorylation of p38 MAPK mediates aquaporin 9 expression in rat brains during permanent focal cerebral ischaemia - Xiaoyu Wei; Xuxia Ren; Rong Jiang; Hui Li; Fei Gao; Yuqin Chen; Jiaojiao Hou; Xueyuan Liu; Shanquan Sun; Mei Yang (Journal of Molecular Histology, 2015)

Prauserella endophytica sp. nov., an endophytic actinobacterium isolated from Tamarix taklamakanensis - Jia-Meng Liu; Xugela Habden; Lin Guo; Li Tuo; Zhong-Ke Jiang; Shao-Wei Liu; Xian-Fu Liu; Li Chen; Rong-Feng Li; Yu-Qin Zhang; Cheng-Hang Sun (Antonie van Leeuwenhoek, 2015)

Mycoremediation potential and tolerance responses of Oudemansiella radicata in cadmium-pyrene co-contaminated soil - Rong Chen; Zhiren Zhou; Yuanxiu Liu; Juan Jiang; Qiao Li; Haihai Song; Donghui Pei; Heng Xu (Journal of Soils and Sediments, 2015)

The Marginal Division of the Striatum and Hippocampus Has Different Role and Mechanism in Learning and Memory - Si-Yun Shu; Gang Jiang; Qi-Yi Zeng; Bin Wang; Hong Li; Lin Ma; Harry Steinbusch; Cai Song; Wood-Yee Chan; Xu-Hong Chen; Yon-Ming Wu; Rong Bao; et al. (Molecular Neurobiology, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Abundance and distribution of fatty acids in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Journal of Ocean University of China, 2015)

FgSKN 7 and FgATF 1 have overlapping functions in ascosporogenesis, pathogenesis and stress responses in F usarium graminearum - Cong Jiang; Shijie Zhang; Qiang Zhang; Yin Tao; Chenfang Wang; Jin‐Rong Xu (Environmental Microbiology, 2015)
Summary Fusarium head blight caused by F usarium graminearum is one of the most destructive diseases of wheat and barley. Deoxynivalenol ( DON ) produced by the pathogen is an important mycotoxins and virulence factor. Because oxidative burst is a common defense response and reactive oxygen species ( ROS ) induces DON production, in this study, we characterized functional relationships of three stress‐related transcription factor genes FgAP 1 , FgATF 1 and FgSKN 7. Although all of them played a role in tolerance to oxidative stress, deletion of FgAP 1 or FgATF 1 had no significant effect on DON production. In contrast, F gskn7 mutants were reduced in DON production and defective in H 2 O 2 ‐induced TRI gene expression. The F gap1 mutant had no detectable phenotype other than increased sensitivity to H 2 O 2 and F gap1 F gatf1 and F gap1 F gskn7 mutants lacked additional or more severe phenotypes than the single mutants. The F gatf1 , but not F gskn7 , mutant was significantly reduced in virulence and delayed in ascospore release. The F gskn7 F gatf1 double mutant had more severe defects in growth, conidiation and virulence than the F gatf1 or F gskn7 mutant. Instead of producing four‐celled ascospores, it formed eight small, single‐celled ascospores in each ascus. Therefore, FgSKN 7 and FgATF 1 must have overlapping functions in intracellular ROS signalling for growth, development and pathogenesis in F . graminearum .

Verification of Progeny from Crosses Between Sugarcane (Saccharum spp.) and an Intergeneric Hybrid (Erianthus arundinaceus × Saccharum spontaneum) with Molecular Makers - Yi-Jing Gao; Xi-Hui Liu; Rong-Hua Zhang; Hui Zhou; Jiang-Xiong Liao; Wei-Xing Duan; Ge-Min Zhang (Sugar Tech, 2015)

Genome-wide investigation and transcriptome analysis of the WRKY gene family in Gossypium - Mingquan Ding; Jiadong Chen; Yurong Jiang; Lifeng Lin; YueFen Cao; Minhua Wang; Yuting Zhang; Junkang Rong; Wuwei Ye (Molecular Genetics and Genomics, 2015)

The Effects of Fludarabine on Rat Cerebral Ischemia - Qian Xu; Chunjuan Jiang; Yutao Rong; Chun Yang; Ying Liu; Kai Xu (Journal of Molecular Neuroscience, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

De novo analysis of the Tenebrio molitor (Coleoptera: Tenebrionidae) transcriptome and identification of putative glutathione S-transferase genes - Su Liu; Xiao-Xiao Shi; Yan-Dong Jiang; Zi-Jie Zhu; Ping Qian; Min-Jing Zhang; Hang Yu; Qing-Zi Zhu; Zhong-Jun Gong; Zeng-Rong Zhu (Applied Entomology and Zoology, 2015)

Effects of exogenous NO on the growth, mineral nutrient content, antioxidant system, and ATPase activities of Trifolium repens L. plants under cadmium stress - Shi-Liang Liu; Rong-Jie Yang; Ming-Dong Ma; Fang Dan; Yan Zhao; Pan Jiang; Mao-Hua Wang (Acta Physiologiae Plantarum, 2015)

Heme Oxygenase-2 Suppress TNF-α and IL6 Expression via TLR4/MyD88-Dependent Signaling Pathway in Mouse Cerebral Vascular Endothelial Cells - Ren-Jin Chen; Hong-Hua Yuan; Teng-Ye Zhang; Zhen-Zhen Wang; An-kang Hu; Lian-Lian Wu; Zhang-Ping Yang; Yong-Jiang Mao; De-Jun Ji; Xiao-Rong Zhu (Molecular Neurobiology, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

RETRACTED ARTICLE: Explore on the effect of ATF6 on cell growth and apoptosis in cartilage development - Xiaofeng Han; Peng Zhang; Rong Jiang; Fei Xia; Meiling Li; Feng-Jin Guo (Histochemistry and Cell Biology, 2014)

Component characteristics of polycyclic aromatic compounds in sediments of the South Mid-Atlantic Ridge - Xin Huang; Zhigang Zeng; Shuai Chen; Xuebo Yin; Xiaoyuan Wang; Yao Ma; Baoju Yang; Kunbo Rong; Yunchao Shu; Tao Jiang (Acta Oceanologica Sinica, 2014)

Determination of Pb genotoxic effects in Allium cepa root cells by fluorescent probe, microtubular immunofluorescence and comet assay - Ze Jiang; Rong Qin; Huanhuan Zhang; Jinhua Zou; Qiuyue Shi; Junran Wang; Wusheng Jiang; Donghua Liu (Plant and Soil, 2014)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

Mantle Transition Zone Structure Beneath Southeastern China and its Implications for Stagnant Slab and Water Transportation in the Mantle - Rong Huang; Yixian Xu; Yinhe Luo; Xiaohuan Jiang (Pure and Applied Geophysics, 2014)

Three major nucleolar proteins migrate from nucleolus to nucleoplasm and cytoplasm in root tip cells of Vicia faba L. exposed to aluminum - Rong Qin; Huaning Zhang; Shaoshan Li; Wusheng Jiang; Donghua Liu (Environmental Science and Pollution Research, 2014)

Protective effect of indomethacin in renal ischemia-reperfusion injury in mice - Sheng-hong Zhu; Li-jia Zhou; Hong Jiang; Rong-jun Chen; Chuan Lin; Shi Feng; Juan Jin; Jiang-hua Chen; Jian-yong Wu (Journal of Zhejiang University-SCIENCE B, 2014)

Expression of TGF-β1, SNAI1 and MMP-9 is associated with lymph node metastasis in papillary thyroid carcinoma - Ni Wang; Rong Jiang; Jun-Yan Yang; Cui Tang; Lei Yang; Man Xu; Qi-Feng Jiang; Zhi-Min Liu (Journal of Molecular Histology, 2014)

Clodronate-superparamagnetic iron oxide-containing liposomes attenuate renal injury in rats with severe acute pancreatitis - Sheng-chun Dang; Yan-hua Zeng; Ping-jiang Wang; Bao-ding Chen; Rong-fang Chen; Arun Kumar Singh; Pankaj Kumar; Shu Feng; Lei Cui; Hao Wang; Jian-xin Zhang (Journal of Zhejiang University-SCIENCE B, 2014)

The Report of Sustained Low-Efficiency Dialysis (SLED) Treatment in Fifteen Patients of Severe Snakebite - Junzhang Cheng; Dan Wang; Shouliang Hu; Hong Jiang; Hongzhu Lu; Qingfeng Lei; Juncheng Liu; Fanli Yuan; Rong Chen (Cell Biochemistry and Biophysics, 2014)

Effects of interannual salinity variability on the barrier layer in the western-central equatorial Pacific: A diagnostic analysis from Argo - Fei Zheng; Rong-Hua Zhang; Jiang Zhu (Advances in Atmospheric Sciences, 2014)

Molecular characterisation and expression profiling of the ENO1 gene in the ovarian follicle of the Sichuan white goose - Bo Kang; Dong Mei Jiang; Lin Bai; Hui He; Rong Ma (Molecular Biology Reports, 2014)

Overexpression of S100P promotes colorectal cancer metastasis and decreases chemosensitivity to 5-FU in vitro - Lei Dong; Fule Wang; Xiaona Yin; Ling Chen; Gang Li; Feiyan Lin; Wuhua Ni; Jianbo Wu; Rong Jin; Lei Jiang (Molecular and Cellular Biochemistry, 2014)

Endothelial Insulin-Like Growth Factor-1 Modulates Proliferation and Phenotype of Smooth Muscle Cells Induced by Low Shear Stress - Lu Wang; Yue Han; Yan Shen; Zhi-Qiang Yan; Ping Zhang; Qing-Ping Yao; Bao-Rong Shen; Li-Zhi Gao; Ying-Xin Qi; Zong-Lai Jiang (Annals of Biomedical Engineering, 2014)

Depression in older patients with advanced colorectal cancer is closely connected with immunosuppressive acidic protein - Rong Li; Jie Yang; Jihua Yang; Weijun Fu; Hua Jiang; Juan Du; Chunyang Zhang; Hao Xi; Jian Hou (Metabolic Brain Disease, 2014)

The role of Gracilaria lemaneiformis in eliminating the dissolved inorganic carbon released from calcification and respiration process of Chlamys farreri - Zeng Jie Jiang; Jian Guang Fang; Ting Ting Han; Yu Ze Mao; Jia Qi Li; Mei Rong Du (Journal of Applied Phycology, 2014)

Enhanced Oxidation Stability of Quasi Core-Shell Alloyed CdSeS Quantum Dots Prepared Through Aqueous Microwave Synthesis Technique - Hong-Ju Zhan; Pei-Jiang Zhou; Rong Ma; Xi-Jing Liu; Yu-Ning He; Chuan-Yun Zhou (Journal of Fluorescence, 2014)

( − )-Arctigenin as a lead compound for anticancer agent - Gui-Rong Chen; Hong-Fu Li; De-Qiang Dou; Yu-Bin Xu; Hong-Shuai Jiang; Fu-Rui Li; Ting-Guo Kang (Natural Product Research, 2013)

Lithium Chloride Alleviates Neurodegeneration Partly by Inhibiting Activity of GSK3β in a SCA3 Drosophila Model - Dan-Dan Jia; Li Zhang; Zhao Chen; Chun-Rong Wang; Feng-Zhen Huang; Ran-Hui Duan; Kun Xia; Bei-Sha Tang; Hong Jiang (The Cerebellum, 2013)

Effect of combined treatment with recombinant interleukin-2 and allicin on pancreatic cancer - Cong-Jun Wang; Chao Wang; Jiang Han; Yong-Kun Wang; Lin Tang; Dong-Wei Shen; Yi Zhao; Rong-Hua Xu; Hui Zhang (Molecular Biology Reports, 2013)

Association of single-nucleotide polymorphisms in the STAT3 gene with autoimmune thyroid disease in Chinese individuals - Ling Xiao; Fatuma-Said Muhali; Tian-tian Cai; Rong-hua Song; Renming Hu; Xiao-hong Shi; Wen-juan Jiang; Dan-Feng Li; Shuang-tao He; Jian Xu; Jin-an Zhang (Functional & Integrative Genomics, 2013)

Identification and characterization of Pestalotiopsis spp. causing twig blight disease of bayberry (Myrica rubra Sieb. & Zucc) in China - Hai-Ying Ren; Gang Li; Xing-Jiang Qi; Li Fang; Han-Rong Wang; Ji-Guang Wei; Shaobin Zhong (European Journal of Plant Pathology, 2013)

What interests them in the pictures? — Differences in eyetracking between rhesus monkeys and humans - Ying-Zhou Hu; Hui-Hui Jiang; Ci-Rong Liu; Jian-Hong Wang; Cheng-Yang Yu; Synnöve Carlson; Shang-Chuan Yang; Veli-Matti Saarinen; Joshua D. Rizak; Xiao-Guang Tian; Hen Tan; Zhu-Yue Chen; et al. (Neuroscience Bulletin, 2013)

Meat quality traits of four Chinese indigenous chicken breeds and one commercial broiler stock - Rong-fa Guan; Fei Lyu; Xiao-qiang Chen; Jie-qing Ma; Han Jiang; Chao-geng Xiao (Journal of Zhejiang University-SCIENCE B, 2013)

Estimations of net primary productivity and evapotranspiration based on HJ-1A/B data in Jinggangshan city, China - Rong-hua Zhang; Rui Sun; Jun-ping Du; Ting-long Zhang; Yao Tang; Hong-wei Xu; Sheng-tian Yang; Wei-guo Jiang (Journal of Mountain Science, 2013)

Erratum to: The endoplasmic reticulum stress induced by highly expressed OsrAAT reduces seed size via pre-mature programmed cell death - Liping Zhang; Daiming Jiang; Jianlei Pang; Rong Chen; Xianghong Wang; Daichang Yang (Plant Molecular Biology, 2013)

The endoplasmic reticulum stress induced by highly expressed OsrAAT reduces seed size via pre-mature programmed cell death - Liping Zhang; Daiming Jiang; Jianlei Pang; Rong Chen; Xianghong Wang; Daichang Yang (Plant Molecular Biology, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Short-term effect of cultivation and crop rotation systems on soil quality indicators in a coastal newly reclaimed farming area - Rong-Jiang Yao; Jing-Song Yang; Tong-Juan Zhang; Peng Gao; Shi-Peng Yu; Xiang-Ping Wang (Journal of Soils and Sediments, 2013)

A novel role of ribonuclease inhibitor in regulation of epithelial-to-mesenchymal transition and ILK signaling pathway in bladder cancer cells - Xue Yao; Dan Li; Dong-mei Xiong; Lin Li; Rong Jiang; Jun-xia Chen (Cell and Tissue Research, 2013)

An exploratory analysis of vegetation strategies to reduce shallow landslide activity on loess hillslopes, Northeast Qinghai-Tibet Plateau, China - Xia-song Hu; Gary Brierley; Hai-li Zhu; Guo-rong Li; Jiang-tao Fu; Xiao-qing Mao; Qin-qin Yu; Na Qiao (Journal of Mountain Science, 2013)
Heavy summer rainfall induces significant soil erosion and shallow landslide activity on the loess hillslopes of the Xining Basin at the northeast margin of the Qinghai-Tibet Plateau. This study examines the mechanical effects of five native shrubs that can be used to reduce shallow landslide activity. We measured single root tensile resistance and shear resistance, root anatomical structure and direct shear and triaxial shear for soil without roots and five rootsoil composite systems. Results show that Atriplex canescens (Pursh) Nutt. possessed the strongest roots, followed by Caragana korshinskii Kom., Zygophyllum xanthoxylon (Bunge) Maxim., Nitraria tangutorum Bobr. and Lycium chinense Mill. Single root strength and shear resistance relationships with root diameter are characterized by power or exponential relations, consistent with the Mohr-Coulomb law. Root mechanical strength reflects their anatomical structure, especially the percentage of phloem and xylem cells, and the degree and speed of periderm lignifications. The cohesion force of root-soil composite systems is notably higher than that of soil without roots, with increasing amplitudes of cohesion force for A. canescens , C. korshinskii , Z. xanthoxylon , N. tangutorum and L. chinense of 75.9%, 75.1%, 36.2%, 24.6% and 17.0 % respectively. When subjected to shear forces, the soil without root samples show much greater lateral deformation than the root-soil composite systems, reflecting the restraining effects of roots. Findings from this paper indicate that efforts to reduce shallow landslides in this region by enhancing root reinforcement will be achieved most effectively using A. canescens and C. korshinskii .

Cadmium can induce alterations in the cellular localization and expression of three major nucleolar proteins in root tip cells of Vicia faba L - Rong Qin; Wusheng Jiang; Donghua Liu (Plant and Soil, 2013)

The association between CD14 gene C-260T polymorphism and coronary heart disease risk: a meta-analysis - Hong Pu; Jiong Yin; Yan Wu; Dongming Zhang; Yanian Wang; Rong Zhou; Lijuan Jiang; Yan Liu (Molecular Biology Reports, 2013)

Prostaglandin E2 receptor EP1 phosphorylate CREB and mediates MMP2 expression in human cholangiocarcinoma cells - Bo Sun; Rong Rong; Hai Jiang; Hai Zhang; YiPin Wang; Xiaoming Bai; Min Zhang; Juan Ma; Shukai Xia; Wei Shu; Li Zhang; Jing Leng (Molecular and Cellular Biochemistry, 2013)

Levosimendan versus dobutamine in critically ill patients: a meta-analysis of randomized controlled trials - Xuan Huang; Shu Lei; Mei-fei Zhu; Rong-lin Jiang; Li-quan Huang; Guo-lian Xia; Yi-hui Zhi (Journal of Zhejiang University-SCIENCE B, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Influence of ORM1 polymorphisms on the maintenance stable warfarin dosage - Lian Sheng Wang; Jing Jing Shang; Shu Ya Shi; Yan Qing Zhang; Jian Lin; Zhi Hua Guo; Yi Chen Wang; Jie Tang; Jie Liu; Ying Zi Liu; Zhi Li; Zhi Rong Tan; et al. (European Journal of Clinical Pharmacology, 2013)

Accelerated ovarian aging in mice by treatment of busulfan and cyclophosphamide - Yan Jiang; Jing Zhao; Hui-jing Qi; Xiao-lin Li; Shi-rong Zhang; Daniel W. Song; Chi-yang Yu; Jian-gang Gao (Journal of Zhejiang University-SCIENCE B, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Levels, sources and risk assessment of trace elements in wetland soils of a typical shallow freshwater lake, China - Haifeng Gao; Junhong Bai; Rong Xiao; Peipei Liu; Wei Jiang; Junjing Wang (Stochastic Environmental Research and Risk Assessment, 2013)

Identification and characterization of a gene encoding a putative lysophosphatidyl acyltransferase from Arachis hypogaea - Si-Long Chen; Jia-Quan Huang; Yong Lei; Yue-Ting Zhang; Xiao-Ping Ren; Yu-Ning Chen; Hui-Fang Jiang; Li-Ying Yan; Yu-Rong Li; Bo-Shou Liao (Journal of Biosciences, 2012)

Multiple time scale characteristics of rainfall and its impact on soil salinization in the typical easily salinized area in Huang-Huai-Hai Plain, China - Shi-Peng Yu; Jing-Song Yang; Guang-Ming Liu; Rong-Jiang Yao; Xiang-Ping Wang (Stochastic Environmental Research and Risk Assessment, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Comparative analysis of water stress-responsive transcriptomes in drought-susceptible and -tolerant wheat (Triticum aestivum L.) - Yong Chun Li; Fan Rong Meng; Chun Yan Zhang; Ning Zhang; Ming Shan Sun; Jiang Ping Ren; Hong Bin Niu; Xiang Wang; Jun Yin (Journal of Plant Biology, 2012)

Synthesis and anticonvulsant activity of 8-alkoxy-5,6-dihydro-4H-benzo[f][1,2,4]triazolo[4,3-a]azepine derivatives - Wen-Bin Zhang; Rong-Bi Han; Wei Zhang; Ri-Shan Jiang; Feng-Yu Piao (Medicinal Chemistry Research, 2012)

Effect of maternal age on the outcomes of in vitro fertilization and embryo transfer (IVF-ET) - JunHao Yan; KeLiang Wu; Rong Tang; LingLing Ding; Zi-Jiang Chen (Science China Life Sciences, 2012)

Recombinant human endostatin inhibits adjuvant arthritis by down-regulating VEGF expression and suppression of TNF-α, IL-1β production - Wei Hu; Li-Juan Xia; Fei-Hu Chen; Fan-Rong Wu; Jie Tang; Cun-Zhi Chen; Sheng Jiang; Hui-Hui Chen (Inflammation Research, 2012)

Recent developments in the detection of melamine - Yuan Liu; Ewen E. D. Todd; Qiang Zhang; Jiang-rong Shi; Xian-jin Liu (Journal of Zhejiang University-SCIENCE B, 2012)

A novel microbial fuel cell and photobioreactor system for continuous domestic wastewater treatment and bioelectricity generation - Haiming Jiang; Shengjun Luo; Xiaoshuang Shi; Meng Dai; Rong-bo Guo (Biotechnology Letters, 2012)

Interactions between CYP1A1 polymorphisms and cigarette smoking are associated with the risk of hepatocellular carcinoma: evidence from epidemiological studies - Lei Yu; Lei Sun; Yang-Fang Jiang; Bao-Ling Lu; De-Rong Sun; Li-Ying Zhu (Molecular Biology Reports, 2012)

Study on the effect of IRE1α on cell growth and apoptosis via modulation PLK1 in ER stress response - Xiangzhu Li; Huifang Zhu; Huizhe Huang; Rong Jiang; Wenjun Zhao; Yanna Liu; Jinghua Zhou; Feng-Jin Guo (Molecular and Cellular Biochemistry, 2012)

Characterization of the expression profile of calpain-3 (CAPN3) gene in chicken - Zeng-Rong Zhang; Qing Zhu; Yong-Gang Yao; Xiao-Song Jiang; Hua-Rui Du; Yi-Ping Liu (Molecular Biology Reports, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Influence of education and working background on physicians’ knowledge of secondary prevention guidelines for coronary heart disease: results from a survey in China - Yan-jun Gong; Tao Hong; Jie Jiang; Rong-hui Yu; Yan Zhang; Zhao-ping Liu; Yong Huo (Journal of Zhejiang University-SCIENCE B, 2012)

Introgression from cultivated rice influences genetic differentiation of weedy rice populations at a local spatial scale - Zhuxi Jiang; Hanbing Xia; Barbara Basso; Bao-Rong Lu (Theoretical and Applied Genetics, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Adsorption of Pseudomonas putida on soil particle size fractions: effects of solution chemistry and organic matter - Huayong Wu; Daihua Jiang; Peng Cai; Xingmin Rong; Ke Dai; Wei Liang; Qiaoyun Huang (Journal of Soils and Sediments, 2012)

Synthesis of (–)-arctigenin derivatives and their anticancer activity - Chen Gui-Rong; Cai Li-Ping; Dou De-Qiang; Kang Ting-Guo; Li Hong-Fu; Li Fu-Rui; Jiang Ning (Natural Product Research, 2012)

Decreased expression of Beclin-1 and LC3 in human lung cancer - Zi-Feng Jiang; Li-Jie Shao; Wei-Min Wang; Xue-Bo Yan; Rong-Yu Liu (Molecular Biology Reports, 2012)

Molecular characterization, expression pattern, and association analysis with carcass traits of the porcine SHIP2 gene - Qi Xiong; Jin Chai; Changyan Deng; Siwen Jiang; Xiaofeng Li; Xiaojun Suo; Nian Zhang; Qianping Yang; Yang Liu; Rong Zheng; Mingxin Chen (Molecular and Cellular Biochemistry, 2012)

Mitochondrial Permeability Transition Induced by Different Concentrations of Zinc - Xiao-Rong Liu; Jia-Han Li; Yue Zhang; Yu-Shu Ge; Fang-Fang Tian; Jie Dai; Feng-Lei Jiang; Yi Liu (The Journal of Membrane Biology, 2011)

Increased production of succinic acid in Escherichia coli by overexpression of malate dehydrogenase - Li-ya Liang; Rong-ming Liu; Jiang-feng Ma; Ke-quan Chen; Min Jiang; Ping Wei (Biotechnology Letters, 2011)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Isolation of a buprofezin co-metabolizing strain of Pseudomonas sp. DFS35-4 and identification of the buprofezin transformation pathway - Kai Chen; Xiao-Mei Liu; Rong Li; Yuan Liu; Hai Hu; Shun-Peng Li; Jian-Dong Jiang (Biodegradation, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

cDNA cloning and characterization of 5′ upstream promoter region of porcine mef2c gene - Min Liu; De Quan Xu; Jian Peng; Rong Zheng; Fenge Li; Si Wen Jiang (Molecular Biology Reports, 2011)

Normal epigenetic inheritance in mice conceived by in vitro fertilization and embryo transfer - Lei Li; Fang Le; Li-ya Wang; Xiang-rong Xu; Hang-ying Lou; Ying-ming Zheng; Jiang-zhong Sheng; He-feng Huang; Fan Jin (Journal of Zhejiang University-SCIENCE B, 2011)

LPS pretreatment ameliorates multiple organ injuries and improves survival in a murine model of polymicrobial sepsis - Dong-Wei Shi; Jing Zhang; Hong-Ni Jiang; Chao-Yang Tong; Guo-Rong Gu; Yuan Ji; Hanssa Summah; Jie-Ming Qu (Inflammation Research, 2011)

Expressions of thermostable bacterial cellulases in tobacco plant - Xi-ran Jiang; Xiao-ya Zhou; Wen-yan Jiang; Xiao-rong Gao; Wen-li Li (Biotechnology Letters, 2011)

Inhibition of oestrogen biosynthesis induces mild anxiety in C57BL/6J ovariectomized female mice - Fan-Tao Meng; Rong-Jun Ni; Zhi Zhang; Jun Zhao; Ya-Jing Liu; Jiang-Ning Zhou (Neuroscience Bulletin, 2011)

The complete mitochondrial genome of Spilonota lechriaspis Meyrick (Lepidoptera: Tortricidae) - Jin-Liang Zhao; Yan-Yan Zhang; A-Rong Luo; Guo-Fang Jiang; Stephen L. Cameron; Chao-Dong Zhu (Molecular Biology Reports, 2011)

Highly efficient and catalyst-free synthesis of substituted thioureas in water - Shi-Feng Gan; Jie-Ping Wan; Yuan-Jiang Pan; Cui-Rong Sun (Molecular Diversity, 2011)

Tongxinluo promotes mesenchymal stem cell tube formation in vitro - Xin-yang Hu; Wen-xia Wang; Min-jia Yu; Xian-bao Liu; Rong-rong Wu; Feng Gao; Xin Huang; Jiang Cao; Xiao-jie Xie; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Mimic peptides bonding specifically with the first and second extracellular loops of the CC chemokine receptor 5 derived from a phage display peptide library are potent inhibitors of experimental autoimmune encephalomyelitis - Hui-min Zheng; Yun Jiang; Ju-rong Wang; Xue-lian Gong; Bao-yu Guo (Inflammation Research, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Spectroscopic and Microscopic Studies on the Mechanisms of Mitochondrial Toxicity Induced by Different Concentrations of Cadmium - Yue Zhang; Jia-Han Li; Xiao-Rong Liu; Feng-Lei Jiang; Fang-Fang Tian; Yi Liu (The Journal of Membrane Biology, 2011)

Identification of the Biochemical Degradation Pathway of Triazophos and its Intermediate in Diaphorobacter sp. TPD-1 - Chengli Yang; Rong Li; Yao Song; Kai Chen; Shunpeng Li; Jiandong Jiang (Current Microbiology, 2011)

Molecular cloning, characterization and expression analysis of adenylosuccinate lyase gene in grass carp (Ctenopharyngodon idella) - Tian Yuan; Ji-Rui Gu; Wen-Bo Gu; Jiang Wu; Shao-Rong Ge; Heng Xu (Molecular Biology Reports, 2011)

Knockdown of ribonuclease inhibitor expression with siRNA in non-invasive bladder cancer cell line BIU-87 promotes growth and metastasis potentials - Junxia Chen; Xi Ou-Yang; Juan Gao; Jun Zhu; Xiaoyan He; Jiang Rong (Molecular and Cellular Biochemistry, 2011)

Biophysical Studies on the Interactions of a Classic Mitochondrial Uncoupler with Bovine Serum Albumin by Spectroscopic, Isothermal Titration Calorimetric and Molecular Modeling Methods - Yue Zhang; Jia-Han Li; Yu-Shu Ge; Xiao-Rong Liu; Feng-Lei Jiang; Yi Liu (Journal of Fluorescence, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Plantagiolide F, a minor withanolide from Tacca plantaginea - Jun-Yun Yang; Chang-Xiang Chen; Rong-Hua Zhao; Xiao-Jiang Hao; Hai-Yang Liu (Natural Product Research, 2011)

Methotrexate ameliorates pristane-induced arthritis by decreasing IFN-γ and IL-17A expressions - Wei-kun Hou; Lie-su Meng; Fang Zheng; Yu-rong Wen; Wen-hua Zhu; Cong-shan Jiang; Xiao-jing He; Yan Zhou; She-min Lu (Journal of Zhejiang University-SCIENCE B, 2011)

Serum complement C3 has a stronger association with insulin resistance than high sensitive C-reactive protein in non-diabetic Chinese - Bangqiong Wang; Qifu Li; Yuanjuan Jiang; Zhoujun Liu; Li Zhong; Rong Luo; Qingfeng Cheng; Hua Qing (Inflammation Research, 2011)

Seismic analysis of the active character of the Taihang Mountain piedmont fault - Ming-Cai Xu; Jing-Hua Gao; Li-Xin Rong; Guang-Ke Wang; Xiao-Jiang Wang (Applied Geophysics, 2010)

Assessment of effects of climate change and grazing activity on grassland yield in the Three Rivers Headwaters Region of Qinghai–Tibet Plateau, China - Jiang-Wen Fan; Quan-Qin Shao; Ji-Yuan Liu; Jun-Bang Wang; Warwick Harris; Zhuo-Qi Chen; Hua-Ping Zhong; Xin-Liang Xu; Rong-Gao Liu (Environmental Monitoring and Assessment, 2010)

Genetic Polymorphisms of the CACNA2D1 Gene and Their Association with Carcass and Meat Quality Traits in Cattle - Guan-Yu Hou; Zheng-Rong Yuan; Xue Gao; Jun-Ya Li; Hui-Jiang Gao; Jin-Bao Chen; Shang-Zhong Xu (Biochemical Genetics, 2010)

Hydrolytic Dechlorination of Chlorothalonil by Ochrobactrum sp. CTN-11 Isolated from a Chlorothalonil-Contaminated Soil - Bin Liang; Rong Li; Dong Jiang; Jiquan Sun; Jiguo Qiu; Yanfu Zhao; Shunpeng Li; Jiandong Jiang (Current Microbiology, 2010)

Effect of glycyrrhizin on the activity of CYP3A enzyme in humans - Jiang-Hua Tu; Yi-Jing He; Yao Chen; Lan Fan; Wei Zhang; Zhi-Rong Tan; Yuan-Fei Huang; Dong Guo; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2010)

Magma mixing origin for the post-collisional adakitic monzogranite of the Triassic Yangba pluton, Northwestern margin of the South China block: geochemistry, Sr–Nd isotopic, zircon U–Pb dating and Hf isotopic evidences - Jiang-Feng Qin; Shao-Cong Lai; Chun-Rong Diwu; Yin-Juan Ju; Yong-Fei Li (Contributions to Mineralogy and Petrology, 2010)

Normal Shear Stress and Vascular Smooth Muscle Cells Modulate Migration of Endothelial Cells Through Histone Deacetylase 6 Activation and Tubulin Acetylation - Yan-Hua Wang; Zhi-Qiang Yan; Ying-Xin Qi; Bin-Bin Cheng; Xiao-Dong Wang; Dan Zhao; Bao-Rong Shen; Zong-Lai Jiang (Annals of Biomedical Engineering, 2010)

Simvastatin attenuates TNF-α-induced growth inhibition and apoptosis in murine osteoblastic MC3T3-E1 cells - Yun-mei Yang; Wei-dong Huang; Qiang-min Xie; Zhe-rong Xu; Qi-jiang Zhao; Xi-mei Wu; Fen-fen Li; Xin-wei Dong (Inflammation Research, 2010)

Cadmium induction of lipid peroxidation and effects on root tip cells and antioxidant enzyme activities in Vicia faba L. - Shanshan Zhang; Huimin Zhang; Rong Qin; Wusheng Jiang; Donghua Liu (Ecotoxicology, 2009)

Hydraulic pressure inducing renal tubular epithelial-myofibroblast transdifferentiation in vitro - Fei-yan Li; Xi-sheng Xie; Jun-ming Fan; Zi Li; Jiang Wu; Rong Zheng (Journal of Zhejiang University-SCIENCE B, 2009)

Phase I clinical trial on intracoronary administration of Ad-hHGF treating severe coronary artery disease - Zhi-Jian Yang; You-Rong Zhang; Bo Chen; Shu-Lan Zhang; En-Zhi Jia; Lian-Sheng Wang; Tie-Bing Zhu; Chun-Jian Li; Hui Wang; Jun Huang; Ke-Jiang Cao; Wen-Zhu Ma; et al. (Molecular Biology Reports, 2009)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

Promotion of nicotine biosynthesis in transgenic tobacco by overexpressing allene oxide cyclase from Hyoscyamus niger - Keji Jiang; Yan Pi; Rong Hou; Lili Jiang; Xiaofen Sun; Kexuan Tang (Planta, 2009)

Induction of cytochrome P450 2B6 activity by the herbal medicine baicalin as measured by bupropion hydroxylation - Lan Fan; Jin-Chao Wang; Feng Jiang; Zhi-Rong Tan; Yao Chen; Qing Li; Wei Zhang; Guo Wang; He-Ping Lei; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

The sources and seasonal variations of organic compounds in PM2.5 in Beijing and Shanghai - Yilun Jiang; Ximei Hou; Guoshun Zhuang; Juan Li; Qiongzhen Wang; Rong Zhang; Yanfen Lin (Journal of Atmospheric Chemistry, 2009)

Molecular cloning and expression profiling of the first specific jasmonate biosynthetic pathway gene allene oxide synthase from Lonicera japonica - Keji Jiang; Yan Pi; Rong Hou; Hainian Zeng; Zhuoshi Huang; Zheng Zhang; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2009)

Ensemble hindcasts of ENSO events over the past 120 years using a large number of ensembles - Fei Zheng; Jiang Zhu; Hui Wang; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2009)

Cistanche deserticola Ma cultivated as a new crop in China - Rong Xu; Jun Chen; Shi-Lin Chen; Tong-Ning Liu; Wei-Cheng Zhu; Jiang Xu (Genetic Resources and Crop Evolution, 2009)

Hypertonic stimulation induces synthesis and release of glutamate in cultured rat hypothalamic astrocytes and C6 cells - Rong Cao; Shan Jiang; Li Duan; Ying-Fei Xiong; Bei Gao; Zhi-Ren Rao (Neuroscience Bulletin, 2008)

Association of MYF5 and MYOD1 Gene Polymorphisms and Meat Quality Traits in Large White × Meishan F2 Pig Populations - Min Liu; Jian Peng; De-Quan Xu; Rong Zheng; Feng-E Li; Jia-Lian Li; Bo Zuo; Ming-Gang Lei; Yuan-Zhu Xiong; Chang-Yan Deng; Si-Wen Jiang (Biochemical Genetics, 2008)

Preliminary studies on the chemical characterization and antioxidant properties of acidic polysaccharides from Sargassum fusiforme - Jing Zhou; Nan Hu; Ya-lin Wu; Yuan-jiang Pan; Cui-rong Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Dysregulation of CREB binding protein triggers thrombin-induced proliferation of vascular smooth muscle cells - Jing Chen; Hong Jiang; Lin Xu; Li-Hua Zhu; Lang Wang; Hua-Zhi Wen; Xiao-Rong Hu (Molecular and Cellular Biochemistry, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

A new dibenzofuran and other constituents from Ligularia caloxantha , a chinese medicinal plant - Shu-Yun Shi; Ming-Hui Hu; Di-Yao Wu; Chang-Xin Zhou; Jian-Xia Mo; Juan-Hua Xu; Liu-Rong Chen; Hui Dou; Hua Peng; Xiao-Jiang Hao; Joachim Stöckigt; Yu Zhao (Natural Product Research, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Identification of defense-related genes in rice responding to challenge by Rhizoctonia solani - Chang-Jiang Zhao; Ai-Rong Wang; Yu-Jun Shi; Liu-Qing Wang; Wen-De Liu; Zong-Hua Wang; Guo-Dong Lu (Theoretical and Applied Genetics, 2008)

Sensing Escherichia coli O157:H7 via frequency shift through a self-assembled monolayer based QCM immunosensor - Li-jiang Wang; Chun-sheng Wu; Zhao-ying Hu; Yuan-fan Zhang; Rong Li; Ping Wang (Journal of Zhejiang University-SCIENCE B, 2008)

Molecular cloning, characterization and expression of two rapeseed (Brassica napus L.) cDNAs orthologous to Arabidopsis thaliana phenylalanine ammonia-lyase 1 - Yu Ni; Hong-Lin Jiang; Bo Lei; Jia-Na Li; You-Rong Chai (Euphytica, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Cloning, expression, and pharmacological activity of BmK AS, an active peptide from scorpion Buthus martensii Karsch - Jian-Hua Shao; Yue-Qiu Wang; Xiao-Yan Wu; Rui Jiang; Rong Zhang; Chun-Fu Wu; Jing-Hai Zhang (Biotechnology Letters, 2007)

Heregulin protects mesenchymal stem cells from serum deprivation and hypoxia-induced apoptosis - Chun Gui; Jian An Wang; Ai Na He; Tie Long Chen; Rong Hua Luo; Jun Jiang; Xin Yang Hu; Xiao Jie Xie (Molecular and Cellular Biochemistry, 2007)

Akt/PKB interacts with the histone H3 methyltransferase SETDB1 and coordinates to silence gene expression - Haidong Gao; Zhigang Yu; Dongsong Bi; Liyu Jiang; Yazhou Cui; Jingzhong Sun; Rong Ma (Molecular and Cellular Biochemistry, 2007)

Knockout of the gene (ste15) encoding a glycosyltransferase and its function in biosynthesis of exopolysaccharide in Streptomyces sp. 139 - Qing-Li Sun; Ling-Yan Wang; Jun-Jie Shan; Rong Jiang; Lian-Hong Guo; Yang Zhang; Ren Zhang; Yuan Li (Archives of Microbiology, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Simultaneous biodegradation of methyl parathion and carbofuran by a genetically engineered microorganism constructed by mini-Tn5 transposon - Jiandong Jiang; Ruifu Zhang; Rong Li; Ji-Dong Gu; Shunpeng Li (Biodegradation, 2007)

Direct evidence that two cysteines in the dopamine transporter form a disulfide bond - Rong Chen; Hua Wei; Erik R. Hill; Lucy Chen; Liying Jiang; Dawn D. Han; Howard H. Gu (Molecular and Cellular Biochemistry, 2007)

Improved ENSO forecasts by assimilating sea surface temperature observations into an intermediate coupled model - Fei Zheng; Jiang Zhu; Rong-Hua Zhang; Guangqing Zhou (Advances in Atmospheric Sciences, 2006)

Roots of pioneer trees in the lower sub-tropical area of Dinghushan, Guangdong, China - Yan-ru Hao; Shao-lin Peng; Jiang-ming Mo; Xin-wei Liu; Zhuo-quan Chen; Kai Zhou; Jin-rong Wu (Journal of Zhejiang University-SCIENCE B, 2006)

Characterization of a novel impurity in bulk drug of lisinopril by multidimensional NMR technique - Dan-hua Wang; Sai-feng Pei; Ming-hua Zhou; Cui-rong Sun; Yuan-jiang Pan (Journal of Zhejiang University-SCIENCE B, 2006)

Changes in Soil Microbial Community Associated with Invasion of the Exotic Weed, Mikania micrantha H.B.K - Wei-hua Li; Cong-bang Zhang; Hong-bo Jiang; Guo-rong Xin; Zhong-yi Yang (Plant and Soil, 2006)

Extremely Rapid Extraction of DNA from Bacteria and Yeasts - Hai-Rong Cheng; Ning Jiang (Biotechnology Letters, 2006)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

FPF1 transgene leads to altered flowering time and root development in rice - Ming-Li Xu; Jia-Fu Jiang; Lei Ge; Yun-Yuan Xu; Hui Chen; Yuan Zhao; Yu-Rong Bi; Jiang-Qi Wen; Kang Chong (Plant Cell Reports, 2005)

Hydrogenation of ortho-nitrochlorobenzene on activated carbon supported platinum catalysts - Cheng-jun Jiang; Hong Yin; Zhi-rong Chen (Journal of Zhejiang University-SCIENCE B, 2005)

Complex influence of rice variety, fertilization timing, and insecticide on population dynamics of Sogatella furcifera (Horvath) , Nilaparvata lugens (Stl) (Homoptera: Delphacidae) and their natural enemies in rice in Hangzhou, China - Zeng-Rong Zhu; Jiaan Cheng; Ming-Xing Jiang; Xiao-Xi Zhang (Journal of Pest Science, 2004)

CHARACTERIZATION OF CULTURED INSECT CELLS SELECTED BY BACILLUS THURINGIENSIS CRYSTAL TOXIN - KAIYU LIU; BINGLIAN ZHENG; HUAZHU HONG; CAIFU JIANG; RONG PENG; JIANXIN PENG; ZEHUA YU; JIN ZHENG; HONG YANG (In Vitro Cellular & Developmental Biology - Animal, 2004)

The role of CYP2C19 in amitriptyline N-demethylation in Chinese subjects - Zhi-Ping Jiang; Yan Shu; Xiao-Ping Chen; Song-Lin Huang; Rong-Hua Zhu; Wei Wang; Nan He; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2002)

Expression of nucleolus, endosperm storage proteins and disease resistance in an amphiploid between Aegilops tauschii and Secale silvestre - Yang Zu-Jun; Li Guang-Rong; Jiang Hua-Ren; Ren Zheng-Long (Euphytica, 2001)